Integrating multi-omics reveals the protective effects of Lycium ruthenicum anthocyanins against radiation pneumonitis through gut-lung axis modulation - Kai Deng; Gaoyuan Zhang; Qiang Yan; Shuwen Han; Yunyao Wei; Ying Mei (Tissue and Cell, 2027)

Knockout of miR-200a/200b gene cluster improves sperm quality and heterozygous offspring fitness in yellow catfish (Pelteobagrus fulvidraco) - Qiuen Tan; Xu Wang; Qingqing Han; Youbo Jiang; Ran Miao; Wei Jiang; Jie Mei; Yang Xiong; Peipei Huang (Aquaculture, 2027)

Genome-wide association study reveals acute mountain sickness susceptibility in Chinese population - Xiangyi Zheng; Wenyu Song; Yuanfeng Li; Nandi Bao; Wenhui Li; Yang Liu; Juanjuan Liu; Bin Li; Xi Yang; Xiaobo Han; Jialin Wu; Liqun Ma; et al. (Molecular Genetics and Genomics, 2026)

IFI6 is associated with interferon activation and complement-associated immune responses in primary Sjögren’s disease - Yibing Han; Yikun Mei; Xiaoqin Meng; Minjv Zhang; Shuo Yang; Weizhi Wang; Wen Qiu; Zuoqing Dong (Functional & Integrative Genomics, 2026)

Development of an isoform-discriminating RT-qPCR assay for transcript-level profiling of human ASAH2 in colorectal cancer cell models - You Shan Ngui; Yi-Wen Huang; Shao-Chi Hung; Shih-Han Huang; Chieh-Ju Wen; Yi-An Chang; Hsing-Chen Wu; Hsiu-Chuan Chan; Mei-Lin Chan; Liang-Yin Ke; Hua-Chen Chan (Molecular Biology Reports, 2026)

Astaxanthin activates PI3K/AKT and AMPK signaling to alleviate oxidative stress and improve mouse oocyte In vitro maturation - Mei Zhou; Mengzhen Luo; Yueming Yuan; Liqin Han; Lin Chen; Shangquan Gan (Theriogenology, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Structure-regulated bio-inspired crochet-architectured textile for high-performance triboelectric energy harvesting and self-powered sensing - Bingyu Xu; Yuying Cao; Zhuangzhuang Han; Yulu Mei; Xu Song; Yahui Zhang; Jianye Niu; Qiming Liu; Tinghai Cheng; Jian Fang; Guilin Wen (Chemical Engineering Journal, 2026)

Elemental profiles and determinants of hair composition in residents of Nanning, China: insights from multivariate and comparative analyses - Ziyang Ding; Guilin Han; Hongcheng Mei; Rui Qu; Di Wang; Wenqian Sun; Na Mi; Jun Zhu (ENGINEERING Environment, 2026)

Scalable nanoconfined GO/SWCNT-OH membranes for efficient high-salinity organic wastewater treatment - Yechen An; Xiaoxu Gao; Jing-Long Han; Yuting Ning; Xinping Fu; Ruiyun Ren; Liang Mei; Wenli Jiang; Ruifeng Yan; Jun Cui; Yu Tao; Aijie Wang (Water Research, 2026)

Structurally diverse sesquiterpenoids from Curcuma longa and their anti-inflammatory activities - Guang-Han Li; Chun-Mei Qiu; Guang-Xu Wu; Miao Dai; Rui Feng; Hai-Guo Su; Liang Xiong (Phytochemistry, 2026)

Bench-scale proof-of-concept evaluation of whole-cell quorum quenching for fouling mitigation in a constant-flux membrane bioreactor. - Jiale Han; Xiaohui Chen; Xiaoyu Wang; Zimiao Yan; Xinjiao Dong; Yaru Li; Chenjie Mei; Shimei Ge (Journal of Water Process Engineering, 2026)

Colloidal biochar promotes microbial carbon dioxide fixation and enhances net soil organic carbon gain - Jia Bing Liu; Jia Wang; Wang Kai Tong; Han Tang; Mei Ru Yue; Piao Yi Jiang; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Chemical Engineering, 2026)

Mixed-gas nanobubble and colloidization stacked modification: Enhancing porous/chemical properties and endowing rapid adsorption function of biochar - Mei Ru Yue; Han Tang; Wang Kai Tong; Jia Bing Liu; Piao Yi Jiang; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Chemical Engineering, 2026)

A Shenling Baizhu San polysaccharide fraction (SLP-2)-based synbiotic alleviates lactose-induced gut dysfunction via a microbiota-metabolite-barrier axis - Li-Li Han; Chun-Feng Mei; Mengxiong Lu; Hong Xue (Food Research International, 2026)

AppleMM: A multimodal model for apple moldy core diagnosis via low-fielda NMR and expert text fusion - Yang Lv; ChangShuo Li; Mei Li; Yin Li; YeHui Han (Food Control, 2026)

Spirofluorene-grafted triazine branched poly(aryl piperidinium) anion exchange membranes for high performance water electrolysis and flow batteries - Wei-Feng Yang; Yong-Xin An; Rui Guo; Han Yan; Tian-Tian Wang; Chang-Ping Liu; Yong-Mei Tian; Wen-Bin Sun (Chemical Engineering Journal, 2026)

Optimizing nitrogen and legume green manure management enhances soil microbial network complexity and wheat productivity - Falong Hu; Minglong Zhang; Hao Lu; Zhilong Fan; Wen Yin; Hong Fan; Wei He; Yali Sun; Qiang Chai; Mei Han; Weidong Cao (Applied Soil Ecology, 2026)

Interspecific Competition Between Dominant Macrobenthic Species and Meretrix meretrix in a Clam Aquaculture Area - Haopeng Hu; Yan Liu; Longyu Liu; Peng Gao; Yanming Sui; Shuai Han; Mei Jiang; Lei Li (Fishes, 2026)
Understanding niche differentiation and interspecific coexistence patterns of macrobenthos provides critical references for ecological assessment of bivalve aquaculture. Seasonal field surveys (Autumn 2023–Summer 2024) across 12 sampling sites were conducted in an intensive Meretrix meretrix tidal flat farm in Rudong, Jiangsu. Synchronous water depth, sediment grain size and total organic carbon (TOC), and salinity were measured at each station to characterize habitat gradients; no unfarmed reference tidal flats were included, so all community patterns only reflect within-farm variation. The study area has sustained 10-year continuous bottom culture with baseline juvenile stocking density of 250 ind./m2 and twice-yearly manual harvesting. A total of 58 macrobenthic taxa were identified, and 13 dominant species were screened with a dominance index threshold Y > 0.02. All abundance data were fourth-root-transformed before Bray–Curtis community analysis to reduce bias of hyper-abundant taxa. Standardized Shannon niche breadth (0–1 normalized, r = 48 site–season composite units) and permutation-tested (999 replicates) Pianka niche overlap/similarity coefficients were calculated to quantify resource utilization similarity. Niche breadth ranged from 0.018 to 0.971, with farmed M. meretrix showing the maximum value, indicating broader seasonal resource adaptation. High niche overlap (>0.50) was detected between M. meretrix and four wild dominant species (Nephtys californiensis, Moerella iridescens, Lingula anatina, Umbonium thomasi). Notably, niche metrics derived solely from spatial abundance data cannot directly confirm interspecific competition or trophic segregation; the stable coexistence observed in our assemblage is tentatively hypothesized to be driven by vertical sediment partitioning and divergent feeding guilds based on published functional studies, without direct in situ trophic or stratified sediment evidence from this work. Hierarchical UPGMA clustering (0.35 Bray–Curtis distance threshold) and corrected NMDS ordination (48 site–season units, dominant-species fitted vectors) illustrated distinct functional groups. Based on the observed niche convergence among filter-feeding bivalves under local farming conditions, the range of 230–280 ind./m2 is presented as an observational reference. Controlled manipulative experiments with gradient stocking densities are needed to test whether this range can balance aquaculture yield and benthic biodiversity.

Biogeochemical cycling and fate of PAHs in coral reef ecosystem: Associations with coral holobiont microbial functional profiles - Mei Xiong; Minwei Han; Kefu Yu; Xuejiao Lin; Xiangrong Xu (Water Research, 2026)

Hexaconazole enantiomers drive the dissemination and risks of antibiotic resistance genes in the soil-earthworm system - Mei Shan; Jiao Wang; Weibin Chen; Conglai Zheng; Luqing Zhang; Yunlong Yu; Lingxi Han; Hua Fang (Pesticide Biochemistry and Physiology, 2026)

Compact urban development and green space accessibility: Micro-evidence from Chinese cities - Shuaishuai Han; Wan Li; Mei-Po Kwan; Bindong Sun; Qianqian Liu (Land Use Policy, 2026)

Evaluating and advancing large language models for soil and water conservation tasks: Case study of the black soil region - Junqi Zhao; Mengchen Ju; Mei Dong; Yichao Zhang; Kaijin Tang; Xin Liu; Ke Yang; Han Luo; Chutian Zhang; Gang Liu (Journal of Cleaner Production, 2026)

Nonlinear propagation of meteorological to agricultural droughts on the Mongolian Plateau: Probabilities, thresholds, and drivers - Li Mei; Han Aru; Siqin Tong; Yongfang Wang; Enliang Guo; Xiulian Bai; Altantuya Dorjsuren; Jinyuan Ren; Shan Yin; Yuhai Bao (Global and Planetary Change, 2026)

Fermentation modulates wheat germ gliadin-based nanodelivery systems loaded with wheat bran polyphenols: Physicochemical properties, interaction mechanism, and functional performances - Ai-Mei Liao; Shao-Kang Yang; Meng-Yu Gao; Siyi Han; Long Pan; Jayani Chandrapala; Haiyan Gao; Dandan Zhai; Jun-Wei Chen; Na Liu; Peng Li (Food Bioscience, 2026)

Nanodomain engineering via lattice softening enables high-efficiency electromagnetic absorption in hexagonal YMnO3 ferroelectrics - Mei Su; Shuhan Dai; Chao Guo; Chenglong He; Shengxi Feng; Yanhong Hu; Ningning Sun; Pei Han; Yong Li (Chemical Engineering Journal, 2026)

Calcination-modulated Cu redistribution in CuZr catalysts governs downstream ethylene glycol hydrogenolysis in dimethyl oxalate-to-ethanol conversion - Bolun Mei; Yueru Wang; Zhouxuan Zang; Ouyang Liu; Xu Liang; Guoji Liu; Han Sun; Xingchuan Yang; Li Xu (Chemical Engineering Journal, 2026)

Multi-omics Analysis Reveals the Protection of a Quadruple Probiotic Mixture in Experimental Autoimmune Hepatitis - Yu Chen; Shuhui Wang; Anzhuo Chen; Zhuoying Lin; Han Wang; Wanneng Li; Jun Liu; Jia Yao; Dean Tian; Yu Lei; Mei Liu (Probiotics and Antimicrobial Proteins, 2026)

Reduced exposure diminishes compound extreme climate risk for rice, yet yield losses intensify across Southeast Asia - Dianpeng Chen; Fei Cheng; Zhao Zhang; Jialu Xu; Matthew Tom Harrison; Huimin Zhuang; Jichong Han; Huaqing Wu; Saini Yang; Qinghang Mei; Corey Lesk; Fulu Tao (Agricultural and Forest Meteorology, 2026)

Interactive Toxic Impacts of Thermal Stress and Residual Chlorine on Growth, Nutritional Composition and Digestive Physiology in Meretrix meretrix - Shuai Han; Sitong Wang; Haopeng Hu; Wenping Yang; Shuo Qin; Peng Gao; Yanming Sui; Yebing Yu; Mei Jiang; Lei Li (Fishes, 2026)
Thermal elevation and residual chlorine pollution are two anthropogenic stressors that co-occur in estuarine waters affected by coastal power plant effluents. A 30-day exposure experiment was established with six treatment combinations comprising three temperatures (27 °C, 28 °C, and 30 °C) and two residual chlorine concentrations (0 mg/L and 0.02 mg/L) on Meretrix meretrix. Sampling was conducted on days 0, 10, 20 and 30 of the trial. The results indicated that elevated temperature (30 °C) significantly suppressed shell height and total body weight, while residual chlorine (0.02 mg/L) exerted time-dependent effects on shell length and width, with a significant interactive effect on shell length only at day 30. Crude lipid content declined with increasing temperature and residual chlorine exposure, whereas moisture and ash contents showed significant two-way interactions at all sampling time points. Intestinal amylase activity was continuously regulated by both stressors, with interactive responses on days 10 and 20, and was significantly suppressed under combined high temperature and residual chlorine stress. Collectively, we infer that combined exposure to elevated temperature and residual chlorine impairs shell growth, muscle biochemical composition and intestinal amylase activity of M. meretrix. Long-term experiments are required to further clarify the joint toxic effects of thermal stress and residual chlorine on the clam species.

Integrative bulk and single-cell transcriptomics identify a recurrence-prognostic risk model with exploratory associations with treatment-response phenotypes in colorectal cancer - Shuai Li; Jingxian Li; Xianyue Bu; Mei Han; Ganggang Shi (Human Cell, 2026)

Application of pollutant direct oxidative transfer process (DOTP) for chemical industrial wastewater treatment - Lei Lu; Dong-Mei Zhu; Ye-Cun Chen; Xu Cao; Ying-Jie Zhang; Han-Qing Yu (Water Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

From leaf to landscape: Leaf-based machine learning for genus and species-level mangrove classification of UAV-acquired hyperspectral data - Han Shen Lim; Wai Chong Chia; Yunli Lee; Mei-Hua Lin; Ong Cieh Wong; Stacey Sing; A Aldrie Amir; Kian Meng Yap (Remote Sensing Applications: Society and Environment, 2026)

GNPS-guided discovery of antifungal brominated metabolites from Chaetomium elatum FH-3 via NaBr-regulation and biotransformation - Jing-jing Su; Yin-han Teng; Bai-xue Yin; Hai-fang Wang; Yu-ze Li; Wei Wang; Xiao-mei Song; Dong-dong Zhang; Hao Fan (Phytochemistry Letters, 2026)

Trichodermine A, a new polyketide from the endophytic Trichoderma sp. MH550506.1 associated with Gardenia jasminoides - Yan-Li Zhang; Jie-Zhen Shi; Tong-De Zhao; Han-Wei Ruan; Ju-Cheng Zhang; Jin-Hua Yu; Da-Mei Wang; Li-Feng Wang; Liang Deng; Dong Gan; Zhong-Tao Ding (Phytochemistry Letters, 2026)

Integrated transcriptomic and metabolomic analyses reveal the differential response mechanisms of Gymnocypris eckloni gills to different intensities of acute heat stress - Wenzhuo Ban; Rongrong Liao; Yuting Duan; Mei Peng; Cheng Chen; RenYi Yang; Yinhua Zhou; ZhaoFang Han; Haiping Liu; Luo Lei; Chaowei Zhou (Journal of Thermal Biology, 2026)

Mining rare earth elements with ammonium sulfate as a leaching agent provokes a significant perturbation in soil microbial function - Yong-He Han; Ming-Zhu Zou; Xue-Mei Wei; Xian Chen; Li-Chao Tong; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2026)

Enantioselective migration, degradation, and metabolism of pyriproxyfen and its metabolites from tea garden to cup - Hongxia Li; Yue Hu; Yating Ning; Qing Zhong; Hezhi Sun; Xinru Wang; Mei Yang; Fengjian Luo; Li Zhou; Bingjun Han; Xinzhong Zhang (Food Chemistry, 2026)

Ultra-sensitive self-powered thermogalvanic hydrogel wristband enabled by resistance-gated strategy - Xuebiao Li; Ning Li; Suyi Wen; Jiahui Li; Xinru Yang; Mei Liu; Fei Han; Hulin Zhang (Chemical Engineering Journal, 2026)

Integrated Analysis of Physiological, Histological, and Transcriptomic Responses to Transport Density in Schizothorax nukiangensis - Jinlin Wang; Yuting Duan; Dapeng Gu; Hejiao Li; Luo Lei; Ning Wang; Wenjia He; Yinhua Zhou; Rongrong Liao; Mei Peng; Xinyu Liu; Zhaofang Han; et al. (Marine Biotechnology, 2026)

A Mid-Pleistocene Provenance Shift in the Bohai Strait at 0.94 Myr: Implications for Synergistic Controls on Yellow River Integration - Wei Xiong; Xi Mei; Long Huang; Naishuang Bi; Zongzhu Han; Yong Zhang; Zhonglei Wang (Journal of Ocean University of China, 2026)

Synthesis and biological evaluation of Phorbazole D analogues identify IO-5a as a promoter of hUC-MSC chondrogenic differentiation - Ai-zhu Wang; Xiao-mei Liu; Li-ming Zhang; Lu-lu Fu; Ping Li; Jie-ping Zhang; Hua Han (Molecular Diversity, 2026)

Aspartate Aminotransferase 10 Enhances Salt Tolerance in Poplar by Regulating Ion Homeostasis, Antioxidant Defense, and Transcriptional Remodeling - Mei Han; Xiaoning Liu; Yaxin Sun; Xiao Zeng; Fei Wu; Yujie Zhai; Tao Su (Journal of Plant Growth Regulation, 2026)

Liquid-liquid phase separation-driven enzyme catalysis for efficient biosynthesis of isoprenoid natural products - Han Wang; Bing-Bing Ma; Fei Cao; Ji-Jin Xie; Bei-Bei Wang; Shao-Yong Zhang; Ji-Dong Wang; Zha-Jun Zhan; Yu-Mei Ge; Xu-Ming Mao (Science China Life Sciences, 2026)

B-MARCO: a blockchain-driven multi-national auction and resource optimization framework for cross-border logistics and trade - Mei Sha; Shuang Li; Tao Zhang; Han Liu; Jianli Shen; Xiaohu Huang; Jiahua Hu (Frontiers in Marine Science, 2026)
Cross-border maritime logistics requires coordination among carriers, ports, customs authorities, and financial institutions, yet existing workflows are often constrained by fragmented regulatory data systems, inefficient dynamic capacity matching, and slow batch-based clearing. This paper proposes B-MARCO, a blockchain-driven multi-national auction and resource optimization framework for cross-border maritime logistics. B-MARCO integrates permissioned consortium coordination, rolling auction-based market clearing, a hybrid GA-GSA dispatching engine, and privacy-preserving access-control and compliance-verification components. The evaluation uses a semi-synthetic discrete-event simulation with a 7-day horizon, hourly decision intervals, 30 random seeds, and shared order streams across all configurations. Under a 5,000-orders/day workload, B-MARCO achieves a 91.80% transaction success rate and 21.53 h average end-to-end latency, compared with 60.09% and 36.66 h for the 24-hour batch-clearing baseline. Relative to a centralized rolling-matching baseline, it reduces average latency by 13.60%. The ablation results show that rolling auction clearing reduces latency, while smart-contract-based settlement-delay reduction is a major contributor to improved success and deadline performance. These findings support the value of combining rolling market clearing with spatial-temporal dispatch optimization in simulated cross-border maritime logistics, while the blockchain and cryptographic modules define the broader coordination, auditability, and data-governance architecture.

Quantum-Inspired Bio-Optimization for Robust Received Signal Strength-Based Underwater Target Localization in Noisy Stratified Acoustic Environments - Shiyi Han; Xiaojun Mei; Huafeng Wu; Jiangfeng Xian; Yuanyuan Zhang; Xinqiang Chen (Journal of Marine Science and Engineering, 2026)
Robust underwater target localization is essential for marine sensing and monitoring. However, RSS-based localization is affected by ray bending caused by sound-speed variations, anchor-node position perturbations, and non-line-of-sight (NLOS) propagation biases, resulting in a nonlinear and noise-sensitive estimation problem. To address these challenges, this paper proposes a Quantum-Inspired Animated Oat Optimization (QIAOO)-based localization algorithm for stratified underwater acoustic environments. First, a multi-error-coupled RSS localization model is established by jointly considering acoustic ray propagation effects, anchor-node perturbations, and NLOS propagation biases. Subsequently, the QIAOO algorithm is developed to solve the resulting nonlinear optimization problem, where quantum-inspired initialization, elite opposition-based learning, and a dynamic Cauchy–Gaussian mutation mechanism are incorporated to enhance search diversity and convergence performance. In addition, the Cramér–Rao Lower Bound (CRLB) is derived under the same localization model to provide a theoretical performance benchmark. Simulation results demonstrate that the proposed method outperforms benchmark algorithms in terms of localization accuracy and robustness under various scenarios.

Cell-Type-Specific Calibration of Mitochondrial Ubiquitination in Stem Cell Fate Decisions - Hao-Cheng Liu; Si-Yuan Chen; Nan-Nan Yu; Mei-Hua Jin; Hu-Nan Sun; Ying-Hao Han (Stem Cell Reviews and Reports, 2026)

Compatibility of three adjuvants with Cordyceps fumosorosea and their synergistic effects on controlling the diamondback moth, Plutella xylostella - Mei-Qiong Xie; Long-Jiang Wang; Yong-Qiang Han; Jin-Cui Chen; Li-Ying Cao; Shi-Chuan Luo; Fan-Fan Jiao; Shu-Jun Wei (Crop Protection, 2026)

Foc4-Ap1, a putative aspartic protease of Fusarium oxysporum f. sp. cubense race 4, targets banana NAD(P)H-quinone oxidoreductase subunit S to promote virulence - Ru-Jing Zeng; Wen-Jing Chen; Zheng Li; Huan-Cai Ou; Qing-Dong Chen; Mei Luo; Han-Da Song; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2026)

Field validation of a multi-functional dry habitat for subsea pipeline maintenance - Jin Guo; Jiawang Chen; Bo Han; Haiyang You; Yuan Lin; Deqing Mei (Ocean Engineering, 2026)

Quantifying provincial contributions to carbon intensity reduction in China’s construction industry: ML-assisted analysis via an integrated LMDI-ANCOVA framework - Yunxiao Yuan; Marko Lovrić; Han Zhang; Muhammad Umer; Xiaoyu Yang; Yu Xu; Mei Qu (Energy and Buildings, 2026)

Baseline and fractionation of rare earth elements in hair of urban residents in Nanning, South China - Hongcheng Mei; Ziyang Ding; Guilin Han; Rui Qu; Xiaoyu Hu; Di Wang; Zhaowei Jie; Wenqian Sun; Jun Zhu (Environmental Geochemistry and Health, 2026)

Targeting the fibrosis-inflammation-oxidative stress axis: multifaceted mechanisms of salidroside in chronic organ fibrosis - Ai-Qian Liu; Jongwon Byun; Nan Nan Yu; Mei-Hua Jin; Ying-Hao Han; Dong Seok Lee; Dong-Hun Lee; Hu-Nan Sun (Apoptosis, 2026)

Study on the mechanisms of action of Ephedra sinica Stapf extract in treating acute exacerbation of chronic obstructive pulmonary disease (AECOPD) - Zhe Li; Gui-yun Qian; Ye Yao; Mei-yan Wei; Wei Han (Natural Product Research, 2026)

The eastern branch fault model of the Tanlu Fault zone and its controlling effect on hydrocarbon accumulation: A case study of southern section of Bohai Sea - Ji-mei Deng; Shi-qiang Xia; Wen-hui Huang; Peng Wu; Gang Han; Hong Li (Applied Geophysics, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

A new seco -norlignan and a rare ring B aromatic 1(10→6) abeo -ergostane-type steroid from Tarlmounia elliptica - Qiao-Long Hao; Han-Mei Bai; Lei Miao; Shuang Yao; Chuan-Rui Zhang (Natural Product Research, 2026)

Macro-micro mechanical properties and modified damage constitutive model of marine soil after cement reinforcement - Xiao-Hu Zhang; Jian-Min Yang; Han-Lin Wang; Cheng-Shuang Yin; Liu-Mei Wei; Wen-Han Yu; Kamchibek Kozhogulov (Marine Georesources & Geotechnology, 2026)

Endothelial FAM171A2 is required for maintaining autophagy flux and blood–brain barrier integrity - Si-Da Han; Ning Ding; Jia-hui Huang; Yi-Wei Feng; Kai-Min Wu; Shi-Dong Chen; Qiang Dong; Mei Cui; Ting-ting Wang; Peng Yuan; Jin-Tai Yu (Science Bulletin, 2026)

Construction of PtIn@S-1 || hollow H-ZSM-5 composite catalyst for propane aromatization - Zhao Ma; Sen Wang; Shiying Li; Zhikai Li; Han Wang; Qi Li; Baichao Li; Dezhi Shi; Pengfei Wang; Mei Dong; Weibin Fan (Fuel, 2026)

A dual-functional fluorescent sensor based on a single soybean-derived carbon dots for discrimination and quantification of tetracyclines in food - Xin Lin; Jiaqi Wang; Meiqi Xia; Shuang Li; Yixin Xu; Jingyi Sun; Han Leng; Tianqun Song; Yanzhi Xing; Mei Yang (Food Chemistry, 2026)

A Gegenbauer-Galerkin spectral scheme for three-dimensional incompressible Hall-magnetohydrodynamics system - Shimin Guo; Han Jiang; Pengrui Zhou; Liquan Mei (Computer Physics Communications, 2026)

Synergistic nanoengineering of a bio-based hybrid for superior flame-retardant and robust TPU composites - Qian Geng; Yihui Xia; Dianpu Ma; Zhuoxi Han; Zhiyong Xu; Feng Wu; Yuhui Xie; Yi Mei; Delong Xie; Dong Feng (Chemical Engineering Journal, 2026)

λ-Carrageenan inhibits African swine fever virus infection potentially through its interaction with the viral envelope protein CD2v - Kun Han; Limeng Sun; Can Jin; Siqi Wan; Caiqin Cao; Yulu Yue; Man Lu; Xiaotong Wang; Yi Zheng; Hailong Liu; Yilin Guo; Dagang Tao; et al. (Carbohydrate Polymers, 2026)

ErbB4 in the Dorsolateral Prefrontal Cortex is Required for Sensory Gating and Working Memory in Monkey - Minzhe Yang; Yingying Han; Hongfei Zhang; Chaolin Ma; Lin Mei; Baoming Li (Neuroscience Bulletin, 2026)

Corrigendum to “Acanthoic acid protectsagainst ethanol-induced liver injury: Possible role of AMPK activation and IRAK4 inhibition” [Toxicol. Lett. 281 (2017) 127–138] - You-Li Yao; Xin Han; Jian Song; Jing Zhang; Ya-Mei Li; Li-Hua Lian; Yan-Ling Wu; Ji-Xing Nan (Toxicology Letters, 2026)

Carnian (lower Upper Triassic) conodont biostratigraphy and carbon isotope records of the Hanzeng section, western Sichuan Basin, South China - Chen Han; Shunling Wu; Zhengyi Lyu; Qiuyi Mei; Laishi Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Meta-analysis of the prevalence, serotype distribution, and antimicrobial susceptibility of Salmonella spp. from eggs in China - Shenfei Zhang; Jiaqi Ma; Tianxi Chen; Mengting Han; Xiaoqi Wang; Min Li; Mei Li; Chenyang Cao; Shenghui Cui; Baowei Yang (International Journal of Food Microbiology, 2026)

Three-dimensional crustal velocity and density structures around the eastern Central Asian orogenic belt and implications for the Solonker suture and metallogenic background - Lianghui Guo; Yang Chen; Mei Han; Xueyang Bao (Gondwana Research, 2026)

Genome-characterized Lacticaseibacillus rhamnosus Hao9 alleviates DSS–induced chronic low-grade inflammation and modulates the gut microbiota - Minxin Yang; Jinyan Yu; Shengliang Wang; Xianyan Liao; Mei Han; Junyi Huang (Food Bioscience, 2026)

Characterization of volatile aroma profiles and identification of key stale odorants in albino green tea during accelerated shelf-life storage - Yi-Ming Yang; Bin-Hui Liao; Jin-Miao Zhao; Ying-Gou Zhao; Xiao-Gan Chen; Wen-Han Fan; Li-Qing Mei; Si-Qi Zhang; Hao-Wei Guo; Shu-Ying Gong; Jing-Fei Zhang; Fang-Yuan Fan (Food Control, 2026)

Allergen regulations for non-prepacked foods in the food service sector: A global scoping review - Mariana Scudeller Vicentini; Carolina Neves Freiria; Jan Mei Soon-Sinclair; Iain Malcolm Ferris; Lisa Marie Winnall; Han Wen; Diogo Thimoteo da Cunha (Food Policy, 2026)

Unlocking closed-loop recycling of spent LiFePO4 batteries via photocatalytic leaching: Efficient lithium recovery and mechanistic insights - Yinzhuang Fang; Shuya Chang; Yurong Han; Yifeng Han; Lina Jia; Mingyang Wu; Xianbao Wang; Rui Xia; Tao Mei (Chemical Engineering Journal, 2026)

Genetic deletion of miR-200a/200b increases growth and feed conversion efficiency in yellow catfish - Xu Wang; Yan Xie; Qiaohong Lin; Yang Xiong; Ying Liu; Si Ge; Qiuen Tan; Zhipeng He; Youbo Jiang; Qingqing Han; Shuang Jin; Peipei Huang; et al. (Science China Life Sciences, 2026)

Multi-element response characteristics of Athyrium yokoscense revealed by a spore-derived culture system - Ning Han; Kasane Sato; Chihiro Inoue; Mei-Fang Chien (Plant and Soil, 2026)

Synergistic removal of NOx and CO via CO-SCR over hydrothermally anchored Iridium in SAPO-34 - Lu Zhao; Mei Hong; ChaoQiu Chen; JianFeng Zheng; Xili Tong; XiaoJin Han (Journal of Environmental Chemical Engineering, 2026)

Effects of different ecological restoration approaches on soil nitrogen cycling in abandoned mine lands on the alpine plateau - Lili Ma; Wenchao Yan; Fuzhen Jiang; Zhengpeng Li; Mei Han; Zhe Wang; Kaibin Qi (Journal of Environmental Management, 2026)

Metabolomics-based reveals the relation between internal metabolism and storage quality of sesame harvested by machine at different speeds - Ling-Yu Qu; Shu-Guang Gao; Di-Chen Gong; Jing-Wen Zhao; Yun-Xuan Hu; Xiao-Tian Zhu; Han-Zhe Zhang; Hua-Min Liu; Hong-Mei Miao (Food Research International, 2026)

Fermented red quinoa (FRQ) effectively mitigates chronic alcohol-induced cognitive impairment and hepatic steatosis through multi-mechanistic pathways - Zi-Han Lin; Zhaohui Wang; FenFen Wei; Xinyao Zhu; Junwei Ma; Yan Wu; Song-Mei Chen; Li-Hua Song (Food Research International, 2026)

Prevalence and genomic characterization of pathogenic blaNDM-positive Escherichia coli from retail meats: The first large-scale study in 22 cities of China - Mei-Jun Chu; Ming Zou; Han Wang; Junjie Wang; Zhiyuan You; Yan Li; Bao-Tao Liu (Food Microbiology, 2026)

EBV-driven rewiring of Drp1-Mediated mitophagy exacerbates trichloroethylene-induced hypersensitivity syndrome - Yuyan Xu; Shuai Liu; Mengnan Yi; Wen Gu; Yican Wang; Guoyong Mei; Jun Han; Yufei Dai (Environmental Pollution, 2026)

Crustal three-dimensional architecture of the Yarlung Zangbo magmatic belt: Insights from magnetic inversion - Dingmei Liu; Lianghui Guo; Mei Han (Science China Earth Sciences, 2026)

Ex vitro rooting of Spathiphyllum cannifolium in a microponic system: optimization of key physicochemical factors - Peng-Yu Zhang; Xue-Han Zong; Shuo Yu; Yin-Ji Jiang; Xin-Mei Jin; Song-Hao An; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Mobilization and redistribution of Arsenic during intense weathering of granite, eastern Tibetan Plateau, China - Zi-Han Xia; Jun-Wen Zhang; Na Wu; Mei-Li He; Qi Liu; Zhi-Qi Zhao (Environmental Geochemistry and Health, 2026)

Novel Models to Predict Pregnancy for Patients Receiving In-Vitro-Fertilization Embryo Transfer: The Significance of Clinical Indicators and Key Gene Expression in the Endometrium - Cheng Shi; Yan-Bin Wang; Huan Shen; Fu-Mei Gao; Min Fu; Xi Chen; Hong-Jing Han (Biochemical Genetics, 2026)

Allelopathic and phytotoxic activity of essential oil of Elaeagnus angustifolia flowers and its major constituents on Amaranthus retroflexus and Lolium perenne - Caixia Han; Yu Mei; Nigora Kuchkarova; Zokir Toshmatov; Shijie Fang; Hua Shao (Natural Product Research, 2026)

Trace carbonyls in water reuse: Structure-dependent multi-barrier penetration and enhanced deep mineralization via dual-radical oxidation synergism - Yun-Peng Wu; Qian-Yuan Wu; Zi-Bo Jing; Yu-Ming Tian; Jiang-Lei Xiong; Mu-Da Han; Sheng-Mei Li; Er-Dong Wang; Wen-Long Wang (Water Research, 2026)

Ultra-low loading bio-based nanoarchitecture enables fire-safe TPU with exceptional smoke suppression - Zhuoxi Han; Dong Feng; Yihui Xia; Yuqi Lu; Yuhui Xie; Feng Wu; Yi Mei; Hongying Su; Delong Xie (Chemical Engineering Journal, 2026)

Cadmium absorption and dehydrin gene expression revealed tolerance to cadmium stress in the rice genotypes - Adnan Khan; Qurban Ali; Asmat Ali; Mei Han; Nadir Zaman Khan; Waqar Ali; Abdulwahed Fahad Alrefaei; Mikhlid H. Almutairi; Atif Ali Khan Khalil; Sajid Ali (Cereal Research Communications, 2026)

Distinct ecology patterns of bacterial generalists and specialists provide fresh insights into the management of ship ballast sediments - Baoyi Lv; Shenglong Mei; Guolin Kan; Yangchun Han; Changhai Jiang; Yuxue Cui; Jianhong Shi (Marine Pollution Bulletin, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Microbiota and free amino acid dynamics during aging of Cougar Gold cheese: insights into the puffy defects - To Chiu; Bing Han; Alejandro Bravo Iniguez; Mei-Jun Zhu (International Journal of Food Microbiology, 2026)

Edge activation-oxidation strategy enhances sodium storage performance and economic viability of spent battery graphite - Yifeng Han; Hao Tan; Hongling Yao; Shuya Chang; Zihan Huang; Zhaojun He; Anan Zuo; Yong Ding; Rui Xia; Tao Mei (Chemical Engineering Journal, 2026)

Innovative cellulose-mediated liquid metal composites hydrogel with adhesive and mechanical-thermal multimodal sensing capabilities for smart wearable devices - Jingren Ma; Shengnan Li; Yuanjie Gu; Danning Wang; Weisheng Yang; Changtong Mei; Xinwu Xu; Huining Xiao; Jingquan Han (Chemical Engineering Journal, 2026)

High-latitude species with temperature-dependent sex determination will face an elevated risk from climate change - Jun Zhong; Shan Li; Ming-Shen Hong; Mei-Lian Song; Han-Yi Lan; Xiang Ji (Biodiversity and Conservation, 2026)

Attached microalgae-simulated plants enhanced multiple-pollutant removal in a tidal flow constructed wetland: quantified efficiencies, pathways, and biological mechanisms - Shu-Han Ge; Mei-Zi Yang; Wei-Yi Qian; Lin-Lan Zhuang; Hai-Ming Wu; Zhuo Chen; Xiao-Xiong Wang; Jian Zhang (Water Research, 2026)

Metagenomics insights into the functional traits and risk surveillance of ballast water microbiome from a genome-centric perspective - Baoyi Lv; Guolin Kan; Shenglong Mei; Yangchun Han; Changhai Jiang; Yuxue Cui; Jianhong Shi (Process Safety and Environmental Protection, 2026)

Caseazins R−Y, cytotoxic podocarpane diterpenoids from Casearia kurzii - Xue-Wen Wu; Qiong Wei; Xia Pu; Chun-Mei Cha; Rui Li; Yin-Qiao Huang; Rui-Han Zhang; Xiao-Li Li; Hong-Liang Li; Wei-Lie Xiao (Phytochemistry, 2026)

Distinct links between climate warming, mariculture activities, and coastal benthic ecosystem change - Yong Xu; Jixing Sui; Lin Ma; Jinbao Wang; Qi Kou; Zhibin Gan; Lin Gong; Mei Yang; Qingxi Han; Xinzheng Li; Dong Dong (Journal of Environmental Management, 2026)

Construction and optimization of Liuzhuang coal molecular model for wettability mechanism analysis - Fuhong Hu; Fangwei Han; Kunlang Wu; Mei Liu; Guirui Niu; Diandian Xue; Hetang Wang (Fuel, 2026)

Addition of chemical oxidation catalysts accelerates heating and humification in biodrying-enhanced composting process for kitchen waste - Chenxuan Fang; Jiefei Mo; Yuzhou Long; Yujie Han; Yong Qin; Qingqing Mei; Weixiang Wu (Bioresource Technology, 2026)

Quorum sensing enhances extracellular electron uptake of electrotrophic biofilm via metabolic cascade for aerobic biochemical oxygen demand sensing - Tiantian Yang; Yilian Han; Mou Zhang; Linxiao Li; Mei Chen; Nan Li; Xin Wang (Bioresource Technology, 2026)

Aboveground living plant-based methane production does not dominate methane emissions in terrestrial ecosystems - Zhi-Ping Wang; Luke C. Jeffrey; Josep Barba; Katerina Machacova; Xi-Mei Zhang; Ang Li; Shi-Jie Han (Planta, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

Sensitive MicroRNA detection via single nanoparticle collision electrochemistry using DNA-functionalized silver nanoparticles - Xiao-Han Yuan; Shuo Zhang; Jian-Hua Zhang; Xin-Yue Meng; Dian-Mei Song; Wen-Min Zhang (Analytica Chimica Acta, 2026)

Integrated multi-trophic aquaculture of sandfish Holothuria scabra with hard clam Meretrix taiwanica and milkfish Chanos chanos under environmental stress - Po-Kun Tseng; Min-Luen Tsai; Li-Xi Xu; Meei-Mei Chen; Yin-Hao Lai; Yu-San Han; Feng-Jie Su (Aquaculture International, 2026)

BET bromodomain inhibition potentiates antitumor activity of tumor-associated macrophages and enhances anti-CD47 immunotherapy in triple-negative breast cancer - Fuxing Mei; Delin Li; Nannan Zhu; Tao Zhu; Han Xie; Yue Liu; Lei Chen; Xiao Zhang; Wei Ji (Apoptosis, 2026)

Multistep-Ahead Forecasting of Chlorophyll Concentration Based on Dynamic Collaborative Attention Network - Lei Wang; Guodong Han; Ping Wu; Jie Mei; Zhenyu Lin; Shengming Cheng; Xianhua Wei; Xu Yang; Chuxu Xiong; Shaoyang Dai; Ying Zhao (Journal of Marine Science and Engineering, 2025)
Multistep-ahead forecasting of chlorophyll concentration is of great significance in red tide early warning systems. Existing methods often neglect the potential adverse interactions between non-predictive variables and chlorophyll while failing to fully utilize the effective information in historical decoder units. To address these issues, this paper proposes a Dynamic Collaborative Attention Network (DCAN) model for chlorophyll concentration forecasting, which consists of two components: a Two-Stage Variable Embedding Network (TSVEN) and a Dynamic Attention Network (DyAN). The TSVEN can identify the non-predictive variables that have the most significant impact on chlorophyll changes and generate corresponding spatial vectors from them, thereby alleviating the information conflict between chlorophyll and non-predictive variables. The DyAN integrates a context attention module and a filtering gate mechanism. The former effectively extends the forecasting time range by dynamically retrieving historical decoder states, while the latter selectively integrates historical decoder information, thereby improving the reliability of model decisions and prediction accuracy. Experimental results based on real datasets show that the proposed model outperforms the current state-of-the-art methods in chlorophyll concentration forecasting tasks and exhibits good interpretability.

Plastisphere fungi from Yunnan, China: hydrolytic enzyme screening and taxonomic insights - Xue-Mei Chen; Jaturong Kumla; Pratthana Kodchasee; Wenhua Lu; Li-Su Han; Dongqin Dai; Abdallah M. Elgorban; Meiyan Han; Nakarin Suwannarach; Saowaluck Tibpromma (New Zealand Journal of Botany, 2025)

Quantum-inspired optimal sensor deployment for 3D localization under uncertain target in stratified oceanic environment - Xiaojun Mei; Huafeng Wu; Fahui Miao; Dezhi Han (Ocean Engineering, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Redox-regulated plastoglobule ABC1K1–ABC1K3 kinase complex controls plastoquinone mobilization for chloroplast photosynthetic adaptation to red light - Mei Yang; Hao Huang; Chao Xu; Xue Han; Guochen Qin; Le Chang; Fang Lin; Xuncheng Wang; Hang He; Xing Wang Deng (Molecular Plant, 2025)

A vulnerability assessment with freight flow data of railway freight transportation network in Northeast China - Yuanting Jiang; Mei Han; Chao Chen; Yanhui Han; Fuhao Yu; Xiwei Mi (Journal of Transport Geography, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Efficient removal of nitrogen, phosphorus and antibiotics in freshwater aquaculture wastewater using a novel hybrid aeration biological filter - Dongyu Xia; Weina Dou; Yawei Tian; Lei Zhang; Cai Wang; Yong Wang; Jingyi Zhang; Yutong Han; Yanyan Xiao; Xu Yang; Xiang Mei (Journal of Environmental Management, 2025)

Mixed gas nanobubbles promote microbial CO2 fixation: Universal verification, mechanism, and application - Jia Wang; Piao Yi Jiang; Jia Bing Liu; Han Tang; Wang Kai Tong; Jia Jie Zou; Mei Ru Yue; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Management, 2025)

Electrochemical formation of UO2 on 3D flower carbon film electrode in LiCl-KCl system - Quanxing Liu; Mei Li; Rugeng Liu; Meng Zhang; Wei Han (Journal of Environmental Chemical Engineering, 2025)

Interpretability analysis of rockburst risk prediction in coal mines based on machine learning-SHAP - Mei Hongjia; Wang Yanbing; Zhang Xiangliang; Wang Jianlong; Qi Gaowei; Han Yingying; Zheng Wenjing (Journal of Applied Geophysics, 2025)

Comparative genomic analysis of ciprofloxacin-resistant Escherichia coli from retail chicken in Shaanxi, China and global sources - Jiali Sun; Mengting Han; Qiuping Yang; Mei Li; Siyue Wang; Min Li; Wei Zhou; Shenghui Cui; Baowei Yang (Food Research International, 2025)

In vitro and in vivo assessments of hypothermal condition on Vibrio alginolyticus virulence factor and immunity of Litopenaeus vannamei - Zhong-Wen Chang; Chin-Chyuan Chang; Mei-Han Lu (Fish & Shellfish Immunology, 2025)

Continuous flow synthesis of mononitrotoluene with high selectivity using acetyl nitrate in the microreactor - Rao Chen; Yuyang Xu; Mei Han; Yingjiang Lian; Fengjun Jiao; Chaoqun Yao; Guangwen Chen (Chemical Engineering Journal, 2025)

Copper single-atom MAX phase as a peroxidase and photothermal/photodynamic nanoplatform for facilitating diabetic wound repair - Shuairu Zhu; Mei Yang; Qiang Zhou; Youbing Li; Qiwei Guo; Mi Su; Yilin Shen; Minjin Wang; Xinyi Luo; Han Luo; Feng Gong; Xuping Sun; et al. (Chemical Engineering Journal, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

Predicting and interpreting nitrogen removal performance and functional microbial abundance of single-stage partial nitrification and anammox system using machine learning methods - Xiulin Mu; Fangxu Jia; Shengming Qiu; Yiran Li; Ning Mei; Xingcheng Zhao; Baohong Han; Xiangyu Han; Jingjing Zhang; Hong Yao (Bioresource Technology, 2025)

Carbon sequestration potentials in paddy soil: Rice straw phytolith and phytolith carbon with protozoa abundance - Tianyi Shi; Pan Zhou; Wenyuan Wang; Chunyu Hou; Mei Han; Xuming Pan; Liangzi Cao; Jianye Li; Shichen Sun; Li Wang; Duu-Jong Lee (Bioresource Technology Reports, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Pan-genomic insights into RLK family evolution and adaptation in Dioscorea alata - Zhi-Yan Wei; Sai-Xi Li; Ming-Han Li; Jie Tang; Yu-Qian Jiang; Xin-Yu Lu; Yan-Mei Zhang; Jia-Yu Xue (Plant Molecular Biology, 2025)

Human umbilical cord mesenchymal stem cells improve the ovarian function through oxidative stress-mediated PERK/eIF-2α/ATF4/CHOP signaling in premature ovarian insufficiency mice - Pei-Ling Wu; Shi-Huan Tang; Han-Yue Wang; Hong-Mei Zhang; Lu Peng; Yao Liu; Yuan Yang; Chun-Bing Zheng; Xian-ping Zhang (Molecular Biology Reports, 2025)

Nonlinear Consolidation Analysis of Soft Soils Considering Boundary Time Effect and Non-Darcian Flow Under Time-Dependent Loading - Han Su; Mengfan Zong; Wenbing Wu; Yi Zhang; Jin Wu; Guoxiong Mei (Geotechnical and Geological Engineering, 2025)

Scalable production of Actinidia arguta adventitious roots in air-lift bioreactors and their antibacterial efficacy against Staphylococcus aureus - Wen Jiang; Xue-Han Zong; Song-Hao An; Jing-Run Xiu; Shuo Yu; Ke-Xin Zhang; Yue-Jun Hao; Mei-Yu Jin (In Vitro Cellular & Developmental Biology - Plant, 2025)

Phylogenetic analysis and morphological evidence reveal a new genus Motuoorchis in subtribe Goodyerinae (Orchidaceae) - Yue Liu; Mei Sun; Chen Xing Li; Xiang Feng Han; Zhen Liu; Huai Zhen Tian (Plant Biosystems, 2025)

Multi-criteria carbon emission allowance allocation for liner shipping companies in China: An integrated approach based on composite indicators and zero-sum gains DEA - Mo Zhu; Yuquan Du; Mei Sha; Yiwen Jiang; Zhongdai Wu; Bing Han (Ocean & Coastal Management, 2025)

Effects of vegetation restoration on infiltration patterns and preferential flow in semi-arid areas with shallowly buried soft bedrock (Pisha sandstone) in China - Jian Hu; Yunzhuo Ren; Mei Tang; Zhiao Zhang; Kaiqi Yang; Qing Zhen; Fengpeng Han (Journal of Hydrology, 2025)

The potential of anthraquinone-2-sulfonate (AQS) for “shell breaking” of iron-coated denitrification granular sludge - Xin-Rui Zhang; Zhi-Han Xi; Zi-Jun Yan; Xin-Tao Liu; Ying Wang; Run-Mei Li; Zi-Yue Li; Ke-Yu Wu; Ren-Cun Jin; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Management, 2025)

Achieving partial nitritation-anammox in membrane-aerated biofilm reactor by hydroxylamine addition - Ning Mei; Fangxu Jia; Ying Liu; Yiran Li; Xin Qi; Baohong Han; Xu Zhang; Tao Liu; Hong Yao (Journal of Environmental Management, 2025)

Development of a rapid method for the determination of the spatial distribution of protein in wheat grain using mature resin section and image processing algorithm - Hengtong Wang; Haijiang Min; Minghao Gao; Han Zhong; Chuan Zhong; Zenan Ban; Qin Zhou; Xiao Wang; Jian Cai; Qing Li; Mei Huang; Dong Jiang; et al. (Journal of Cereal Science, 2025)

Spatiotemporal evolution patterns of mining-induced overburden damage based on microseismic event response analysis - Xiao Yang; Longqing Shi; Mei Qiu; Jin Han; Xingyue Qu; Song Fu (Journal of Applied Geophysics, 2025)

Protective effects of microalgal macular pigment on diabetic retinopathy upon blue light irradiation induced oxidative stress, inflammation, and MAPK pathways - Meng-Wei Lin; Cheng-Han Lin; Wei-Hong Chiu; Hui-Fang Chang; Wai-Man Cheang; Chien-Chun Chang; Vivian C.H. Wu; Chih-Sheng Lin; Chiu-Mei Kuo (Food Research International, 2025)

Assessing the human health risks from organophosphate esters: exposure assessment via wild freshwater fish consumption - Shuhui Wang; Ang Zhao; Bing Wang; Yifan Zhang; Qian Han; Emi Yang; Haode He; Chao Wei; Yuxia Yang; Jianzhong Xu; Mei Wang (Food Chemistry, 2025)

Toxic risk assessment of multi-endpoint toxicity and toxicity transformation mechanisms during UV-combined advanced treatments in wastewater treatment plants: Development of effect-based trigger values, in vitro bioassays, and FT-ICR MS analysis - Shuo Zhang; Kongrui Zhu; Kaifeng Rao; Yingnan Han; Jing-Long Han; Mei Ma; Aijie Wang; Jifang Zhang; Zhihang Yuan (Environmental Pollution, 2025)

MWCNT-OH/PDMS elastomer-based microwave absorber with high-performance thermal stability and mechanical sensing properties - Jialiang Chen; Kaixi Bi; Shuqi Han; Hao Liu; Wenjun He; Yifan Li; Guangchen Yin; Wenqi Xiong; Linyu Mei; Xiujian Chou (Chemical Engineering Journal, 2025)

Synergistic dual-Lewis sites in cobalt-doped Fe3S4 for enhanced hydrogen peroxide activation and contaminant degradation - Li-Ping Jin; Fan Zhou; Qin Liu; Su-Qin Wang; Meng-Meng Zeng; Xin-Yu Huang; Li Liu; Xiao-Han Yu; Mei-Feng Wu; Jian-Ping Zou (Chemical Engineering Journal, 2025)

Antimony-doped tin oxide/graphite composite counter electrode for hole transport layer-free printable mesoscopic perovskite solar cells with enhanced hole collection - Qiaojiao Gao; Kai Chen; Xiaoyu Li; Jiale Liu; Qian Yue; Yuan Shi; Junwei Xiang; Chuang Yang; Song Shen; Shichao Zhang; Siqi Jiang; Shijie Guan; et al. (Chemical Engineering Journal, 2025)

Response mechanisms of nitrogen-cycling microbiota and metabolic functions to nitrogen input in the Panax ginseng rhizosphere - Kexin Li; Mei Han; Mingming Wan; Limin Yang (Plant and Soil, 2025)

Harnessing Landscape Genomics to Evaluate Genomic Vulnerability and Future Climate Resilience in an East Asia Perennial - Li Feng; Cong‐Ying Wang; Li‐Pan Zhou; Yi‐Han Wang; Jing Wang; Zheng‐Yuan Wang; Tao Zhou; Xu‐Mei Wang (Molecular Ecology, 2025)
In this era of rapid climate change, understanding the adaptive potential of organisms is imperative for buffering biodiversity loss. Genomic forecasting provides invaluable insights into population vulnerability and adaptive potential under diverse climatic conditions, thereby facilitating management interventions and bolstering shaping species‐specific germplasm conservation strategies. We primarily employed landscape genomics approaches, leveraging single‐nucleotide polymorphisms obtained through whole‐genome resequencing of 201 individuals across 43 Rheum palmatum complex populations, to pinpoint adaptive variation and its significance in the context of future climates, delineate seed zones, and establish guidelines for ex situ germplasm conservation. The species complex exhibited strong signatures of local adaptation and differential genomic vulnerabilities across its distribution range, with eastern lineage populations facing significant maladaptation risks under future climate scenarios. Using diverse datasets of putatively adaptive loci and climate change scenarios, we delineated three distinct seed zones within the species' range, estimated varying sample sizes per zone to capture most adaptive diversity, and predicted shifts in seed zone centroids ranging from 48.3 to 359.3 km from historical distributions to mitigate climate change impacts. Collectively, our findings underscore the importance of integrating genomic and environmental data to forecast the adaptive trajectory of an East Asian perennial under anticipated climate changes, guide seed zone delineation for germplasm conservation and enhance population resilience. These results provide a blueprint for designing targeted conservation strategies and restoration plans in other imperilled species.

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

Study on the propagation processes and driving mechanisms of meteorological, hydrological, and agricultural droughts on the Mongolian Plateau - Li Mei; Han Aru; Siqin Tong; Yongfang Wang; Enliang Guo; Tianshu Zhang; Shan Yin; Yuhai Bao (Journal of Hydrology, 2025)

Determination of site-specific natural background values for soil potentially toxic elements supported by partial least squares regression method - Li-Mei Cai; Ao Wang; Song He; Yi-Meng Fan; Han-Hui Wen; Jie Luo; Lai-Guo Chen (Journal of Hazardous Materials, 2025)

Bioplastics (PC/GL) versus non-biodegradable plastics (PE/PP): Effects on growth and rhizosphere soil microbial-metabolomics of Houttuynia cordata - Mei Li; Beibei Zhao; Xiao Han; Jie Jiang; Chuanhuan Liu; Yingzhu Liu (Journal of Hazardous Materials, 2025)

Enhancing soil carbon sequestration capacity: Synergistic effect of low-release biochar and autotrophic microbial agents over one year - Han Tang; Jiajun Hu; Yundong Liu; Bu Li; Jia Wang; Wang Kai Tong; Mei Ru Yue; Jia Jie Zou; Min-tian Gao; Saiwei Zhang; Nan Liu; Jixiang Li (Journal of Environmental Chemical Engineering, 2025)

Dual-sulfur defects decorated 1T-WS2/Cd0.5Zn0.5S heterojunctions for boosted photocatalytic hydrogen evolution - Mei Dong; Wenjun Li; Liang Geng; Ruixue Huang; Hongli Han; Yuan Liu (Journal of Environmental Chemical Engineering, 2025)

Design and analysis of LNG cold energy utilization system combining hydrogen liquefaction and power output - Xu Zheng; Yan Li; Ji Zhang; Han Yuan; Ning Mei (International Journal of Refrigeration, 2025)

DPF-Net: Physical imaging model embedded data-driven underwater image enhancement - Han Mei; Kunqian Li; Shuaixin Liu; Chengzhi Ma; Qianli Jiang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Photo-induced aggregation of hole-transport material for enhancing photoelectrochemical performance in sensing ochratoxin - Han-Mei Deng; Ning Yang; Jie Xu; Xin-Ci Geng; Ya-Li Yuan; Ruo Yuan; Ya-Qin Chai (Chemical Engineering Journal, 2025)

Unlocking the power of sesquiterpenoids: phytochemistry and bioactivities in Artemisia (2017–2023) - Li Ping Tang; Tao Liu; Xiao Yu Han; Bin Li; Hong Dong Liu; Xue Mei Gao (Phytochemistry Reviews, 2025)

Single-Cell Sequencing Screening of Biomarkers Associated with Lipophagy in the MPTP Model Mice of Parkinson’s Disease - Mei-jun Liu; Jing-yi Zhu; Shi-yu Han; Si-jia Zhu; Dong-dong Yang (Molecular Neurobiology, 2025)

Isochrysis zhanjiangensis exhibits protective effects against metabolic abnormalities induced by high-fat diet in mice - Mei Wu; Yu Bai; Yanrong Li; Kang Chen; Jingyang Le; Jian Li; Chengxu Zhou; Spiros N. Agathos; Lin Zhang; Xiaojun Yan; Jichang Han (Marine Life Science & Technology, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Double special bodyguard: Selenium-enhanced loop-mediated isothermal amplification combined with CRISPR/Cas12a biosensing strategy - Keyi Long; Tiao Han; Wenxi Hu; Mei Yang; Danqun Huo; Zhen Huang; Changjun Hou (Analytica Chimica Acta, 2025)

Development of single nucleotide polymorphisms markers associated with disease resistance towards Pseudomonas koreensis in empurau (Tor tambroides) using T-Plex ARMS PCR assay - Melinda Mei Lin Lau; Hung Hui Chung; Cindy Jia Yung Kho; Han Ming Gan; Azham Zulkharnain (Aquaculture International, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Prenatal bisphenol analogues exposure, metabolites in breast milk and offspring anthropometric growth during infancy: The Wuhan twin birth cohort study - Hong Mei; Liqin Hu; Haoshuang Liu; Neng Li; Yunxia Li; Jiali Xu; Hailin Gu; Feiyan Xiang; Meng Yang; Pan Yang; Jianduan Zhang; Han Xiao; et al. (International Journal of Hygiene and Environmental Health, 2025)

Different benefit from clonal integration of stress signal between a stoloniferous alien invasive plant and its congeneric native one - Jie Deng; Jiao Tian; Cheng-Gang Qiu; Xue-Mei Wang; Jie Jiang; Han-Jun Yang; Yi Dan; Chang-Fan Chen; Su-Juan Duan; Jin-Song Chen (Flora, 2025)

Corrigendum to “Different benefit from clonal integration of stress signal between a stoloniferous alien invasive plantand its congeneric native one” [FLORA Volume 326, May 2025, 152724] - Jie Deng; Jiao Tian; Cheng-Gang Qiu; Xue-Mei Wang; Jie Jiang; Han-Jun Yang; Yi Dan; Chang-Fan Chen; Su-Juan Duan; Jin-Song Chen (Flora, 2025)

Transfer learning on lateral capacity prediction of monopile foundations with limited data - Mohammed Alduais; Qipei (Gavin) Mei; Amir Hosein Taherkhani; Fei Han (Computers and Geotechnics, 2025)

Architecting a spherical Bi12SiO20/Bi4O5I2/BiOBr double Z-scheme heterojunction for high-efficiency degradation of emerging pollutants - Xiya Xin; Pengfei Zhu; Mei Liu; Zhaoxin Huang; Han Lu (Chemical Engineering Journal, 2025)

Bioinspired slippery harp structures optimized by simulation for efficient fog harvesting - Xueqiu Zhou; Xikui Wang; Ningkang Luo; Han Wei; Hong Luo; Bingli Qin; Yi Mei; Zhengqiang Tang (Chemical Engineering Journal, 2025)

AgX-modified perovskite nanocrystalline glass: Boosting optical performance and stability for wide color gamut display applications - Enrou Mei; Ye He; Han Zhao; Ziyi Jiang; Xiaojuan Liang; Weidong Xiang (Chemical Engineering Journal, 2025)

Construction and optimization of low carbon-to-nitrogen ratio-adapted Chlorococcum-Bacteria symbiosis for energy-efficient wastewater remediation - Ru Yan; Han Ji; Zhuo-Chao Liu; Mei-Qi Ren; Shuai Wang; Li-Ming Yang; Dan Cui (Bioresource Technology, 2025)

AdaptiveGS: an explainable genomic selection framework based on adaptive stacking ensemble machine learning - Zhen Yang; Mei Song; Xianggeng Huang; Quanrui Rao; Shanghui Zhang; Zhongzheng Zhang; Chenyang Wang; Wenjia Li; Ran Qin; Chunhua Zhao; Yongzhen Wu; Han Sun; et al. (Theoretical and Applied Genetics, 2025)

Berberine dissociates mitochondrial complex I by SIRT3-dependent deacetylation of NDUFS1 to improve hepatocellular glucose and lipid metabolism - Xuekai Wang; Hu Li; Jianrui Li; Lei Lei; Jingchen Xu; Han Sun; Jiayu Li; Jing Jiang; Hongying Li; Mei Tang; Biao Dong; Yue Gong; et al. (Science China Life Sciences, 2025)

Microbe-mediated denitrification promotes nitrogen loss in mining soils contaminated with rare earth elements - Ying Luo; Duo Zhang; Ying Guo; Yong Guo; Tomoyasu Nishizawa; Ju-Mei Liu; Han-Gai Bai; Rina Su; Shao-Hua Zhang; Yu Qi; Ji Zhao; Zhihua Bao (Applied Soil Ecology, 2025)

TSeq-GAN: a generalized and robust blind source separation framework for AIS signals of unmanned surface vehicles - Jiansen Zhao; You Peng; Bing Han; Xiaojun Mei; Haoyu Li; Yue Liu (Frontiers in Marine Science, 2025)
Autonomous Identification System (AIS) enables unmanned surface vehicles (USVs) to sense their surrounding environment, enhancing safe navigation. However, AIS signals may collide in congested waterways, degrading sensing performance. Conventional statistical blind source separation (BSS) algorithms struggle to isolate signals lacking strictly non-Gaussian features in complex communication environments. Due to Gaussian filtering in AIS signal modulation, essential higher-order statistics are lost, often leading to low accuracy and instability with conventional methods. To this end, this paper develops a time sequence generative adversarial network (TSeq-GAN)-enabled BSS method. The proposed approach replaces an ordered training set with a randomly constructed AIS mixed signal matrix and incorporates a spatialtemporal feature extraction network paired with a generative adversarial framework to capture multidimensional signal characteristics and reconstruct the original signals. Furthermore, a global multi-objective optimization strategy is applied to the loss function to balance error minimization and signal quality. Under a 5 dB signal-to-noise ratio (SNR) and varying numbers of mixed signals, experimental results show that the method reduces mean squared error (MSE) by at least 9.84%, improves signal-to-interference ratio (SIR) by 10.03%, and increases continuous mutual information (cMI) by at least 4.11% compared to existing techniques, validating its robust and accurate extraction of AIS signals.

Membranal phosphatidylglycerol enhances oxygen diffusion and release from cyanobacteria - Jian-Lu Duan; Yi Han; Xiao-Yu Liu; Mei-Yan Liu; Yu-Chen Sun; Jing-Ya Ma; Xiao-Dong Sun; Yue Wang; Miao-Miao Tan; Bo Gong; Xian-Zheng Yuan (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Reduction in Serum Concentrations of Uremic Toxins Driven by Bifidobacterium Longum Subsp. Longum BL21 is Associated with Gut Microbiota Changes in a Rat Model of Chronic Kidney Disease - Yao Dong; Zhonghui Gai; Mei Han; Jiaqi Xu; Kang Zou (Probiotics and Antimicrobial Proteins, 2025)
Gut microbiota dysbiosis and consequent impairment of gut barrier function, culminating in elevated levels of uremic toxins, are prevalent in chronic kidney disease (CKD) patients. These toxins, notably indoxyl sulphate (IS), indole-3-acetic acid (IAA), and trimethylamine oxide (TMAO), are implicated in a spectrum of CKD-related complications, including cardiovascular disease, bone and mineral disorders, and inflammation. The specific impacts of various probiotics on these CKD manifestations remain unexplored. This study delved into the potential of dietary probiotic interventions, particularly Bifidobacterium longum subsp. longum BL21, to modulate gut microbiota and mitigate metabolic disorders in a CKD rat model. Over a six-week period, we administered a dietary regimen of BL21 and conducted comprehensive analyses, including serum uremic toxin quantification and 16S rRNA gene sequencing, to systematically profile gut microbial alterations at the phylogenetic level. Our findings reveal that BL21 intervention significantly ameliorated CKD-induced disruptions in gut microbial populations, enhancing both microbial richness and the relative abundance of key taxa. Importantly, BL21 appeared to exert its beneficial effects by modulating the abundance of crucial species such as Barnesiella and Helicobacter . Functionally, the intervention markedly normalized serum levels of IS, IAA, and TMAO, while potentially attenuating p-cresol sulphate (PCS) and p-cresol glucuronide (PCG) concentrations. Consequently, BL21 demonstrated efficacy in regulating gut microbiota and curtailing the accumulation of uremic toxins. Our results advocate for the utilization of BL21 as a dietary intervention to diminish serum uremic toxins and re-establish gut microbiota equilibrium at the phylogenetic level, underscoring the promise of probiotic strategies in the management of CKD.

A Robust Threshold Method of Mixed Layer Height Based on Lidar Turbulence Data Under Different Thermal Convection Conditions - Lu Wang; Fan He; Jinlong Yuan; Guohua Hu; Jian Mei; Shengliang Han; Lei Hong; Haiyun Xia (Boundary-Layer Meteorology, 2025)

Methyltrimethyltridecylchromans (MTTCs) in Mature Crude Oils: Implications for Oil Family Classification and Palaeoenvironmental Diagnosis - Youjun Tang; Mengyue Han; Xiaoyong Yang; Ke Liu; Lian Chen; Yahao Mei; Yulu Han; Tianwu Xu; Chengfu Zhang (Journal of Marine Science and Engineering, 2025)
Methyltrimethyltridecylchromans (MTTCs), a class of oxygen-containing aromatic derivatives, have been used as indicators of paleosalinity in source rocks and crude oils. However, the reliability of these compounds as indicators in mature organic matter remains unclear, hindering a definitive assessment of their significance for oil–oil or oil–source rock correlation. In this study, a suite of mature oils and associated source rocks from the Paleogene Shahejie (E2s) Formation in the Machang area, Dongpu Depression, Bohai Bay Basin, were analyzed. The distribution of bulk compositions and biomarkers in the oils and source rock extracts suggests a genetic relationship, indicating that the oils were derived from similar organic matter (predominantly algae and aquatic macrophytes) and depositional environments (low salinity), with comparable maturity levels (within the middle oil window). The β/γ-MTTC ratio, a proposed maturity indicator, appears unreliable in mature organic matter, as evidenced by its poor correlation with established maturity proxies (e.g., C29 24-ethylcholestanes αββ/(ααα + αββ)) in the studied samples. In contrast, MTTC-based salinity paraments (α/δ, α/γ, MTTCI, and the cross-plot of MTTCI versus Pr/Ph) consistently reflect a low-salinity depositional environment for these crude oils and source rocks, except in the ternary diagram of relative alkylation abundances. These findings suggest that MTTC-derived paleosalinity indicators may serve as effective tools for oil–oil or oil–source rock correlation within the middle oil window. This study provides evidence supporting the broader applicability of MTTC-based proxies for paleosalinity reconstruction and correlation studies, particularly in mature organic matter under geological conditions. The results also offer insights for regional petroleum exploration in saline lacustrine basins.

Spatiotemporal distribution and driving forces of ecological fragility in Chengde’s transitional region from plateau to plain, China - Mei Dong; Qingyu Zhang; Qingning Wang; Chunhao Jing; Han Luo (Environmental Monitoring and Assessment, 2025)

Pre-biodrying enhanced lignin degradation to promote aromatic macromolecular humic acid formation in double-phase composting - Jiefei Mo; Changxun Zhao; Chenxuan Fang; Yuzhou Long; Yujie Han; Qingqing Mei; Weixiang Wu (Waste Management, 2025)

Analytical solutions for determining the most unfavorable moment of shaking occurrence in underwater shaking table tests - Zhongxing Wang; Mei Liu; Mengyu Li; Hao Wu; Mingjie Liu; Xiang Yan; Qinghua Han (Soil Dynamics and Earthquake Engineering, 2025)

Ruthenium and nitrogen co-doped biochar for sulfamethoxazole degradation via peroxymonosulfate activation: Performance and mechanism - Lianghui Guo; Jiajun Xu; Dong Liu; Aoxiang Yin; Runyao Han; Guifan Gong; Shi Li; Zimeng Liu; Keke Zhi; Mei Wu (Process Safety and Environmental Protection, 2025)

Simultaneous high molecular weight PAHs degradation and chromate and arsenite detoxification by Altererythrobacter sp. H2 - Qun Han; Mei-Ling Yang; Ze-Shen Liu; Ying-Hao Zhao; Xue-Hui Liu; Guo-Min Ai; Wei-Hong Qin; Xing-Yu Liu; De-Feng Li (Journal of Hazardous Materials, 2025)

Mechanism of concentration and enrichment of citrus peel pectin driven by multi-chamber electrophoresis and low temperature - Zhanwei Yang; Jin Wang; Hanquan Liu; Mei Wang; Han Liao; Xianbiao Liu; Yuancong Zhang; Ting Liu; Lecheng Shen; Hecheng Meng; Shujuan Yu; Xiaobing Guo (Food Hydrocolloids, 2025)

Environmental and health impacts of reduced PM2.5 and trace metals from ship emissions under low-sulfur fuel oil policy in Shanghai, China - Xuyang Dong; Yan Zhang; Guangyuan Yu; Yuqi Xiong; Zimin Han; Juntao Huo; Cheng Huang; Haidong Kan; Mei Zheng; Zhi Ning; Bing Xie (Environmental Pollution, 2025)

Alkyl chain length engineering of zwitterionic sulfobetaine passivators for efficient printable mesoscopic perovskite solar cells - Xufeng Xiao; Kai Chen; Mi Qin; Xiaoyu Li; Ranjun Meng; Xiaoru Wang; Yang Zhou; Anyi Mei; Hongwei Han (Chemical Engineering Journal, 2025)

Degradation-Resistant Biochar Improves Soil Organic Carbon Storage: Promoting Autotrophic Metabolism & Increasing Refractory Organic Carbon - Han Tang; Jiajun Hu; Bu Li; Yundong Liu; Wang Kai Tong; Mei Ru Yue; Jia Wang; Wenjuan Wang; Min-tian Gao; Nan Liu; Jixiang Li (Bioresource Technology, 2025)

Improved method for estimating chlorine depletion in sea salt aerosols using single particle aerosol mass spectrometer - Youtian Zhang; Rongrong Han; Guanru Wu; Xinshuo Wang; Lei Li; Mei Li; Zhen Zhou; Jian Zhen Yu; Yang Zhou (Atmospheric Environment, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Genetic diversity assessment and disease resistance gene identification of Yunnan rice landraces - Mei Li; Rongping Li; Yunxiu Yang; Xiaoqiao Zhu; Huiling Zhang; Yun-Yue Wang; Ping He; Guangyu Han (European Journal of Plant Pathology, 2025)

Triaxial loading mechanical properties and differential failure mechanisms of damaged sandstone under pore water pressure changes - Xiang Fu; Han Su; Qiang Xie; Kuang Dong; Hao Mei; Yuxin Ban (Bulletin of Engineering Geology and the Environment, 2025)

Neural Networks and Chemical Messengers: Insights into Tobacco Addiction - Jieping Sun; Qingqing Lv; Jinghan Dang; Mengzhe Zhang; Qiuying Tao; Yimeng Kang; Longyao Ma; Bohui Mei; Weijian Wang; Shaoqiang Han; Jingliang Cheng; Yong Zhang (Brain Topography, 2025)

Metabolomic analysis of blood spots in a Chinese cohort with autism spectrum disorders: a pilot study - Hui Wang; Li Ding; Zheng-huan Mao; Yu Du; Qing-mei Han; Jia-yu Xu; Fei-fei Peng; Hai-feng Li; Chao-chun Zou (Metabolic Brain Disease, 2025)

The role of microalgae in Penaeus vannamei aquaculture: Exploring the importance of biofloc technology - Aihua Zhang; Han Shen; Xunzhi Zhang; Tao Wang; Fengxian Mei; Dhanushya Thilagam Jeyakumar; Fang Fang; Wensheng Qin; Zhiqiang Xu (Aquaculture, 2025)

Uppermost Permian to Lower Triassic conodont biostratigraphy and carbon isotope records from Southern Armenia - Chen Han; Shunling Wu; He Zhao; Zhengyi Lyu; Qiuyi Mei; Laishi Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Passivation mechanism driven selective leaching for recycling spent LiFePO4 lithium-ion batteries - Yurong Han; Menglong Yan; Yinzhuang Fang; Yifeng Han; Yi Chen; Liangyou Lin; Jingwen Qian; Tao Mei; Xianbao Wang (Journal of Environmental Chemical Engineering, 2025)

Surface and interface modification of biochar based on thermal nanobubble water - Mei Ru Yue; Jia Bing Liu; Piao Yi Jiang; Wang Kai Tong; Han Tang; Jia Wang; Wenjuan Wang; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Chemical Engineering, 2025)

In-situ hydrogen-mediated catalytic transfer hydrogenolysis of Kraft lignin for highly selective production of monomeric phenols - Han-Bing Gao; Bing-Hu Xie; Yue-Lun Wang; Le-Le Qiu; Yun-Peng Zhao; Jian Xiao; Mei Zhong; Jing Liang; Jian Li; Fang-Jing Liu; Jing-Pei Cao (Fuel, 2025)

Ecological benefits of integrating broadleaf tree species into Pinus massoniana monocultures and their impacts on soil fertility microbial diversity and network stability - Xiaomei Han; Izhar Ali; Saif Ullah; Yanling Zhang; Yuanyuan Xu; Mei Yang (Forest Ecology and Management, 2025)

A novel four-species microbial consortium for nutritional value improvement of rapeseed meal - Kunqiang Hong; Han Zhang; Mei Han; Xuejiao Nie; Xiaomeng Fu; Fenfen Lei; Dongping He (Food Chemistry, 2025)

Metatranscriptomics sheds light on electron transfer in anammox bacteria enhanced by the redox mediator neutral red - Xingcheng Zhao; Fangxu Jia; Bo Wang; ZhiFeng Hu; Baohong Han; Ning Mei; Feirui Jia; Yawen Liu; Hong Yao (Environmental Research, 2025)

Increased megafauna stranding risk from sand mining: Lessons from the Yangtze finless porpoise - Ruilong Wang; Qiyue Li; Jiaxian Ren; Yi Han; Xiaodong Sun; Yingen Dai; Yuyin Guo; Kexiong Wang; Ding Wang; Zhigang Mei (Biological Conservation, 2025)

Clinical characteristics and associated factors of macrolide-resistant mycoplasma pneumoniae pneumonia in children: a systematic review and meta-analysis - Shuo Yang; Xinying Liu; Yaowei Han; Huizhe Wang; Yunzheng Mei; Haokai Wang; Na Zhang; Yingying Peng; Xinmin Li (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Deciphering the effective substances of mangrove plant Acanthus ilicifolius Linn. against liver injury - Qing Zhao; Shu-Yue Song; Han Fang; Yao-Yao Zheng; Meng-Qi Zhang; Xia Ren; Ya-Hui Zhang; Xiu-Mei Fu; Xin Li; Chang-Yun Wang (Natural Product Research, 2025)

Permeability response and mechanism of anaerobic granular sludge under mixed salinity (NaCl and CaCl2) stress: Internal pore development and plugging - Zhuo Zeng; Mei-jie Zhou; Xue Yang; Tao Lei; Si Li; Hao Wen; Han Zhang (Journal of Water Process Engineering, 2025)

Engineering a thermophilic Bacillus thermoamylovorans for degradation of polyethylene terephthalate waste - Yi-Mei Cai; Cui-Can Lu; Tian-Tian Wang; Li-Jun Song; Yu-Ming Deng; Han Xu; Sheng Chen; Wei Xia; Jing Wu; Zheng-Fei Yan (Journal of Cleaner Production, 2025)

Thermal decomposition behavior of retired wind turbine blades: kinetics, pyrolysis product distribution and characterization - Mei Han; Yonghui Bai; Yuan Ma; Peng Lv; Xudong Song; Jiaofei Wang; Weiguang Su; Guangsuo Yu; Xuebin Wang (Journal of Environmental Management, 2025)

Rational design of alginate lyase ALYI1 for improving the antioxidant activity of the alginate oligosaccharides - Jin-Ping Huang; Jin-Xin Zhao; Ming-jing Zhang; Jiru Han; Ya-Tong Han; Xue-Ting Wang; Tian-Bao Wu; Jun-Nan He; Cai-Mei Chen; Yan-Xia Zhou (Food Chemistry, 2025)

Different benefit from clonal integration of stress signal between a stoloniferous alien invasive plantand its congeneric native one - Jie Deng; Jiao Tian; Cheng-Gang Qiu; Xue-Mei Wang; Jie Jiang; Han-Jun Yang; Yi Dan; Chang-Fan Chen; Su-Juan Duan; Jin-Song Chen (Flora, 2025)

Formaldehyde oxidation reaction enhanced by interface engineering of Cu/Cu2O/Co(OH)2 composite electrocatalyst for bipolar hydrogen production - Zi Qiang Ma; Chang Bao Han; Wen Kang Zhao; De Cai Fang; Yi Lin Zhao; Chang Xin Liu; Xinxin Wang; Ling Sun; Xue Mei Song (Chemical Engineering Journal, 2025)

Organic acid promoting the degradation of nonylphenol by persistent free radicals in biochar - Jie Ji; He Zhang; Feichao Zhang; Yao Wu; Han Zhang; Ziwei Mei; Wenxuan Zhou; Liang Li; Hong Tao; Meicheng Wen (Chemical Engineering Journal, 2025)

Interface selectivity-based biochar: Directional evolution of properties, application & carbon neutralization evaluation - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Mei Ru Yue; Yun Dong Liu; Bu Li; Jia Jie Zou; Jia Wang; Han Tang; Min-tian Gao; Yucang Liang; Wenjuan Wang; et al. (Chemical Engineering Journal, 2025)

Environmental fate of antibiotic resistance genes in livestock farming - Jiali Sun; Xiaoqi Wang; Yuanjie He; Mengting Han; Mei Li; Siyue Wang; Jia Chen; Qiang Zhang; Baowei Yang (Archives of Microbiology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Impacts of forest expansion on microbial diversity and community assembly in fragmented mountain ecosystems - Wen-Hui Lian; Wen-Sheng Zhao; Jia-Rui Han; Chao-Jian Hu; Guo-Yuan Shi; Fang Chen; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Mukhtiar Ali; Lei Dong; Ting Zhou; et al. (Environmental Research, 2025)

Synergy between aerated drip and biodegradable film enhances sustainable maize production in arid oasis - Yonghui Liang; Mei Wu; Jinzhu Zhang; Zhanli Ma; Yue Han; Yue Wen; Rui Chen; Jian Liu; Haiqiang Li; Zhenhua Wang (European Journal of Agronomy, 2025)

Theoretical analysis on absorption heat transformers boosted multi-effect distillation system for ocean thermal energy conversion - Suyun Yi; Zhixiang Zhang; Han Yuan; Yu Bai; Yongchao Sun; Wenyi Peng; Ning Mei; Yonggong Yuan; Tao Jiang (Desalination, 2025)

Molecular chelating and shielding operation for organic photoelectrochemical transistor detection of chlorpyrifos - Lang Lin; Yu-Mei Li; Rui Ban; De-Man Han; Feng-Zao Chen; Wei-Wei Zhao (Analytica Chimica Acta, 2025)

Vapor pressure deficit dominates dryness stress on forest biomass carbon in China under global warming - Yunfeng Cen; Mei Tang; Qingyuan Wang; Guanfang Sun; Zhiming Han; Yonghong Li; Zhaoliang Gao (Agricultural and Forest Meteorology, 2025)

Nitrification inhibitor induced microbial NH4+-N immobilization improves maize nitrogen use efficiency in strong ammonia oxidation soil - Si-Yi Liu; Di Wu; Xiao-Tang Ju; Ju-Pei Shen; Yi Cheng; Na Deng; Xiao-Tong Song; Hong-Jie Di; Pei-Pei Li; Li-li Han; An-Hui Ge; Chuan-Fa Wu; et al. (Soil Biology and Biochemistry, 2025)

Preparation and performance of novel GG/PVA/SA suppressant for coal dust control - Fangwei Han; Guirui Niu; Mei Liu; Fuhong Hu; Diandian Xue (Process Safety and Environmental Protection, 2025)

Semi-sacrificial fabrication of binder-free lithium-aluminum layered double hydroxides adsorbents for lithium extraction - Jinqiang Gao; Mei Hong; Jiatao Zhong; Shengnan Na; Yuqing Su; Han Li; Mingyu Hu; Shihe Yang (Desalination, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Flexible Ag/AgCl quasi-reference electrode with nano silver dendrites semi-embedded in PDMS: Ensuring long operation lifespan, remarkable stability for electrophysiological monitoring and flexible sensor applications - Jing Sun; Yalei Mei; Weiliang Bai; Li Han; Yuqiang Li; Yuzhong Gao; Ming-Fei Lang; Hongsheng Xue (Chemical Engineering Journal, 2025)

Efficient fog harvesting system inspired by cactus spine and spider silk with vertical crisscross spindle structure - Han Wei; Bingli Qin; Hong Luo; Xueqiu Zhou; Xikui Wang; Yi Mei (Chemical Engineering Journal, 2025)

Synthesis of furan-based cationic biopolyamides and their removal abilities for perfluoroalkyl and polyfluoroalkyl substances - Hong-Hui Shu; Liu-Qi Shi; Hui-Qin Zhang; Yun Liu; Sheng-Li Han; Jing-Yi Rao; Cheng-Mei Liu (Chemical Engineering Journal, 2025)

Remodeling of bacterial nitrilase active pocket improves the capability to degrade glucosinolate-derived nitriles - Ming-Yu Liu; Yu-Yue Wang; Han-Zhi Li; Xue-Mei Luo; Jia-Xun Feng; Shuai Zhao (World Journal of Microbiology and Biotechnology, 2025)

Vagus nerve stimulation (VNS) preventing postoperative cognitive dysfunction (POCD): two potential mechanisms in cognitive function - Zi-Feng Xie; Sheng-Yu Wang; Yuan Gao; Yi-Dan Zhang; Ya-Nan Han; Jin Huang; Mei-Na Gao; Chun-Guang Wang (Molecular and Cellular Biochemistry, 2025)

Cultivar shifts have offset climate warming impacts on soybean phenology in China since 1981 - Qinghang Mei; Zhao Zhang; Jichong Han; Jie Song; Fei Cheng; Huimin Zhuang; Huaqing Wu; Jialu Xu (Agricultural Systems, 2025)

Evaluations of two ion temperature models in IRI-2020 based on the observations from ICON and COSMIC-2 IVM - Tingwei Han; Huijun Le; Shun-Rong Zhang; Vladimir Truhlik; Natalie Reeves; Angkita Hazarika; Yujin Cho; Mei-Yu Chen; Libo Liu; Yiding Chen; Ruilong Zhang (Advances in Space Research, 2025)

Novel Polarization Construction Method and Synchronization Algorithm for Underwater Acoustic Channel Under T-Distribution Noise Environment - Jiangfeng Xian; Zhisheng Li; Huafeng Wu; Weijun Wang; Xinqiang Chen; Xiaojun Mei; Yuanyuan Zhang; Bing Han; Junling Ma (Journal of Marine Science and Engineering, 2025)
Underwater acoustic channel (UWAC) is characterized by significant multipath effects, strong time-varying properties and complex noise environments, which make achieving high-rate and reliable underwater communication a formidable task. To address the above adverse challenges, this study first presents a novel, robust and efficient polar code construction (NREPCC) method using the base-adversarial polarization weight (BPW) algorithm tailored for typical ocean channel models, including invariable sound velocity gradient (ISVG) channels, negative sound velocity gradient (NSVG) channels, and positive sound velocity gradient (PSVG) channels. Subsequently, a robust and reliable polar-coded UWAC system model based on the orthogonal frequency division multiplexing (OFDM) technique is designed using the t-distribution noise model in conjunction with real sea noise data fitting. Then, an enhanced time synchronization and packet detection algorithm based on t-distribution is proposed for the performance optimization of the polar-coded UWAC OFDM system. Finally, extensive numerical simulation results confirm the excellent performance of the proposed NREPCC method and polar-coded UWAC OFDM system under a variety of channel conditions. Specifically, the NREPCC method outperforms low-density parity-check (LDPC) codes by approximately 0.5~1 dB in PSVG and ISVG channels while maintaining lower encoding and decoding complexity. Moreover, the robustness of the NREPCC method under t-distribution noise with varying degrees of freedom is rigorously validated, which renders vital technical support for the design of high-precision and high-robustness UWAC systems.

Promoted metabolic remolding by overexpression of AspAT9 ameliorates cadmium toxicity in Arabidopsis - Mei Han; Junhu Feng; Yujie Zhai; Yujia Si; Xiaoning Liu; Yirong Han; Jinghan Hu; Tao Su; Fuliang Cao (Journal of Hazardous Materials, 2025)

Intelligent sensing platform based on europium-doped carbon dots for dual-functional detection of ciprofloxacin/Ga3+ and its tracking in vivo - Le Liang; Su-qian Cai; Yan-li Leng; Chan Huang; Yong-qing Liu; Ye Wang; Li Luo; Mei Han; Xiao-hong Li; Xiao-hua Cai (Journal of Hazardous Materials, 2025)

Biosurfactants are green and versatile enhancers for sustainable treatment of oily sludge: A review - Feng Zhao; Qingfeng Cui; Han Su; Chunyan Li; Mei Dong (Journal of Environmental Chemical Engineering, 2025)

Genomic characteristics and virulence of common but overlooked Yersinia intermedia, Y. frederiksenii, and Y. kristensenii in food - Zexun Lü; Li Su; Mengting Han; Xiaoqi Wang; Mei Li; Siyue Wang; Shenghui Cui; Jia Chen; Baowei Yang (International Journal of Food Microbiology, 2025)

Recent advances in cold plasma technology for enhancing the safety and quality of meat and meat products: A comprehensive review - Changyan Zhang; Yulong Luo; Ziyao Deng; Rui Du; Mei Han; Junqin Wu; Wenxiu Zhao; Rong Guo; Yanru Hou; Songlei Wang (Food Research International, 2025)

Understanding the anti-browning mechanism and physicochemical properties in potato pulp during the magnetic field processing - Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Xin Zhang; Chuangshuo Yan; Yujian Xie; Dongliang Zhang; Hongjun Li (Food Chemistry, 2025)

Exploring the influence of extruded rice adjunct on wort separation efficiency: A bio-macromolecule degradation perspective - Lijun Jiang; Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Dongliang Zhang; Shifeng Yu; Hongjun Li (Food Chemistry, 2025)

Self-assembled preparation of wheat germ gliadin and (−)-epigallo-catechin 3-gallate nanoparticles: Structural characterization, formation mechanism and bioactivity - Zhi-Tong Zhu; Zhi-Rui Ding; Yu-Qing Liu; Ying Zhang; Jian-Zheng Li; Si-Yi Han; Xian-Ming Liu; Ming Hui; Na Liu; Ai-Mei Liao (Food Bioscience, 2025)

Construction of a self-priming hairpin probe for rapid and isothermally one-step detection of multiple long noncoding RNAs in living cells and tissues - Xiao-wen Liu; Yun Han; Shu-hua Wei; Bao-mei Zhou; Xiaoran Zou; Chun-yang Zhang (Chemical Engineering Journal, 2025)

All-solid-state wire-shaped micro-supercapacitors: A microfluidic approach to core-shell structured bacterial cellulose-GN/PPy fibers - Yue Jiao; Yao Wang; Huining Xiao; Jian Li; Changtong Mei; Qiliang Fu; Jingquan Han (Carbohydrate Polymers, 2025)

Deciphering the landscape and evolutionary trajectory of NLR immune receptors in Dioscorea alata - Yue Wang; Xing-Yu Feng; Wen-Qiang Wu; Ming-Han Li; Sai-Xi Li; Zhen Zeng; Zhu-Qing Shao; Yan-Mei Zhang (Plant Molecular Biology, 2025)

Dorsal CA1 NECTIN3 Reduction Mediates Early-Life Stress-Induced Object Recognition Memory Deficits in Adolescent Female Mice - Yu-Nu Ma; Chen-Chen Zhang; Ya-Xin Sun; Xiao Liu; Xue-Xin Li; Han Wang; Ting Wang; Xiao-Dong Wang; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2025)

Food consumption away from home had divergent impacts on diet nutrition quality across urban and rural China - Huaqing Wu; Zhao Zhang; Jialu Xu; Jie Song; Jichong Han; Jing Zhang; Qinghang Mei; Fei Cheng; Huimin Zhuang; Shaokun Li (Food Security, 2025)

Medium modification of Cynanchum wilfordii adventitious root culture for the production of C21 steroidal glycosides, polysaccharides, and polypeptides using orthogonal design methods - Han-Xi Li; Yu-Qing Guo; Wei-Qi Ye; Zhong-Yu Zhou; Ling-Hong Bai; Xuan-Chun Piao; Mei-Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2025)

Migratory life cycle of Anguilla anguilla : a mirror symmetry with A. japonica - Hsiang‐Yi Hsu; Kuan‐Mei Hsiung; Yu‐San Han (Journal of Fish Biology, 2025)
The European and Japanese eel populations have declined significantly in recent decades. To effectively manage and conserve them, gaining a better understanding of their migratory life cycles is important. Previous research on the spawning ecology and larval dispersal of European and Japanese eels has led to many significant discoveries and advancements for their migratory life cycles. However, different scholars hold varying views on their migratory life cycles, especially concerning the European eel, therefore this article aims to provide a comprehensive review of research from multiple disciplines concerning the spawning ecology and larval dispersal of European and Japanese eels and to propose migratory life cycles of these two species. The migratory life cycle of the European eel is as follows: European silver eels undertake a year‐long spawning migration from September to January to reach the Sargasso Sea for spawning before the next spawning season, typically between December and May. After hatching, European eel leptocephali are transported by the Gulf Stream, Frontal Countercurrents, North Atlantic Current, and Azores Current and return to Europe and North Africa for growth. Recruitment of European glass eels mainly occurs between October and June of the following year, and the recruiting season is more concentrated in countries closer to the spawning area and more dispersed in countries farther away. The consistent recruitment pattern and the growth rate of leptocephali suggest a larval transport period, also called larval duration, of around 1 year. Understanding the migratory life cycle of European eels can facilitate the evaluation or development of their conservation measures.

A new isoflavone from the stems of Derris eriocarpa How - Ying Liu; Zhen-Xin Zhu; Yue Lu; Cong Wang; Hong-Cun Liu; Juan Meng; Jin Qi; Xiao-Ning Huang; Xiao-Mei Lu; Wen-Sen Lu; Shu-Han Luo; Hai-Na Liang; et al. (Natural Product Research, 2025)

Magnetic field inhibited the deterioration of frozen dough via promoting the interaction between starch and gluten - Ting-Shi He; Han Tao; Mei Liu (Journal of Cereal Science, 2025)

High UV-shielding polyvinyl alcohol/chitosan-based transparent bioplastic film for food preservation - Mei Bao; Honglei Mu; Ben Niu; Ruiling Liu; Huizhi Chen; Hangjun Chen; Lishu Wang; Yanchao Han; Guannan Wang; Haiyan Gao (Food Packaging and Shelf Life, 2025)

Bioinspired 1D structures for water harvesting: Theory, design and application - Xikui Wang; Hong Luo; Ningkang Luo; Han Wei; Xueqiu Zhou; Bingli Qin; Yi Mei; Moyuan Cao; Youfa Zhang (Chemical Engineering Journal, 2025)

Flexible disk ultramicroelectrode: Facile preparation and high-resolution scanning electrochemical microscopy imaging - Xinfang Zhang; Xuanhao Mei; JinPeng Bao; Ping Song; Haiyan Lu; Ce Han; Weilin Xu (Analytica Chimica Acta, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Sponge-based FeS activated persulfate coupled with biodegradation for highly efficient removal of tetracycline: Batch and column validation - Shou Mei; Mengyao Han; Jintao Hao; Yuxuan Ye; Yuwei Deng; Luxin Liang; Ziyi Zhan; Rongling Wang; Xuanyuan Pei; Qiang Li; Zhenbin Wu; Fei Pan (Journal of Water Process Engineering, 2024)

Artemisia argyi leaf powder improves soil properties and recruits Sphingobium bacteria to promote the growth and yield of Pinellia ternata - Jinxin Li; Kaili Qu; Lu Wei; Hong Chen; Huixia Cai; Jingyi Zhang; Likun Mei; Bingsen Liu; Yifan Han; Yuhuan Miao; Dahui Liu (Journal of Environmental Management, 2024)

Particle size is an important factor influencing the effects of biochar return to woodland soils: An evaluation from the perspective of sapling growth and soil microbial carbon processes - Xiaoyu Gao; Haoting Liu; Wenxuan Mei; Wenwen Zhang; Haoyu Dong; Xiaohua Fu; Mengdi Xie; Yujie Han; Lei Wang (Journal of Environmental Management, 2024)

Performance analysis and multi-objective optimization for an integrated air separation, power generation, refrigeration and ice thermal storage system based on the LNG cold energy utilization - Xu Zheng; Ji Zhang; Yan Li; Zhihao Zhang; Jikai Lu; Ning Mei; Zhixiang Zhang; Han Yuan (International Journal of Refrigeration, 2024)

Disease risk of the foliar endophyte Colletotrichum from invasive Ageratina adenophora to native plants and crops - Ai-Ling Yang; Yi-Shan Chen; Liang Mei; Jing Guo; Han-Bo Zhang (Fungal Ecology, 2024)

A comprehensive approach for quantifying source-specific ecological and health risks of potentially toxic elements in agricultural soil - Li-Mei Cai; Ke Quan; Han-Hui Wen; Jie Luo; Shuo Wang; Lai-Guo Chen; He Song; Ao Wang (Environmental Research, 2024)

Partitioned granular sludge coupling with membrane-aerated biofilm reactor for efficient autotrophic nitrogen removal - Ning Mei; Fangxu Jia; Hui Wang; Zhifeng Hu; Baohong Han; Yao Chen; Xingcheng Zhao; Xiangyu Han; Jingjing Zhang; Dongmei Li; Hong Yao; Jianhua Guo (Bioresource Technology, 2024)

Soy whey and brewer’s spent grain hydrolysates wholly replace conventional medium for microalgae growth: Process performance and economic considerations - Mei Zhi Alcine Chan; Vivian Jing Han Hau; Byron Perez; Iris Haberkorn; Alexander Mathys; Shao-Quan Liu (Bioresource Technology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

A novel variant (p.A524P) in Spastin is responsible for a Chinese family with hereditary spastic paraplegia - Yu-Han Jin; Yang-Ziyu Xiang; Mei-Fang Zhao; Yi-Hui Liu; Liang-Liang Fan; Xiao-Cong Li (Molecular Biology Reports, 2024)

Peroxiredoxin II exerts neuroprotective effects by inhibiting endoplasmic reticulum stress and oxidative stress-induced neuronal pyroptosis - Mei-Hua Jin; Xiao-Dong Liu; Hu-Nan Sun; Ying-Hao Han; Taeho Kwon (Molecular Biology Reports, 2024)

Influence of Selenium Supplementation on Mercury Levels in hair of Metropolitan Residents in China: Spatial Distribution, Impact Factors, and Antagonism - Geting Wang; Qianqian Hong; Jian Mei; Jinyi Chen; Wansheng Wu; Feng Han; Jingchen Xing; Shijian Yang (Exposure and Health, 2024)

Stagnating rice yields in China need to be overcome by cultivars and management improvements - Huimin Zhuang; Zhao Zhang; Jichong Han; Fei Cheng; Shaokun Li; Huaqing Wu; Qinghang Mei; Jie Song; Xinyu Wu; Zongliang Zhang; Jialu Xu (Agricultural Systems, 2024)

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

Spatial variability, source identification, and partitioning of groundwater constituents in a typical lakeside plain on Yungui Plateau - Wenxu Hu; Yong Xiao; Liwei Wang; Yuqing Zhang; Mei Feng; Wenchao Shi; Chunyan He; Yadan Wen; Hongjie Yang; Jibin Han; Jie Wang (Process Safety and Environmental Protection, 2024)

Crystallization behavior of BOF slag during the cooling process towards leaching for CO2 sequestration - Xiaohui Mei; Qing Zhao; Chengzhi Han; Zengrui Wang; Yi Min; Chengjun Liu; Henrik Saxén; Ron Zevenhoven (Process Safety and Environmental Protection, 2024)

Enhanced removal of quinoline and nitrate in synthetic photovoltaic wastewater by non-aerating algae-bacteria symbiosis system: Microbial environmental response and nitrogen metabolism - Zipeng Yan; Mengqi Zheng; Yan Wang; Hao Shen; Yaqi Liu; Jie Wang; Hong Mei; Yuying Du; Yantao Zhou; Kuizu Su; Hongjun Han (Journal of Water Process Engineering, 2024)

Biodiversity-safeguarding threshold for urea-fertilizer application on paddy fields: Protozoa-based toxicity tests - Chunyu Hou; Kexin Yu; Tianyi Shi; Benchao Jiang; Liangzi Cao; Wenyuan Wang; Mei Han; Jing Tang; Yuting Zhao; Xuming Pan; Jianye Li; Duu-Jong Lee; et al. (Journal of Environmental Management, 2024)

Impacts of shifting from single-species pine forests to distinct agroforestry models on soil fertility, exchangeable cations, and microbial functions - Saif Ullah; Xiaomei Han; Rongyan Deng; Izhar Ali; Wannian Li; Yuanyuan Xu; Mei Yang (Journal of Environmental Management, 2024)

Effect of wheat flour particle size on the quality deterioration of quick-frozen dumpling wrappers during freeze-thawed cycles - Lulu Yin; Xinyue Wu; Guolan Qin; Jiajing Han; Mei Liu; Yangkun Wei; Ying Liang; Jin Zhang; Shenying Zhang; Haojia Zhu; Ying Huang; Xueling Zheng; et al. (Food Research International, 2024)

Green massive mechanical synthesis of highly efficient Zn-Doped Cs3Cu2I5 for LED and X-ray imaging applications - Qi-Hua Yang; Gui-Hua Li; Yu-Chen Ao; Shu-Juan Zhao; Han-Qi Wei; Le Fu; Zhi-Wei Luo; Tian-Liang Zhou; Chu-Jie Wang; Ge-Mei Cai (Chemical Engineering Journal, 2024)

Homogeneous crystallization of MA-free, wide-bandgap perovskite films via self-assembled monolayer capping for laminated silicon/perovskite tandem solar cells - Weidong Zhu; Mei Yang; Tianjiao Han; Yiru Wang; Xin Luo; Wenming Chai; He Xi; Long Zhou; Dazheng Chen; Jincheng Zhang; Chunfu Zhang; Yue Hao (Chemical Engineering Journal, 2024)

Improving the removal rate of bisphenol A and Cu2+ from water using P/N coexisting β-cyclodextrin-based adsorbents by enhancing adsorbents-pollutants interactions - Xiuqin Fang; Chang Wang; Hong-Hui Shu; Sheng-Li Han; Cheng-Mei Liu (Carbohydrate Polymers, 2024)

Short-term usage of proton pump inhibitors during admission was associated with increased risk of rehospitalization in critically ill patients with myocardial infarction: a cohort study - Jia-De Zhu; Li-Juan Yang; Jian-Nan Zhao; Ping Wang; Yi-Hua Li; Xue-Sha Zhang; Jian-Mei Pan; Meng-Han Jiang; Hai-Ying Yang; Sun-Jun Yin; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Agricultural management reshaped the diversity patterns and community assembly of rhizosphere bacterial communities in a desert farming system - Wen-Hui Lian; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Zhi-Liang Lin; Chao-Jian Hu; Jia-Rui Han; Wen-Jun Li; Lei Dong (Applied Soil Ecology, 2024)

Vortex-Induced Vibration Performance Analysis of Long-Span Sea-Crossing Bridges Using Unsupervised Clustering - Tao Chen; Yi-Lun Wu; Xiao-Mei Yang; Shu-Han Yang (Journal of Marine Science and Engineering, 2024)
Vortex-induced vibration is a type of wind-induced vibration occurring frequently in large-span sea-crossing bridges under relatively low wind speeds, posing a threat to the structural fatigue performance and driving comfort. Identifying the instantaneous occurrence moments of vortex-induced vibration is a prerequisite for establishing a data-driven prediction model for vortex-induced vibration, and it is of great significance for the monitoring and early warning of vortex-induced vibration performance in bridges. To automatically detect the occurrence moments of vortex-induced vibration and establish a correlation model between vortex-induced vibration amplitude and environmental factors, this study proposes a fuzzy C-means clustering-based classification method. In order to detect the occurrence moments of vortex-induced vibration more finely, only short-term or even instantaneous structural vibration indicators were selected and transformed for distribution as clustering features. The entire detection process could be carried out unsupervised, reducing the manual cost of obtaining vortex-induced vibration information from massive monitoring data. Finally, actual vortex-induced vibration test data from a certain overseas bridge was utilized to verify the feasibility of this method. Based on the classification results, the correlation between vortex-induced vibration amplitude and environmental variables was determined, providing valuable guidance for predicting vortex-induced vibration amplitudes.

Deciphering the effects of different types of high-temperature Daqu on the fermentation process and flavor profiles of sauce-flavor Baijiu - Wei Shi; Li-Juan Chai; Han Zhao; Ya-Ning Song; Jun-Lan Mei; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Bo Yang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Bioscience, 2024)

Species-level understanding of the bacterial community in Daqu based on full-length 16S rRNA gene sequences - Pei-Jie Han; Liang Song; Zhang Wen; Hai-Yan Zhu; Yu-Hua Wei; Jian-Wei Wang; Mei Bai; Lu-Jun Luo; Ju-Wei Wang; Shen-Xi Chen; Xiao-Long You; Da-Yong Han; et al. (Food Microbiology, 2024)

Harnessing donor cyclization strategy: Converting type II to type I photosensitizers and enhancing AIE performance for NIR-II FL/MR imaging-guided photodynamic therapy under hypoxia condition - Chonglu Li; Jie Li; Yida Pang; Longcan Mei; Wenhan Xu; Zhipeng Zhang; Cuipin Han; Yao Sun (Chemical Engineering Journal, 2024)

A novel pH-responsive multi-component nanodelivery system with siRNA for plant disease management - Chengying Ding; Yubing Jiao; Ying Li; Lili Shen; Wanhong Zhang; Haohua Ma; Lu Han; Zongjin Zhang; Fangfang Yan; Yunpeng Mei; Robert YL Wang; Jinguang Yang (Chemical Engineering Journal, 2024)

Chemical constituents from Elephantopus scaber L. and their chemotaxonomic significant - Ze-Ming Wu; Mei-Ya Lian; Xiao-Yu Han; Ming Bai; Shao-Jiang Song (Biochemical Systematics and Ecology, 2024)

Chemical constituents from Ficus tikoua and chemotaxonomic significance - Han-Lei Wang; Jing Lu; Xue-Lin Chen; Ru Li; Kun Zhang; Yu-Ling Guo; Xia Zhao; Yu-Mei Zhang (Biochemical Systematics and Ecology, 2024)

Construction of artificial microbial consortia for efficient degradation of chicken feathers and optimization of degradation conditions - Wencai Xia; Mei Jin; Xin Li; Chunbo Dong; Yanfeng Han (World Journal of Microbiology and Biotechnology, 2024)

Effects of 6-methoxybenzoxazolinone (6-MBOA) on animals: state of knowledge and open questions - Jia-Yi Shi; Ke-Han Gu; Sheng-Mei Yang; Wan-Hong Wei; Xin Dai (The Science of Nature, 2024)

Nanoplastics enhanced the developmental toxicity of aromatic disinfection byproducts to a marine polychaete at non-feeding early life stage - Yun Yang; Xiangru Zhang; Jiarui Han; Wanxin Li; Xinyi Chang; Yuhe He; Kenneth Mei Yee Leung (Chemosphere, 2024)

Effects of melatonin on sperm quality, enzyme activity, antioxidant gene expression and fertility of cryopreserved bovine semen - Peng Niu; Fei Huang; Jie Wang; Jia-jia Suo; Jie-ru Wang; Di Fang; Chun-mei Han; Qing-hua Gao (Theriogenology, 2024)

Effects of polysaccharides on colonic targeting and colonic fermentation of ovalbumin-ferulic acid based emulsion - Hesheng Liu; Zhenzhen Huang; Ting Xin; Lihong Dong; Mei Deng; Lipeng Han; Fei Huang; Dongxiao Su (Food Chemistry, 2024)

Continuous alkylation of 1,3,5-trihydroxy-2,4,6-trinitrobenzene in microreactor: Process intensification and reaction kinetics - Xuan Liu; Lixia Yang; Rao Chen; Mei Han; Chaoqun Yao; Guangwen Chen (Chemical Engineering Journal, 2024)

The mechanism of interaction between tri-para-cresyl phosphate and human serum protein: A multispectroscopic and in-silico study - Shang-Chun Li; Han Xu; Peng-Fei Wang; Li-Mei Wang; Yue-Rou Du; Yong-Bin Guan; Zhi-Xia Han; Qing-Bi Zhang (Chemico-Biological Interactions, 2024)

Phenolic Acid Concentration and Adsorption in the Soil of Monoculture Eucalyptus and Acacia Mangium Plantations Versus Species Mixtures in Subtropical Forests - Saif Ullah; Chengrui Liao; Yuanyuan Xu; Wannian Li; Izhar Ali; Xiaomei Han; Shaoming Ye; Mei Yang (Journal of Soil Science and Plant Nutrition, 2024)

Co-infection of H9N2 subtype avian influenza virus and QX genotype live attenuated infectious bronchitis virus increase the pathogenicity in SPF chickens - Qinghua Huang; Xiao Yang; Xiaoran Zhao; Xiaoxia Han; Shouli Sun; Chuantian Xu; Ning Cui; Mei Lu (Veterinary Microbiology, 2024)

Serum deprivation protein response intervenes in the proliferation, motility, and extracellular matrix production in keloid fibroblasts by blocking the amplification of TGF-β1/SMAD signal cascade via ERK1/2 - Peilong Li; Mei Han; Liaoyi Wang; Cong Gao (Toxicology and Applied Pharmacology, 2024)

Enhanced treatment of pyridine wastewater by a hybrid membrane biofilm reactor: Simultaneous biodegradation of pyridine and removal of nitrogen - Jingyi Zhang; Yawei Tian; Zhan Wang; Mengmeng Yang; Yong Wang; Han Gao; Zimiao Zhang; Yutong Han; Yanyan Xiao; Xu Yang; Xuanwei Zhao; Yue Wu; et al. (Process Safety and Environmental Protection, 2024)

Cement-based external wall insulation material with thermal performance improvement by partial substitution of calcium silicate - Wen Rui Ren; Cheng Hai Wang; Chang Bao Han; Dong Han; Jia Yu Zheng; Ya Nan Cui; Xue Mei Song; Quan Jiang; Hui Yan (Energy and Buildings, 2024)

Conformational transformation of activator strand directly regulates CRISPR/Cas12a system activity for live cell sensing of multiple biomolecules - Qing-Nan Li; Dong-Xia Wang; Zhi-Qi Dai; Shun-Li Wu; Gui-Mei Han; Sha Lu; Li-Na Zhu; Hong-Xin Jiang; De-Ming Kong (Chemical Engineering Journal, 2024)

Effects of different reclaimed mine land use patterns on the soil properties and water infiltration of opencast coal mines in the northern Loess Plateau, China - Jian Hu; Shilei Zhu; Kaiqi Yang; Yunzhuo Ren; Zhiao Zhang; Mei Tang; Fengpeng Han; Qing Zhen (CATENA, 2024)

A leaf age‐dependent light use efficiency model for remote sensing the gross primary productivity seasonality over pantropical evergreen broadleaved forests - Jie Tian; Xueqin Yang; Wenping Yuan; Shangrong Lin; Liusheng Han; Yi Zheng; Xiaosheng Xia; Liyang Liu; Mei Wang; Wei Zheng; Lei Fan; Kai Yan; et al. (Global Change Biology, 2024)
Tropical and subtropical evergreen broadleaved forests (TEFs) contribute more than one‐third of terrestrial gross primary productivity (GPP). However, the continental‐scale leaf phenology‐photosynthesis nexus over TEFs is still poorly understood to date. This knowledge gap hinders most light use efficiency (LUE) models from accurately simulating the GPP seasonality in TEFs. Leaf age is the crucial plant trait to link the dynamics of leaf phenology with GPP seasonality. Thus, here we incorporated the seasonal leaf area index of different leaf age cohorts into a widely used LUE model (i.e., EC‐LUE) and proposed a novel leaf age‐dependent LUE model (denoted as LA‐LUE model). At the site level, the LA‐LUE model (average R 2 = .59, average root‐mean‐square error [RMSE] = 1.23 gC m −2 day −1 ) performs better than the EC‐LUE model in simulating the GPP seasonality across the nine TEFs sites (average R 2 = .18; average RMSE = 1.87 gC m −2 day −1 ). At the continental scale, the monthly GPP estimates from the LA‐LUE model are consistent with FLUXCOM GPP data ( R 2 = .80; average RMSE = 1.74 gC m −2 day −1 ), and satellite‐based GPP data retrieved from the global Orbiting Carbon Observatory‐2 (OCO‐2) based solar‐induced chlorophyll fluorescence (SIF) product (GOSIF) ( R 2 = .64; average RMSE = 1.90 gC m −2 day −1 ) and the reconstructed TROPOspheric Monitoring Instrument SIF dataset using machine learning algorithms (RTSIF) ( R 2 = .78; average RMSE = 1.88 gC m −2 day −1 ). Typically, the estimated monthly GPP not only successfully represents the unimodal GPP seasonality near the Tropics of Cancer and Capricorn, but also captures well the bimodal GPP seasonality near the Equator. Overall, this study for the first time integrates the leaf age information into the satellite‐based LUE model and provides a feasible implementation for mapping the continental‐scale GPP seasonality over the entire TEFs.

PbARF19-mediated auxin signaling regulates lignification in pear fruit stone cells - Yanling Wang; Qi Wang; Fanhang Zhang; Chenyang Han; Wen Li; Mei Ren; Yueyang Wang; Kaijie Qi; Zhihua Xie; Shaoling Zhang; Shutian Tao (Plant Science, 2024)

Structurally diverse isoquinoline alkaloids from the barks of Alangium salviifolium (L. f.) Wangerin and their cytotoxicity - Yan-Mei Wei; Xuan Zhang; Fu-Ling Cen; Yi-Yi Du; Yuan-Ling Liu; Qiao-Yuan Han; Zhang-Xin Yu; Guang-Ying Chen (Phytochemistry, 2024)

Nanocellulose-mediated bilayer hydrogel actuators with thermo-responsive, shape memory and self-sensing performances - Yuanyuan Ma; Ya Lu; Yiying Yue; Shuijian He; Shaohua Jiang; Changtong Mei; Xinwu Xu; Qinglin Wu; Huining Xiao; Jingquan Han (Carbohydrate Polymers, 2024)

Enhanced Target Localization in the Internet of Underwater Things through Quantum-Behaved Metaheuristic Optimization with Multi-Strategy Integration - Xiaojun Mei; Fahui Miao; Weijun Wang; Huafeng Wu; Bing Han; Zhongdai Wu; Xinqiang Chen; Jiangfeng Xian; Yuanyuan Zhang; Yining Zang (Journal of Marine Science and Engineering, 2024)
Underwater localization is considered a critical technique in the Internet of Underwater Things (IoUTs). However, acquiring accurate location information is challenging due to the heterogeneous underwater environment and the hostile propagation of acoustic signals, especially when using received signal strength (RSS)-based techniques. Additionally, most current solutions rely on strict mathematical expressions, which limits their effectiveness in certain scenarios. To address these challenges, this study develops a quantum-behaved meta-heuristic algorithm, called quantum enhanced Harris hawks optimization (QEHHO), to solve the localization problem without requiring strict mathematical assumptions. The algorithm builds on the original Harris hawks optimization (HHO) by integrating four strategies into various phases to avoid local minima. The initiation phase incorporates good point set theory and quantum computing to enhance the population quality, while a random nonlinear technique is introduced in the transition phase to expand the exploration region in the early stages. A correction mechanism and exploration enhancement combining the slime mold algorithm (SMA) and quasi-oppositional learning (QOL) are further developed to find an optimal solution. Furthermore, the RSS-based Cramér–Raolower bound (CRLB) is derived to evaluate the effectiveness of QEHHO. Simulation results demonstrate the superior performance of QEHHO under various conditions compared to other state-of-the-art closed-form-expression- and meta-heuristic-based solutions.

Produce low-CO2 silica fume hybrid high-strength concrete using dry ice (solid CO2) as a CO2-utilized admixture - Mei-Yu Xuan; Run-Sheng Lin; Yi Han; Gui-yu Zhang; Cheng Guo; Xiao-Yong Wang (Journal of Cleaner Production, 2024)

A novel membrane-aerated biofilm reactor using flexible and adjustable plate membrane modules: Treatment of wastewater containing anionic surfactants - Mengmeng Yang; Cai Wang; Zimiao Zhang; Zhan Wang; Lijie Xu; Yong Wang; Han Gao; Chenxue Jiang; Yutong Han; Yanyan Xiao; Xu Yang; Yang Liu; et al. (Journal of Environmental Chemical Engineering, 2024)

Linear and nonlinear rheological characterization of capillary protein oleogels as potential fat replacers: Comparison with high internal-phase emulsions - Gao-Shang Wang; Qing Li; Guang-Xin Feng; Chuan-Wu Han; Jian Guo; Jin-Mei Wang; Zhi-Li Wan; Xiao-Quan Yang (Food Hydrocolloids, 2024)

Continuous microalgal culture module and method of culturing microalgae containing macular pigment - Meng-Wei Lin; Chih-Sheng Lin; Yu-Tso Chen; Shao-Qian Huang; Yi-Chun Yang; Wen-Xin Zhang; Wei-Hong Chiu; Cheng-Han Lin; Chiu-Mei Kuo (Bioresource Technology, 2024)

Report on the 4th Board Meeting of the International Human Phenome Consortium - Mei Tian; Han Liu; Shiwen Peng; Zhong Yang; Weishuo Tao; Huiting Che; Xuanxuan Gao; Li Jin (Phenomics, 2024)

Numerical simulation investigation on the seismic performance of high-strength concrete columns reinforced with PVA fibers and HTRB630 steel bars - Mei-Ling Zhuang; Chuanzhi Sun; Jinbo Chen; Hanbo Zhu; Li Gao; Yan Qiao; Yuefeng Shao; Weihua Zhang; Yixiang Han; Guangdong Bao (Bulletin of Earthquake Engineering, 2024)

The effects and mechanisms of deep straw incorporation and denitrifying bacterial agents on mitigating nitrate leaching and N2O emissions in four soil types in the North China Plain - Ya-Bo Zhang; Si-Yi Liu; Jun-Tao Wang; Hong J. Di; Li-Li Han; Pei-Pei Li; Ju-Pei Shen; Bing Han; Li-Mei Zhang (Agriculture, Ecosystems & Environment, 2024)

Pollution characteristics, source apportionment, and health risk assessment of PM10 and PM2.5 in rooftop and kerbside environment of Lanzhou, NW China - Chen-ming Gu; Bo Wang; Qu Chen; Xiao-han Sun; Mei Zhang (Environmental Science and Pollution Research, 2024)

ETE-SRSP: An Enhanced Optimization of Tramp Ship Routing and Scheduling - Xiaohu Huang; Yuhan Liu; Mei Sha; Bing Han; Dezhi Han; Han Liu (Journal of Marine Science and Engineering, 2024)
In the contemporary tramp shipping industry, route optimization and scheduling are directly linked to enhancements in operations, economics, and the environment, making them key factors for the effective management of maritime transportation. To enhance effective ship-to-cargo matching and the refinement of maritime transportation itineraries, this paper introduces a time efficiency and carbon dioxide emission multi-objective optimization algorithm named ETE-SRSP (efficiency–time–emission multi-optimization algorithm). ETE-SRSP incorporates several factors, including the initial positions of ships, time windows for loading and unloading operations, and varying sailing speeds. Within the ETE-SRSP framework, pioneering an approach that integrates ballast and laden sailing velocities as decisional parameters, it employs a multi-objective optimization technique to investigate the intricate interplay between temporal efficiency and carbon dioxide emissions. Additionally, the model’s proficiency in mitigating emissions and managing costs is clearly demonstrated through the optimization of these objectives, thereby offering a robust framework for decision support. The experimental results show that the optimal sailing speeds derived from the ETE-SRSP, under typical time-weight scenarios, can achieve an optimal balance between emission reduction and cost control. In summary, this study underscores the optimization strategy’s potential to effectively address the maritime sector’s need for economic growth and ecological conservation, showcasing its practical value in the industry.

Skin ulcers and microbiota in Rana dybowskii: Uncovering the role of the gut-skin axis in amphibian health - De-quan Zhu; Wen-jing Dong; Xin-zhou Long; Xiu-mei Yang; Xiao-yun Han; Yu-hong Kou; Qing Tong (Aquaculture, 2024)

Rice straw ash and amphibian health: A deep dive into microbiota changes and potential ecological consequences - Wen-jing Dong; Ming-da Xu; Xue-wen Yang; Xiu-mei Yang; Xin-zhou Long; Xiao-yun Han; Li-yong Cui; Qing Tong (Science of The Total Environment, 2024)

Integration of transcriptome, gut microbiota, and physiology reveals toxic responses of the red claw crayfish (Cherax quadricarinatus) to imidacloprid - Yao-Peng Lu; Jia-Han Liu; Xiu-Xia Zhang; Chi Xu; Pei-Hua Zheng; Jun-Tao Li; Jia-Jun Li; Dong-Mei Wang; Jian-An Xian; Ze-Long Zhang (Journal of Hazardous Materials, 2024)

Effect of multi-interface electron transportation and molecule adsorption on hydrogen evolution reaction - Xinyu Zhang; Zhihui Li; Xiaoman Yang; Hanming Zhang; Dan Wang; Zhian Li; Chengyue Han; Bingzheng Dong; Zhisheng Mei; Fei Teng (Chemical Engineering Journal, 2024)

Green manure substitution for potassium fertilizer promotes agro-ecosystem multifunctionality via triggering interactions among soil, plant and rhizosphere microbiome - Qing Zeng; Mei Yin; Li-Bo Fu; Brajesh K. Singh; Si-Yi Liu; Hua Chen; An-Hui Ge; Li-Li Han; Li-Mei Zhang (Plant and Soil, 2024)

Clinicopathological characteristics and prognosis of Epstein-Barr virus–associated gastric cancer - Lin-lin Li; Ao-yang Yu; Mei Zhu; Lu-yao Ma; Meng-han Cao; Wen-lou Liu; Xiao-bing Qin; Chao Gao; Zheng-xiang Han; Hong-mei Wang (Archives of Virology, 2024)

In vitro and in vivo genome-based safety evaluation of Lacticaseibacillus rhamnosus LRa05 - Ting Chen; Yawen Shao; Yinan Zhang; Yunjiao Zhao; Mei Han; Zhonghui Gai (Food and Chemical Toxicology, 2024)

Microbial community evolution and individual-based model validation of biofilms in single-stage partial nitrification/anammox system - Baohong Han; Wei Xing; Zhifeng Hu; Qianqian Tian; Jingjing Zhang; Xiangyu Han; Ning Mei; Xingcheng Zhao; Hong Yao (Bioresource Technology, 2024)

Analysis of an ozone episode in the Greater Bay Area based on low-cost sensor network - Wenlin Chen; Yingchuan Yang; Han Mei; Haijiong Sun; Peter K.K. Louie; Sabrina Yanan Jiang; Zhi Ning (Atmospheric Environment, 2024)

Integrative omics studies revealed synergistic link between sucrose metabolic isogenes and carbohydrates in poplar roots infected by Fusarium wilt - Xianglei Xu; Haikun Wei; Kejun Yao; Hao Wu; Tingting Huang; Mei Han; Tao Su; Fuliang Cao (Plant Molecular Biology, 2024)

Preconditioning exercise reduces brain damage of ischemic stroke in rats via PI3K–AKT pathway by bioinformatic analysis - Kai Li; Zhen-Kun Gao; Yi-Sha Guo; Xin-Ya Shen; Yu Han; Mei Yuan; Xia Bi (Experimental Brain Research, 2024)

Spatial and widely targeted metabolomics and anatomical analysis reveal the mechanisms associated with petal bicolor patterning of two Dendrobium species - Mei-Jing Ou; Hong-Yan Li; Han Liang; Zhen-Hai Deng; Zi-Bin Zhang; Jia-Wei Li (Brazilian Journal of Botany, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Herpesvirus activated NF-κB-mediated antigen processing and presentation to aggravate trichloroethylene-induced hypersensitivity dermatitis - Mengnan Yi; Yong Niu; Shuai Liu; Yuanyuan Chen; Bo Jiao; Yican Wang; Haijun Du; Guoyong Mei; Huawei Duan; Jun Han; Yufei Dai (Toxicology Letters, 2024)

Bbhox2 is a key regulator for conidiation and virulence in Beauveria bassiana - Juanjuan Li; Yan Zhang; Shouhao Jiao; Lian He; Yanhua Fan; Xuemeng Han; Binda Sun; Wenqi Zhao; Yanlin Mei; Ning Wei; Haiyue Zeng; Dan Jin (Journal of Invertebrate Pathology, 2024)

AOB Nitrosospira cluster 3a.2 (D11) dominates N2O emissions in fertilised agricultural soils - Na Deng; Cecile Gubry-Rangin; Xiao-Tong Song; Xiao-Tang Ju; Si-Yi Liu; Ju-Pei Shen; Hong-jie Di; Li-Li Han; Li-Mei Zhang (Journal of Environmental Management, 2024)

Prenatal exposure to poly- and perfluoroalkyl substances and postpartum depression in women with twin pregnancies - Liqin Hu; Hong Mei; Xiaonan Cai; Lulu Song; Qiao Xu; Wenqi Gao; Dan Zhang; Jieqiong Zhou; Chen Sun; Yi Li; Feiyan Xiang; Youjie Wang; et al. (International Journal of Hygiene and Environmental Health, 2024)

Changes in profiles of volatile compounds and prediction of the storage year of organic green tea during the long-term storage - Jia Li; Shanjie Han; Xianshan Mei; Mengxin Wang; Baoyu Han (Food Chemistry, 2024)

Aquifer Water Abundance Evaluation Based on a Variable Weight Model - Aoshuang Mei; Qiang Wu; Keyao Han; Yifan Zeng; Pengfei Yang; Yanping Miao; Yang Lv; Yashuai Cui; Liang Yang (Mine Water and the Environment, 2024)

Prenatal exposure to organophosphate esters and growth trajectory in early childhood - Wenyu Liu; Dan Luo; Aifen Zhou; Han Li; Adrian Covaci; Shunqing Xu; Surong Mei; Yuanyuan Li (Science of The Total Environment, 2024)

Application of roadside air purifiers in urban street canyons: A pilot-scale study in Hong Kong - Xinwei Li; Shuwen Han; Pengge Wang; Han Mei; Zhi Ning; Fan Dong; Long Cui; Yu Huang; Tao Wang; Shao-Yuan Leu; Meng Wang; Shun-cheng Lee (Science of The Total Environment, 2024)

Determination of tetrodotoxin in bivalve mollusks by hydrophilic interaction liquid chromatography-triple quadrupole mass spectrometry with internal standard calibration and its contamination in Zhejiang province, China - Ming-rong Qian; Hui-zhen Wu; Zeng-xuan Cai; Mei-jia Xu; Jian-long Han; Xiao-min Xu (Food Chemistry, 2024)

Integrated analysis of transcriptome and metabolome reveals the regulatory mechanism of largemouth bass (Micropterus salmoides) in response to Nocardia seriolae infection - Fen Dong; Yu-Long Sun; Yuan-Xin Qian; Qiang Chen; Jia-Le He; Ji-Teng Wang; Tao Han; Xiu-Mei Zhang; Yu-Ting Deng (Fish & Shellfish Immunology, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

Magnetic characteristics of atmospheric particulate matter and its indication of atmospheric pollution during winter in Lanzhou, NW China - Bo Wang; Chen-ming Gu; Qu Chen; Mei Zhang; Xiao-han Sun; Jia Jia (Atmospheric Environment, 2024)

Polyketides from Neohelicosporium griseum: structure assignment and bioactivity investigation - Lijuan Zhang; Jian Ma; Mingfei Yang; Tianming Zhao; Mei Yan Han; Dege Zheng; Ausana Mapook; Yongzhong Lu; Ruvishika S. Jayawardena (Medicinal Chemistry Research, 2024)

Metal(Loid)s in Aquatic Products and Their Potential Health Risk - Shi-Lin Hu; Xiao-Chen Chen; Ying-Xin Xue; Li-Ying Zhi; Yu-Han Yang; Yong-Guan Zhu; Xi-Mei Xue (Exposure and Health, 2024)

Pruning and quantization algorithm with applications in memristor-based convolutional neural network - Mei Guo; Yurui Sun; Yongliang Zhu; Mingqiao Han; Gang Dou; Shiping Wen (Cognitive Neurodynamics, 2024)

Laccase-evoked removal of antibiotics: Reaction kinetics, conversion mechanisms, and ecotoxicity assessment - Kai Sun; Mei-Hua Chen; Xue-Min Qi; Dan Hong; Ling-Zhi Dai; Shun-Yao Li; Yi-Chen Lu; Han-Qing Yu (Critical Reviews in Environmental Science and Technology, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

Transmittance optimization of tunnel shading shed for maximum energy savings and traffic safety: When replacing tunnel lighting in threshold zone - Fuqiang Xu; Zhigang Du; Jialin Mei; Lei Han (Tunnelling and Underground Space Technology, 2024)

Short-chain chlorinated paraffin (SCCP) exposure and type 2 diabetes risk: A population-based case-control study in East China - Gaoxin Zhang; Qinghua Zhang; Xiaoling Guan; Mei Liu; Lingling Meng; Xu Han; Yingming Li; Guibin Jiang (Science of The Total Environment, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Selaginellin derivatives from Selaginella tamariscina and evaluation for anti-breast cancer activity - Jing Wen; Dong-Mei Sha; Xiao-Yong He; Yu-Han Tian; Shuai-Cong Ni; Bin He; Yuan Liu; Xin-Jia Yan (Phytochemistry, 2024)

Aza-Wittig reaction of (β-diazo-α,α-difluoroethyl)phosphonates with aldehydes for the synthesis of difluoromethylphosphonate-containing arylidene hydrazones - Qian Wang; Romana Pajkert; Haibo Mei; Gerd-Volker Röschenthaler; Jianlin Han (Journal of Fluorine Chemistry, 2024)

Regioselective synthesis of 3H-Pyrazoles bearing difluoromethyl phosphonate group - Ita Hajdin; Romana Pajkert; Haibo Mei; Jianlin Han; Gerd-Volker Röschenthaler (Journal of Fluorine Chemistry, 2024)

Red blood cell membrane biomimetic nanoprobes for ratiometric imaging of reactive oxygen species level in atherosclerosis - Bo Liu; Gui-Mei Han; Dong-Xia Wang; Ding-Bin Liu; An-An Liu; Jing Wang; Yu-Ling Xiao; Lin Yuan; De-Ming Kong (Chemical Engineering Journal, 2024)

Effects of Aegilops longissima chromosome 1Sl on wheat bread-making quality in two types of translocation lines - Yuliang Qiu; Zhiyang Han; Ningtao Liu; Mei Yu; Shuangxi Zhang; Haiqiang Chen; Huali Tang; Zhiyong Zhao; Ke Wang; Zhishan Lin; Fangpu Han; Xingguo Ye (Theoretical and Applied Genetics, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

The data as a production factor: nonlinear effects of factor efficiency on haze pollution - Mei-Rui Zhong; Jia-Yu Fu; Han Zou (Environment, Development and Sustainability, 2023)

A co-twin control study of in utero exposure to poly- and perfluoroalkyl substances and associations with neonatal thyroid-stimulating hormone - Liqin Hu; Hong Mei; Xiaonan Cai; Feiyan Xiang; Na Li; Zhen Huang; Zhengrong Duan; Pan Yang; Han Xiao (Environmental Research, 2023)

Exogenous hydrogen supply improves in-situ biogas upgrading of sewage sludge: Performance and mechanisms - Zhong-Fang Sun; Lei Zhao; Jie-Ting Wu; Zi-Han Wang; Kai-Kai Wu; Chuan Chen; De-Feng Xing; Dong-Mei Liu; Shan-Shan Yang; Ai-jie Wang; Nan-Qi Ren (Chemical Engineering Journal, 2023)

Generating Stochastic Structural Planes by Considering Parameter Correlations Using Deep Generative Adversarial Networks - Han Meng; Gang Mei; Xiaoyu Qi; Nengxiong Xu; Jianbing Peng (Rock Mechanics and Rock Engineering, 2023)

SCD1 inhibits HBV replication by regulating autophagy under high lipid conditions - Xuan Du; Xiaoyi Shi; Mei Han; Xiaoyun Gao; Chuang Wang; Chunmeng Jiang; Chunwen Pu (Virus Genes, 2023)

Chlorite-incorporated clay nanosheets as acid and H2O2-activated gas-bombs for combating peri-implant infection - Cheng Yang; Lei Chen; Pengfei Yang; Siteng Li; Ruanbin Li; Han Liu; Feng Peng; Mei Li; Dongdong Zhang; Dengwen Zheng; Donghui Wang; Hua Zhong (Applied Clay Science, 2023)

Novel GdTaO4 phase for efficient photocatalytic degradation of organic dye under visible light irradiation: An X-ray spectroscopic investigation - Alageshwaramoorthy Krishnaprasanth; Pandian Mannu; Seetha Mahalingam; Dhanaprabhu Pattappan; Asokan Kandasami; Yi-Ting Lai; Yoshitake Masuda; Han-Wei Chang; Mei-Yu Chen; Ping-Hung Yeh; Chung-Li Dong (Chemosphere, 2023)

The impact of cooperative innovation network on innovation output of China's marine biomedical industry - Xiu-Mei Fu; Ying-Hui Han; Ying Liu; Qiao-Qiao Qi; Yan-Xin Tan; Meng Gao; Chun-Yu Lin (Ocean & Coastal Management, 2023)

Chemical profile of Artemisia vulgaris L. essential oil and its phytotoxic, insecticidal, and antimicrobial activities - Caixia Han; Guoxian Zhang; Yu Mei; Zixiang Shan; Kai Shi; Shixing Zhou; Hua Shao (South African Journal of Botany, 2023)

Bayesian network highlights the contributing factors for efficient arsenic phytoextraction by Pteris vittata in a contaminated field - Hiroshi Kudo; Ning Han; Daiki Yokoyama; Tomoko Matsumoto; Mei-Fang Chien; Jun Kikuchi; Chihiro Inoue (Science of The Total Environment, 2023)

Prenatal exposure to phthalates and child growth trajectories in the first 24 months of life - Meng Yang; Zhong Chen; Zhongqiang Cao; Hong Mei; Feiyan Xiang; Linling Yu; Liqin Hu; Aifen Zhou; Han Xiao (Science of The Total Environment, 2023)

Connecting link between a sediment source and its deep-sea sink: Ilan Shelf offshore northeastern Taiwan - Ho-Han Hsu; Char-Shine Liu; John D. Milliman; Tzu-Ting Chen; Jih-Hsin Chang; J. Paul Liu; Chih-Chieh Su; Mei-Chi Fan (Marine and Petroleum Geology, 2023)

The characteristics of rare earth elements in the main water filling sources of Sunan mining area - Xingyue Qu; Mei Qiu; Longqing Shi; Jin Han (Journal of Cleaner Production, 2023)

Bibliometric analysis of publications on biodegradation of plastics: Explosively emerging research over 70 years - Shan-Shan Yang; Wei-Min Wu; Ji-Wei Pang; Lei He; Meng-Qi Ding; Mei-Xi Li; Yi-Lin Zhao; Han-Jun Sun; De-Feng Xing; Nan-Qi Ren; Jun Yang; Craig S. Criddle; et al. (Journal of Cleaner Production, 2023)

Decision support framework adapted to local conditions to select technologies for rural domestic sewage treatment in the Yangtze River Economic Belt - Mei-Yun Lu; Shan-Shan Yang; Xin-Lei Yu; Han-Jun Sun; Ji-Wei Pang; Nan-Qi Ren; Jie Ding (Journal of Cleaner Production, 2023)

Efficacy of pterostilbene suppression on Aspergillus flavus growth, aflatoxin B1 biosynthesis and potential mechanisms - Yong-Mei Hu; Yi-Rong Wang; Wen-Bin Zhao; Yan Yan Ding; Zheng-Rong Wu; Guang-Han Wang; Peng Deng; Shao-Yong Zhang; Jun-Xia An; Zhi-Jun Zhang; Xiong-Fei Luo; Ying-Qian Liu (International Journal of Food Microbiology, 2023)

Determination of multiclass contaminants in chilli powder based on magnetic multiwalled carbon nanotubes and UPLC-QTOF/MS - Guangyun He; Xue Hou; Mei Han; Shiting Qiu; Xi Yu; Shudi Qin; Fengyi Wang; Ying Li (Food Research International, 2023)

A sweeter future: Using protein language models for exploring sweeter brazzein homologs - Bryan Nicholas Chua; Wei Mei Guo; Han Teng Wong; Dave Siak-Wei Ow; Pooi Leng Ho; Winston Koh; Ann Koay; Fong Tian Wong (Food Chemistry, 2023)

Capacity prediction and design optimization for laterally loaded monopiles in sandy soil using hybrid neural network and sequential quadratic programming - Amir Hosein Taherkhani; Qipei Mei; Fei Han (Computers and Geotechnics, 2023)

Toxicological sensitivity of protozoa to pesticides and nanomaterials: A prospect review - Chunyu Hou; Tianyi Shi; Wenyuan Wang; Mei Han; Xuming Pan; Li Wang; Duu-Jong Lee (Chemosphere, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Synthesis and anti-inflammatory, analgesic activities evaluation of cimifugin amino acid ester derivatives - Hao Chen; Yan Zhao; Fangfei Liu; Jiaxin Ma; Mei Han; Jiahong Han; Enbo Cai; Limin Yang (Phytochemistry Letters, 2023)

Two new iridoids and one new flavonoid glucoside from the tender leaves of Eucommia ulmoides and their anti-inflammatory activity - Zi-Yang Lv; Xiao-Mei Ren; Zhu-Zhen Han; Ruo-Yv Yan; Gui-Xin Chou; Ying-Bo Yang; Zi-Jia Zhang (Phytochemistry Letters, 2023)

Exposure to per- and polyfluoroalkyl substances in women with twin pregnancies: Patterns and variability, transplacental transfer, and predictors - Songyi Huang; Xiaojie Li; Langjing Deng; Jinying Xie; Guangtong Huang; Chenyan Zeng; Nanxin Wu; Sui Zhu; Chaoqun Liu; Hong Mei; Han Xiao; Da Chen; et al. (Journal of Hazardous Materials, 2023)

Overcoming slow removal efficiency-induced highly toxic I-DBPs in water by oxygen vacancies enriched invasive plant biochar catalyst: Experimental and theoretical studies - Yu-Han Fan; Yu-Wei Lu; Faisal Hayat; Yu-Han Mei; Ming Chen (Journal of Hazardous Materials, 2023)

Evaluation of Agricultural Non-point Source Pollution: a Review - Mei Luo; Xiaoxiao Liu; Nebiyou Legesse; Ying Liu; Sheng Wu; Fengxiang X. Han; Youhua Ma (Water, Air, & Soil Pollution, 2023)

Imbalance of multiple neurotransmitter pathways leading to depression-like behavior and cognitive dysfunction in the triple transgenic mouse model of Alzheimer disease - Meng Zhang; Li-yuan Liu; Yong Xu; Wen-zhi Wang; Nian-zhuang Qiu; Fang-fang Zhang; Feng Zhang; Xiao-dan Wang; Wei Chen; Xiao-yan Xu; Yong-feng Gao; Mei-hua Chen; et al. (Metabolic Brain Disease, 2023)

Population pharmacokinetics of topiramate in Chinese children with epilepsy - Shifeng Wei; Xingmeng Li; Qiang Zhang; Han Wu; Yun Wu; Zhigang Zhao; Shenghui Mei; Weixing Feng (European Journal of Clinical Pharmacology, 2023)

Rational design of genotyping nanodevice for HPV subtype distinction - De Yu Li; Yong Jian Jiang; Kun Han Nie; Jing Li; Yuan Fang Li; Cheng Zhi Huang; Chun Mei Li (Analytica Chimica Acta, 2023)

Navigating the depths: a stratification-aware coarse-to-fine received signal strength-based localization for internet of underwater things - Xiaojun Mei; Dezhi Han; Nasir Saeed; Huafeng Wu; Fahui Miao; Jiangfeng Xian; Xinqiang Chen; Bing Han (Frontiers in Marine Science, 2023)
Underwater wireless sensor networks (UWSNs) are the primary enabling technology for the Internet of underwater things (IoUT), with which all underwater objects can interact and communicate. In UWSNs, localization is vital for military or civilized applications since data collected without location are meaningless. However, accurate localization using acoustic signals in UWSNs is challenging, especially for received signal strength (RSS)-based techniques. The adverse effect of hybrid loss (path and absorption loss) and stratified propagation may severely impact localization accuracy. Even though some schemes have been proposed in the literature, the accuracy is unsatisfactory. To this end, this study proposes a coarse-to-fine localization method (CFLM). The problem is reformed into an alternating nonnegative constrained least squares (ANCLS) framework, where a constrained ellipse adjustment (CEA) using block principal pivoting is proposed to obtain the coarse estimation. A refined step using a Taylor series expansion is then further presented, in which a corrected solution is acquired by iteration. Additionally, this study derives the Cramér-Rao lower bound (CRLB) to evaluate the proposed method. Simulation results show that the proposed CFLM improves the localization accuracy by up to 66 percent compared with weighted least squares (WLS), privacy-preserving localization (PPSL), two-step linearization localization approach (TLLA), particle swarm optimization-based (PSO) localization, and differential evolution-based (DE) localization under different scenarios.

Exploring the effects of urban spatial structure on green space in Chinese cities proper - Shuaishuai Han; Mei-Po Kwan; Changhong Miao; Bindong Sun (Urban Forestry & Urban Greening, 2023)

Improved combustion of NH3/C2H4 with Ni modified Fe-based catalyst - Ye Wu; Longzhi Zou; Hang Zhu; Jian Mei; Kaixuan Yang; Yuhan Cui; Kun Qian; Yinghui Han; Maohong Fan; Dong Liu (Chemical Engineering Journal, 2023)

Highly efficient activation of sulfite by p-type S-doped g-C3N4 under visible light for emerging contaminants degradation - Wenyuan Lu; Lijie Xu; Xianbao Shen; Liang Meng; Yuwei Pan; Ying Zhang; Jiangang Han; Xiang Mei; Weichuan Qiao; Lu Gan (Chemical Engineering Journal, 2023)

Structural design of a hyperbranched chitosan-based bioplastic with excellent strength, antibacterial, and UV shielding performance - Shicun Jin; Lihong Xiong; Yuqing Yu; Jieping Xing; Jianzhang Li; Jingquan Han; Changtong Mei; Kuang Li; Huining Xiao (Chemical Engineering Journal, 2023)

A surface-induced coating strategy for constructing hydrophobic zeolite composite to enhance the toluene adsorption in humid environment - Shuangchun Lu; Wenjuan Xue; Hao Wang; Qingling Liu; Rui Han; Donghai Mei (Chemical Engineering Journal, 2023)

Role of NLRP3 inflammasome-mediated neuronal pyroptosis and neuroinflammation in neurodegenerative diseases - Ying-Hao Han; Xiao-Dong Liu; Mei-Hua Jin; Hu-Nan Sun; Taeho Kwon (Inflammation Research, 2023)

Detection of serum Aspergillus-specific IgM and IgG antibody levels for the diagnosis of chronic pulmonary aspergillosis developed in patients with tuberculosis - Zao-Xian Mei; Jun-Feng Han; Hong-Wei Yu; Yuan Zhang; Ping Ji; Yi Xie; Po-Ren Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

New insight into the irreversible membrane fouling in different pore-sized ultrafiltration ceramic membrane bioreactors (UCMBRs) for high-strength textile wastewater treatment - Qiwen Mei; Pengfei Zheng; Wenhao Ma; Ihnsup Han; Min Zhan; Bing Wu (Chemosphere, 2023)

Heterogeneous Fenton water purification catalyzed by iron phosphide (FeP) - Shu-Chuan Mei; Liang Li; Gui-Xiang Huang; Xiao-Qiang Pan; Han-Qing Yu (Water Research, 2023)

Resilience and probiotic interventions to prevent and recover from shrimp gut dysbiosis - Ramya Kumar; Mei-Ying Huang; Chih-Ling Chen; Han-Ching Wang; Hsiao-Pei Lu (Fish & Shellfish Immunology, 2023)

Biomimetic patternable polyhydroxyl nanocellulose/MXene films sequentially bridged through a synergistic hydrogen and ionic interaction with tunable multi-photoresponsive performances - Shaowei Wang; Xiaoyue Jin; Yiying Yue; Changtong Mei; Xinwu Xu; Qinglin Wu; Huining Xiao; Jingquan Han (Chemical Engineering Journal, 2023)

Controlled deposition via a bifunctional layer enables dendrite-free zinc metal batteries - Han Wang; Quanyu Li; Shaozhen Huang; Liangjun Zhou; Lin Mei; Zhibin Wu; Baihua Qu; Weifeng Wei; Xiaobo Ji; Yuejiao Chen; Libao Chen (Chemical Engineering Journal, 2023)

Synthesis of acylated derivatives of chitosan oligosaccharide and evaluation of their potential antifungal agents on Fusarium oxysporum - Bing Li; Lingyu Han; Jinlong Ma; Meijuan Zhao; Binghui Yang; Mei Xu; Yujia Gao; Qingsong Xu; Yuguang Du (Carbohydrate Polymers, 2023)

A comprehensive approach to quantify the source identification and human health risk assessment of toxic elements in park dust - Chang-Chen Huang; Li-Mei Cai; Yao-Hui Xu; Luo Jie; Guo-Cheng Hu; Lai-Guo Chen; Han-Zhi Wang; Xu-Bang Xu; Jing-Xian Mei (Environmental Geochemistry and Health, 2023)

Whole-Genome Sequencing of Pseudomonas koreensis Isolated from Diseased Tor tambroides - Cindy Jia Yung Kho; Melinda Mei Lin Lau; Hung Hui Chung; Ivy Yee Yen Chew; Han Ming Gan (Current Microbiology, 2023)

Short-term Dietary Selenium Deficiency Induced Liver Fibrosis by Inhibiting the Akt/mTOR Signaling Pathway in Rats - Lichun Qiao; Xue Lin; Yan Zhao; Qingfeng Wang; Haobiao Liu; Mei You; Qian Yuan; Zhihao Yang; Wenming Bian; Jiaxin Liu; Ziwei Guo; Jing Han (Biological Trace Element Research, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Chemical characterization and source attribution of organic pollutants in industrial wastewaters from a Chinese chemical industrial park - Yihua Huang; Yinong You; Manman Wu; Min Han; Jin Zhang; Wei Gao; Danping Xie; Hongzhan Chen; Hui Ou; Ninghui Song; Chunlei Cheng; Wen Zhuang; et al. (Environmental Research, 2023)

Tumor microenvironment as a bioreactor for Au&Fe3O4-DNA complex synthesis and targeted cancer therapy - Yi Han Wang; Ke Huang; Zhao Jian Qin; Hong Jie Xiong; Teng Fei Liu; Ting Ya Wang; Xiang Dong Lai; Xiao Hui Liu; Hui Jiang; Xue Mei Wang (Chemical Engineering Journal, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Force system conversion mechanisms of retaining structures for subway excavation in soft soil - Meng Han; Zhe Li; Jinqing Jia; Xiaohua Bao; Guoxiong Mei; Lulu Liu (Bulletin of Engineering Geology and the Environment, 2023)

Digested extracellular DNA shortens the anodic startup of microbial electrolysis cell - Xiangyu Han; Jiaman Wang; Jingjing Zhang; Baohong Han; Ning Mei; Runchuan Fan; Jing Zhao; Hong Yao; Xiaohua Yu; Weiwei Cai (Science of The Total Environment, 2023)

The last Neoproterozoic rift magmatism on the western margin of Yangtze block, South China: New insights of Marinoan onset from low-δ18O magmatic events - Chang-Cheng Huang; Hao Zou; Hai-Feng Chen; Franco Pirajno; Zhong-Wu Lan; Hui-Dong Yu; Bin Xiao; Chun-Mei Liu; Jiang-Han Wu; Yi-Jiang Zhong; Ming-Cai Hou (Precambrian Research, 2023)

Effects of sericin on oxidative stress and PI3K/AKT/mTOR signal pathway in cryopreserved mice ovarian tissue - Wei Han Shu; Song He Yang; Meng Wei; Xiao Chao Liu; Zi Xuan Chen; Chen Yang Wei; Xin Zhang; Li Na Si; Zhi Hong Chen; Yue Bing Qiao; Dong Mei Li; Tie Cheng Sun; et al. (Cryobiology, 2023)

Experimental and numerical study of micro-tubular direct carbon solid oxide fuel cell fueled by the oilseed rape straw-derived biochar - Tingting Han; Yujiao Xie; Lin Li; Ke Miao; Yu Mei; Jian Song; Jinjin Zhang; Xiuxia Meng; Ngie Hing Wong; Jaka Sunarso; Fangyong Yu; Naitao Yang (Chemical Engineering Journal, 2023)

Hydrochromic wood biocomposites for humidity and moisture detection - Yujie Chen; Chaozheng Liu; Zhaolun Liang; Lei Ye; Lin Liu; Zhipeng Liu; Xinhao Feng; Lloyd Donaldson; Tripti Singh; Xianxu Zhan; Jingquan Han; Qiliang Fu; et al. (Chemical Engineering Journal, 2023)

Protective Effect of Ergothioneine Against Stroke in Rodent Models - Wei-Yi Ong; Mei-Han Kao; Wai-Mui Cheung; Damien Meng-Kiat Leow; Irwin Kee-Mun Cheah; Teng-Nan Lin (NeuroMolecular Medicine, 2023)

Exposure to novel brominated and organophosphate flame retardants and associations with type 2 diabetes in East China: A case-control study - Gaoxin Zhang; Lingling Meng; Jiehong Guo; Xiaoling Guan; Mei Liu; Xu Han; Yingming Li; Qinghua Zhang; Guibin Jiang (Science of The Total Environment, 2023)

Rapid screening of diarylpentanoids from Daphne bholua - Shu-Hui Dong; Mei-Ya Lian; Jin-Ling Han; Yun-Fei Ai; Xiao-Fang Zhou; Ming Bai; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Detection of a mid-Holocene climate event at 7.2 ka BP based on an analysis of globally-distributed multi-proxy records - Mei Hou; Wenxiang Wu; David J. Cohen; Zhaoqi Zeng; Han Huang; Hongbo Zheng; Quansheng Ge (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Different sensitivities and assembly mechanisms of the root-associated microbial communities of Robinia pseudoacacia to spatial variation at the regional scale - Yongli Ku; Xiaoting Han; Yuting Lei; Mei Zhang; Zhong Zhao (Plant and Soil, 2023)

Transcriptional profiles of TGF-β superfamily members in the lumbar DRGs and the effects of activins A and C on inflammatory pain in rats - Feng-Ming Zhang; Bing Wang; Han Hu; Ying-Ying Zhang; Hao-Hao Chen; Zuo-Jie Jiang; Mei-Xing Zeng; Xing-Jun Liu (Journal of Physiology and Biochemistry, 2023)

Critical role of extracellular DNA in the establishment and maintenance of anammox biofilms - Baohong Han; Lijun Yang; Zhifeng Hu; Yao Chen; Ning Mei; Hong Yao (Science of The Total Environment, 2023)

Seismic behaviour of shear critical square RC columns strengthened by large rupture strain FRP - Shi-Jie Mei; Yu-Lei Bai; Jian-Guo Dai; Qiang Han (Engineering Structures, 2023)

Platycodon grandiflorus subjected to full- and restricted-water regimes show differential biosynthesis of triterpenoid saponins - Min Li; Lin Cheng; Meng Zhang; Li Min Yang; Mei Han (Acta Physiologiae Plantarum, 2023)

Single bubble probe atomic force microscope and impinging-jet technique unravel the interfacial interactions controlled by long chain fatty acid in anaerobic digestion - Jian-Lu Duan; Yi Han; Li-Juan Feng; Jing-Ya Ma; Xiao-Dong Sun; Xiao-Yu Liu; Fan-Shu Geng; Jia-Li Jiang; Mei-Yan Liu; Yu-Chen Sun; Pascal Peu; Bing-Jie Ni; et al. (Water Research, 2023)

Urinary concentrations of organophosphate esters in relation to semen quality: A cross-sectional study - Yaping Li; Dan Luo; Xiaoya Zhao; Han Wang; Zhiyi Zheng; Jun Liu; Chong Liu; Hui Wang; Yingjun Chen; Yinzhu Shang; Wenqing Lu; Surong Mei; et al. (Science of The Total Environment, 2023)

2,3′,4,4′,5-Pentachlorobiphenyl induces mitochondria-dependent apoptosis mediated by AhR/Cyp1a1 in mouse germ cells - Qiu-Yue Wang; Lin Zhang; Xiao-Ying Han; Dong-Mei Wang; Ming-Long Ding; Dong Cheng; Qi-Long He; Shu-Zhen Liu (Journal of Hazardous Materials, 2023)

Structural and functional properties of sodium caseinate glycosylated by dextran aldehyde - Ying Li; Dong-Mei Li; Yu Han; Xin-An Zeng; Zhong Han (Food Chemistry, 2023)

Exposure to bisphenols, parabens and phthalates during pregnancy and postpartum anxiety and depression symptoms: Evidence from women with twin pregnancies - Liqin Hu; Hong Mei; Huan Feng; Yufang Huang; Xiaonan Cai; Feiyan Xiang; Luyi Chen; Han Xiao (Environmental Research, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Wetting behavior during impacting bituminous coal surface for dust suppression droplets of fatty alcohol polyoxyethylene ether - Fangwei Han; Yue Zhao; Mei Liu; Fuhong Hu; Yingying Peng; Liang Ma (Environmental Science and Pollution Research, 2023)

Simultaneous determination of erythromycin and its transformation products in treated erythromycin fermentation residue and amended soil - Haodi Feng; Mei Tang; Ziming Han; Xiao Luan; Chunmeng Ma; Min Yang; Jiuyi Li; Yu Zhang (Chemosphere, 2023)

Ecological value of mariculture shellfish resources in China: Assessment and management - Chun-Yu Lin; Gui-Lin Dai; Yang Liu; Meng-Qi Zhang; Ying Liu; Wen Jiang; Xiu-Mei Fu; Han-Xue Chen (Marine Policy, 2023)

Divergent responses in the gut microbiome and liver metabolome to ammonia stress in three freshwater turtles - Qin-Yuan Meng; Dong-Mei Mo; Han Li; Wan-Ling Wang; Hong-Liang Lu (Science of The Total Environment, 2023)

Amino-functionalized multilayer Ti3C2Tx enabled electrochemical sensor for simultaneous determination of Cd2+ and Pb2+ in food samples - Yuanyuan Chen; Peng Zhao; Zhikun Hu; Yi Liang; Haiyan Han; Mei Yang; Xiaogang Luo; Changjun Hou; Danqun Huo (Food Chemistry, 2023)

Pyrite coupled with biochar alleviating the toxicity of silver nanoparticles on pollutants removal in constructed wetlands - Mengli Chen; Han Mei; Hao Qin; Xiangyu Yang; Fucheng Guo; Yi Chen (Environmental Research, 2023)

Report on the 3rd Board Meeting of the International Human Phenome Consortium - Mei Tian; Han Liu; Shunling Chen; Zhong Yang; Weishuo Tao; Shiwen Peng; Huiting Che; Li Jin (Phenomics, 2023)

Uplift history of the Northern Tianshan constrained from the inversion of river profiles - Runing Hou; Mei Liu; Ningsheng Chen; MingFeng Deng; Shufeng Tian; Yujia Li; Huayong Ni; Zheng Han (International Journal of Earth Sciences, 2023)

Targeted isolation of antitubercular cycloheptapeptides and an unusual pyrroloindoline-containing new analog, asperpyrroindotide A, using LC–MS/MS-based molecular networking - Yi-Qian Han; Qun Zhang; Wei-Feng Xu; Yang Hai; Rong Chao; Cui-Fang Wang; Xue-Mei Hou; Mei-Yan Wei; Yu-Cheng Gu; Chang-Yun Wang; Chang-Lun Shao (Marine Life Science & Technology, 2023)
Further insights on the secondary metabolites of a soft coral-derived fungus Aspergillus versicolor under the guidance of MS/MS-based molecular networking led to the isolation of seven known cycloheptapeptides, namely, asperversiamides A–C ( 1 – 3 ) and asperheptatides A–D ( 4 – 7 ) and an unusual pyrroloindoline-containing new cycloheptapeptide, asperpyrroindotide A ( 8 ). The structure of 8 was elucidated by comprehensive spectroscopic data analysis, and its absolute configuration was determined by advanced Marfey’s method. The semisynthetic transformation of 1 into 8 was successfully achieved and the reaction conditions were optimized. Additionally, a series of new derivatives ( 10 − 19 ) of asperversiamide A ( 1 ) was semi-synthesized and their anti-tubercular activities were evaluated against Mycobacterium tuberculosis H37Ra. The preliminary structure−activity relationships revealed that the serine hydroxy groups and the tryptophan residue are important to the activity.

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Effect of hydrodynamics on the transformation of nitrogen in river water by regulating the mass transfer performance of dissolved oxygen in biofilm - Mei Pan; Haizong Li; Xiangyun Han; Guixiang Quan; Weixing Ma; Qingyuan Guo; Xuan Li; Bairen Yang; Cheng Ding; Yuxi Chen; Tao Yun; Jiaojiao Qin; et al. (Chemosphere, 2023)

Co-exposure to phenols and phthalates during pregnancy with the difference of body size in twins at one month old - Hong Mei; Langjing Deng; Jinying Xie; Xiaojie Li; Nanxin Wu; Liqin Hu; Guangtong Huang; Fanyu Mo; Da Chen; Han Xiao; Pan Yang (Chemosphere, 2023)

Bioactive diterpenoids and sesquiterpenoids with different skeletons from Salvia digitaloides Diels - Xu Liu; Xiao-Qing Zhan; Mei-Jie Wang; Wen-Bo Cui; Xiao-Han Chen; Feng-Ming Qi; Jian-Ning Yu; Jian-Ye Dai; Dong-Qing Fei; Zhan-Xin Zhang (Phytochemistry, 2023)

Cross-biome soil viruses as an important reservoir of virulence genes - Li Bi; Li-Li Han; Shuai Du; Dan-Ting Yu; Ji-Zheng He; Li-Mei Zhang; Hang-Wei Hu (Journal of Hazardous Materials, 2023)

Molting-related proteases in the brown planthopper, Nilaparvata lugens - Yu-Cheng Xie; Hou-Hong Zhang; Han-Jing Li; Xiao-Ya Zhang; Xu-Mei Luo; Ming-Xing Jiang; Chuan-Xi Zhang (Insect Biochemistry and Molecular Biology, 2023)

Small-sized Ni nanoparticles embedded nickel phyllosilicate as a metal-acid bifunctional zeolite catalyst for cooperatively boosting CO2-CH4 reforming - Chengming Huang; Yiming Zhang; Dingmei Han; Binbin He; Xinyu Sun; Meiyu Liu; Yi Mei; Yun Zu (Fuel, 2023)

Environmental concentrations of benzophenone-3 disturbed lipid metabolism in the liver of clown anemonefish (Amphiprion ocellaris) - Yan-Kun Zhang; Huai-Yang Ke; Yong-Qiang Qin; Han-Ye Ju; Yu-Mei Chen; Fang Lin; Ji-Liang Zhang; Xiao-Ping Diao (Environmental Pollution, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

Activating nitrogen-doped carbon nanosheets by KOH treatment to promote the Fischer-Tropsch synthesis performance - Qiao Zhao; Xiaoxue Han; Haoting Liang; Yue Wang; Jing Lv; Mei-Yan Wang; Shouying Huang; Xinbin Ma (Chemical Engineering Journal, 2023)

In-situ self-assembled block copolymer nanowires on high-modulus carbon fibers surface for enhanced interfacial performance of CFRPs - Han Zhang; Haoruo Zhang; Xueqin Zhang; Tong Sun; Mei Liang; Yang Chen; Zhengguang Heng; Huawei Zou (Chemical Engineering Journal, 2023)

The Nucleus Accumbens CRH–CRHR1 System Mediates Early-Life Stress-Induced Sleep Disturbance and Dendritic Atrophy in the Adult Mouse - Ting Wang; Yu-Nu Ma; Chen-Chen Zhang; Xiao Liu; Ya-Xin Sun; Hong-Li Wang; Han Wang; Yu-Heng Zhong; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2023)

Removal of Cd from contaminated farmland soil by washing with residues of traditional Chinese herbal medicine extracts - Yi Wang; Yuan Li; Shuai Yang; Qi-hao Wang; Shao-cheng Si; Han-yi Mei; Guo-ming Liu; Xiang-liang Pan; Yong-ming Luo (Environmental Science and Pollution Research, 2022)

The association between several autophagy-related genes and their prognostic values in hepatocellular carcinoma: a study on the foundation of TCGA, GEPIA and HPA databases - Xueying Zhao; Shangqi Yin; Jingren Shi; Mei Zheng; Chaonan He; Huan Meng; Ying Han; Jin Chen; Jinyu Han; Zhengrong Yuan; Yajie Wang (Molecular Biology Reports, 2022)

Rootstock rescues watermelon from Fusarium wilt disease by shaping protective root-associated microbiomes and metabolites in continuous cropping soils - An-Hui Ge; Zhi-Huai Liang; Li-Li Han; Ji-Ling Xiao; Yi Zhang; Qing Zeng; Ji-Fang Xiang; Chao Xiong; Li-Mei Zhang (Plant and Soil, 2022)

Cassane diterpenoids from Caesalpinia pulcherrima and their anti-inflammatory and α -glycosidase inhibitory activities - Xin Yun; Xiu-Mei Chen; Jia-Yun Wang; Wang Lu; Zi-Han Zhang; Young Ho Kim; Shi-Chun Zong; Chun-Huan Li; Jin-Ming Gao (Natural Product Research, 2022)

Reclamation-oriented spatiotemporal evolution of coastal wetland along Bohai Rim, China - Fan Wei; Mei Han; Guangxuan Han; Min Wang; Lixin Tian; Jiqian Zhu; Xianglun Kong (Acta Oceanologica Sinica, 2022)

Rapid Characterization of Landslide-Debris Flow Chains of Geologic Hazards Using Multi-method Investigation: Case Study of the Tiejiangwan LDC - Kun He; Bo Liu; Xiewen Hu; Ruichen Zhou; Chuanjie Xi; Guotao Ma; Mei Han; You Li; Gang Luo (Rock Mechanics and Rock Engineering, 2022)

The contribution of nirK gene-containing thaumarchaea to denitrification and N2O production across coastal sediment and terrestrial ecosystems - Bing Han; Si-Yi Liu; Li-Li Han; Xiao-Tong Song; Liu-Ying Mo; Li-Mei Zhang (Journal of Soils and Sediments, 2022)

Characteristics of subway excavation in soft soil and protective effects of partition wall on the historical building and pile foundation building - Meng Han; Zhe Li; Guoxiong Mei; Xiaohua Bao; Jinqing Jia; Lulu Liu; Youyun Li (Bulletin of Engineering Geology and the Environment, 2022)

Evaluating water resource carrying capacity using the deep learning method: a case study of Yunnan, Southwest China - Han Zhang; Cheng Huang; Xudong Hu; Hongbo Mei; Ruifeng Hu (Environmental Science and Pollution Research, 2022)

Grain size-dependent geochemical evidence reveals provenance and implications of aeolian sands, Dinggye region, southern Tibet - You-gui Chen; Mei-hui Pan; Ze-wen Hao; Yu-han Qi; Chen-lu Li (Journal of Mountain Science, 2022)

Vocalization of Bryde's whales ( Balaenoptera edeni ) in the Beibu Gulf, China - Zhi‐Tao Wang; Peng‐Xiang Duan; Mo Chen; Zhi‐Gang Mei; Xiao‐Dong Sun; Zhi‐Wen Nong; Mei‐Han Liu; Tomonari Akamatsu; Ke‐Xiong Wang; Ding Wang (Marine Mammal Science, 2022)
The presence of Bryde's whales ( Balaenoptera edeni ) in the Beibu Gulf, China has been reported since 2016. In the current study, in situ Bryde's whale vocalizations were recorded. Bouts of frequency modulated repetitive and diversified calls were recorded. Repetitive calls were recorded when 1–3 whales were present within 2 km of the boat and were probably emitted by a single whale and functioned as contact calls. Repetitive calls were divided into biphonation downswept tonals and downswept tonals. Diversified calls were recorded when 4–7 whales were present within 2 km of the boat and were probably associated with acoustic exchanges between or among conspecifics. Diversified calls occasionally contained inflection points, frequency jumps, and break point features. The frequency band of Bryde's whale vocalizations overlapped highly with background noise. Most vocalizations in the current study were different than those previously reported for this species. Therefore, the findings of this study provide more information on the known acoustic repertoire of Bryde's whales and provide a basis for noninvasive monitoring of Bryde's whale with passive acoustic methods and for developing mitigation and conservation protocols to ensure their future viability.

Cerebellar Oscillations in Familial and Sporadic Essential Tremor - Shi-Bing Wong; Yi-Mei Wang; Chih-Chun Lin; Scott Kun Geng; Nora Vanegas-Arroyave; Seth L. Pullman; Sheng-Han Kuo; Ming-Kai Pan (The Cerebellum, 2022)

Functional microglia derived from human pluripotent stem cells empower retinal organs - Mei-Ling Gao; Xiao Zhang; Fang Han; Jia Xu; Si-Jian Yu; Kangxin Jin; Zi-Bing Jin (Science China Life Sciences, 2022)

Driving Factors, Co-occurrence Networks, and Metabolic Profiles of Soil Bacterial Communities Within the Root Proximity of Amaranthus palmeri - Mei Zhang; Xueying Li; Cong Shi; Zhenlu Qiu; Jianhua Han; Kefan Wang; Pufan Zheng; Fuchen Shi (Journal of Soil Science and Plant Nutrition, 2022)

Assessing the Resilience of the Marine Economy: A Case Study of Southern China’s Marine Economy Circle - Yue Hu; Han Qian Zhou; Xiao Mei Jin; Ya Fang Shen; Yong Zhe Yan (Frontiers in Marine Science, 2022)
As an important part of the national economy, the marine economy will be subject to various internal and external disturbances in the process of development. Different regions will show different resilience. Based on four dimensions of “resistance–recovery–reorientation–renewal,” this paper measures the marine economic resilience of the four provinces covered within the China’s Southern Marine Economy Circle from 2008 to 2018 by establishing an evaluation index system. The results show that 1) the overall resilience of economy in the Southern Marine Economy Circle showed a fluctuating upward trend from 2008 to 2018. Although there was a decline in 2011–2012 due to natural disasters, the value quickly resumed its increasing trend. 2) At present, there are obvious relative differences in the resilience of marine economy in each region of China’s Southern Marine Economy Circle, and the polarization phenomenon is serious. Among them, Guangdong belongs to the high-value region and Fujian is in the middle, while Hainan and Guangxi are temporarily in the low-value area.

Chemical composition and phytotoxic activity of the essential oil of Artemisia sieversiana growing in Xinjiang, China - Chun-Yu Jiang; Shi-Xing Zhou; Zokir Toshmatov; Yu Mei; Guang-Zhao Jin; Cai-Xia Han; Chi Zhang; Hua Shao (Natural Product Research, 2022)

BSA‑seq and genetic mapping reveals AhRt2 as a candidate gene responsible for red testa of peanut - Kun Zhang; Mei Yuan; Han Xia; Liangqiong He; Jing Ma; Mingxiao Wang; Huiling Zhao; Lei Hou; Shuzhen Zhao; Pengcheng Li; Ruizheng Tian; Jiaowen Pan; et al. (Theoretical and Applied Genetics, 2022)

Correction to: Effectiveness of Newmark‑based sampling strategy for coseismic landslide susceptibility mapping using deep learning, support vector machine, and logistic regression - Chuanjie Xi; Mei Han; Xiewen Hu; Bo Liu; Kun He; Gang Luo; Xichao Cao (Bulletin of Engineering Geology and the Environment, 2022)

Effectiveness of Newmark-based sampling strategy for coseismic landslide susceptibility mapping using deep learning, support vector machine, and logistic regression - Chuanjie Xi; Mei Han; Xiewen Hu; Bo Liu; Kun He; Gang Luo; Xichao Cao (Bulletin of Engineering Geology and the Environment, 2022)

Enhanced genome editing to ameliorate a genetic metabolic liver disease through co-delivery of adeno-associated virus receptor - Shuming Yin; Lie Ma; Tingting Shao; Mei Zhang; Yuting Guan; Liren Wang; Yaqiang Hu; Xi Chen; Honghui Han; Nan Shen; Wenjuan Qiu; Hongquan Geng; et al. (Science China Life Sciences, 2022)

Positron Emission Tomography Molecular Imaging for Phenotyping and Management of Lymphoma - Xiaohui Zhang; Han Jiang; Shuang Wu; Jing Wang; Rui Zhou; Xuexin He; Shufang Qian; Shuilin Zhao; Hong Zhang; Ali Cahid Civelek; Mei Tian (Phenomics, 2022)

Polycyclic aromatic hydrocarbons in street dust from different functional areas in Chengdu, China: seasonal variation and health risk assessment - Han-Han Li; Zhan-Biao Yang; Xiao-Xun Xu; Xue-Mei Zhu; Jun-Ren Xian; Yuan-Xiang Yang; Zhang Cheng (Environmental Geochemistry and Health, 2022)

Susceptibility of patients with chronic obstructive pulmonary disease to heart rate difference associated with the short-term exposure to metals in ambient fine particles: A panel study in Beijing, China - Ke Gao; Xi Chen; Xiaoying Li; Hanxiyue Zhang; Mengxiao Luan; Yuan Yao; Yifan Xu; Teng Wang; Yiqun Han; Tao Xue; Junxia Wang; Mei Zheng; et al. (Science China Life Sciences, 2022)

MiR-582-3p participates in the regulation of biological behaviors of A549 cells by ambient PM2.5 exposure - Mei Yang; Liangliang Ju; Changlian Li; Han Cheng; Na Li; Qi Zhang; Shu Sun; Liu Ding; Xinmiao Sui; Chao Zhang; Mingwei Yang; Jiyu Cao; et al. (Environmental Science and Pollution Research, 2022)

Development and validation of a 30-day death nomogram in patients with spontaneous cerebral hemorrhage: a retrospective cohort study - Qian Han; Mei Li; Dongpo Su; Aijun Fu; Lin Li; Tong Chen (Acta Neurologica Belgica, 2022)

Current Dependent Dispersal Characteristics of Japanese Glass Eel around Taiwan - Kuan-Mei Hsiung; Yen-Ting Lin; Yu-San Han (Journal of Marine Science and Engineering, 2022)
Japanese eel larvae are passively transported to the East Asian Continental Shelf by the North Equatorial Current, Kuroshio and Kuroshio intrusion currents, and coastal currents. Previous studies have investigated the dispersal characteristics and pathways of Japanese glass eels. However, there are still limitations in these studies. According to long-term (2010–2020) catch data from the Fisheries Agency in Taiwan, the distribution and time series of glass eels recruitment to Taiwan are closely related to the surrounding ocean currents. Recruitment begins in eastern Taiwan via the mainstream Kuroshio and in southern Taiwan via the Taiwan Strait Warm Current. In central Taiwan, recruitment occurs from southern Taiwan, as well as from mainland China via the southern branch of the China Coast Current (CCC). The latest recruitment occurred in northern Taiwan and mainly comprised glass eels from mainland China via the northern branch of the CCC. A stronger monsoon during the La Niña phase could affect the recruitment time series in northern and eastern Taiwan. This study suggests that the recruitment directionality of glass eels is an indicator of the flow field of ocean/coastal currents and elucidates the dispersal characteristics of glass eels in the waters around Taiwan.

Historical Connectivity and Demography of the Ferocious Reef Crab, Eriphia ferox (Crustacea; Eriphiidae), Demonstrate That Taoyuan Algal Reef Is an Essential Population Source Along the East Taiwan Strait - Mu-Han Chen; Ya-Yi Huang; Bi-Ying Huang; Hernyi Justin Hsieh; Jen Nie Lee; Mei Lin Neo; Hironobu Fukami; Chaolun Allen Chen (Frontiers in Marine Science, 2022)
The east Taiwan Strait is largely fringed by sandy and muddy habitats. However, a massive algal reef made of crustose coralline algae has been found along the coast off Taoyuan city in northwestern Taiwan. The porous structure of Taoyuan Algal Reef harbors high abundance and diversity in marine organisms, including the ferocious reef crab, Eriphia ferox . Such a pivotal geographic location and unique ecological features make Taoyuan Algal Reef a potential stepping stone connecting biotic reefs in the east Taiwan Strait, South China Sea to the south, and even the high latitude of Japan to the north. In this study, we examined the population connectivity and historical demography of E. ferox by analyzing mitochondrial cytochrome oxidase I (COI) fragments of 317 individuals sampled from 21 localities in the northwestern Pacific. Our analyses of haplotype network and pairwise F ST comparisons revealed a lack of phylogeographical structure among E. ferox populations, implying the existence of a migration corridor connecting the South and East China Seas through the east Taiwan Strait. Multiple lines of evidence, including significant values in neutrality tests, unimodally shaped mismatch distributions, and Bayesian skyline plots elucidated the rapid population growth of E. ferox following the sea-level rise after Last Glacial Maximum (ca. 2–10 Ka). Such demographic expansion in E. ferox coincided with the time when Taoyuan Algal Reef started to build up around 7,500 years ago. Coalescent migration analyses further indicated that the large and continuous E. ferox population exclusively found in Datan Algal Reef, the heart of Taoyuan Algal Reef, was a source population exporting migrants both northward and southward to the adjacent populations. The bidirectional gene flow should be attributed to larval dispersal by ocean currents and secondary contact due to historical population expansion. Instead of serving as a stepping stone, our results support that Taoyuan Algal Reef is an essential population source for biotic reef-associated species along the east Taiwan Strait, and highlight the importance of conserving such a unique ecosystem currently threatened by anthropogenic development.

Effect of feed restriction on the intestinal microbial community structure of growing ducks - Jun-peng Li; Qi-fan Wu; Sheng-chao Ma; Jian-mei Wang; Bin Wei; Yang Xi; Chun-chun Han; Liang Li; Hua He; He-he Liu (Archives of Microbiology, 2022)

Lathyrane diterpenoids from Jatropha podagrica and their antitumor activities in human osteosarcoma cells - Han-Tao Yuan; Qun-Feng Li; Tian Tian; Chun-Yan Zhang; Zou-Qin Huang; Chun-Xiang Fan; Ke Mei; Jie Zhou; Xiao-Xiang Zhai; Si-Bo Li; Jian-Yong Zhu (Natural Product Research, 2021)

MiR-96-5p is an oncogene in lung adenocarcinoma and facilitates tumor progression through ARHGAP6 downregulation - Zhifang Liu; Yong Cui; Shuwei Wang; Changhao Wu; Fuyang Mei; Erlei Han; Zhibin Hu; Bing Zhou (Journal of Applied Genetics, 2021)

Three new diterpenoids from Euphorbia peplus - Yan-Ni Chen; Qing-Yun Lu; Dong-Mei Li; Ying-Yao Li; Xue-Xue Pu; Bo-Ting Li; Xiao-Han Tang; Hong-Yu Tang; Shuai Liu; Lei Yang; Yu Zhang; Ying-Tong Di; et al. (Natural Product Research, 2021)

TLR2 Potentiates SR-Marco-Mediated Neuroinflammation by Interacting with the SRCR Domain - Lu Wang; Han-Yu Yang; Cai-Xia Zang; Jun-Mei Shang; Hui Liu; Zi-Hong Zhang; Fang-Yu Yuan; Cheng Ju; Fang-Yuan Li; Xiu-Qi Bao; Dan Zhang (Molecular Neurobiology, 2021)

A comprehensive exploration on pollution characteristics and health risks of potentially toxic elements in indoor dust from a large Cu smelting area, Central China - Han-Zhi Wang; Li-Mei Cai; Shuo Wang; Guo-Cheng Hu; Lai-Guo Chen (Environmental Science and Pollution Research, 2021)

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

Therapeutic Potential of Cytokines in Demyelinating Lesions After Stroke - Yi-Sha Guo; Mei Yuan; Yu Han; Xin-Ya Shen; Zhen-Kun Gao; Xia Bi (Journal of Molecular Neuroscience, 2021)

Lipophilic Conjugates of Drugs: A Tool to Improve Drug Pharmacokinetic and Therapeutic Profiles - Sifei Han; Lianghe Mei; Tim Quach; Chris Porter; Natalie Trevaskis (Pharmaceutical Research, 2021)

Methane Concentration in the Heartwood of Living Trees and Estimated Methane Emission on Stems in Upland Forests - Zhi-Ping Wang; Huan-Long Li; Hong-Hui Wu; Shi-Jie Han; Jian-Hui Huang; Xi-Mei Zhang; Xing-Guo Han (Ecosystems, 2021)

Apigenin Improves Hypertension and Cardiac Hypertrophy Through Modulating NADPH Oxidase-Dependent ROS Generation and Cytokines in Hypothalamic Paraventricular Nucleus - Hong-Li Gao; Xiao-Jing Yu; Han-Bo Hu; Qian-Wen Yang; Kai-Li Liu; Yan-Mei Chen; Yan Zhang; Dong-Dong Zhang; Hua Tian; Guo-Qing Zhu; Jie Qi; Yu-Ming Kang (Cardiovascular Toxicology, 2021)

The enhanced functional traits contribute to the successful invasion of Amaranthus palmeri in salinity environments: a comparison with its congeners - Tongtong Wang; Jianhua Han; Hongwen Fang; Amir Abdullah Khan; Lili Tang; Mei Zhang; Fuchen Shi (Biologia, 2021)

Triterpene saponins from tea seed pomace ( Camellia oleifera Abel) and their cytotoxic activity on MCF-7 cells in vitro - Xin-Fu Zhang; Ying-Ying Han; Tai-Mei Di; Li-Ping Gao; Tao Xia (Natural Product Research, 2021)

Involvement of Putrescine, Nitric Oxide, and Hydrogen Peroxide in Methyl Jasmonate-Induced Ginsenoside Synthesis in Adventitious Root Cultures of Panax ginseng C.A. Meyer - Xiao-Han Wu; Ming-Zhi Fan; Xue-Feng Li; Xuan-Chun Piao; Ri Gao; Mei-Lan Lian (Journal of Plant Growth Regulation, 2021)

Variations in aeolian landform patterns in the Gonghe Basin over the last 30 years - Yu-han Qi; Mei-hui Pan; Ze-wen Hao; An-na Yang; Wen-xuan Xue (Journal of Mountain Science, 2021)

Multi-model fusion based on MATLAB to identify the water quality between the wet season and the drought period in Changyi water source area - Xingyue Qu; Jin Han; Mei Qiu; Weifu Gao (Arabian Journal of Geosciences, 2021)

Shrub‐rings used to reconstruct drought history of the central Alxa desert, northwest China - Ai‐Jun Ding; Sheng‐Chun Xiao; Xiao‐Mei Peng; Quan‐Yan Tian; Chao Han (International Journal of Climatology, 2021)
The climate history of the Alxa desert of northwestern China must be sought both in recent instrumental records (dating from 1960) and in high‐resolution proxy data. Climate proxies are scarce in desert areas; however, long‐lived desert shrubs can offer one such proxy. We have used shrub‐ring data from Zygophyllum xanthoxylum , collected in the central Alxa desert, to reconstruct the Self‐calibrating Palmer Drought Severity Index (scPDSI) for the period 1880–2015. The data covers the May–July growth season. When we compared the history constructed from the shrub‐ring data with the instrumental data collected 1960–2015, we found that the reconstructed history explained 41% of the variance in scPDSI data (40% after adjusting for loss of degrees of freedom). The reconstructed history shows that this region has experienced six persistent droughts and four seasons wetter than usual during the period under study. Of note is a severe drought event in 1920s that affected much of northern China (as noted in contemporary documents). The droughts and wet seasons identified in our reconstruction are consistent with reports from other researchers who have studied the climate history or the region. Our study suggests that it is feasible to reconstruct climate history using shrub‐ring data from long‐lived desert shrubs.

Landslide susceptibility mapping using an ensemble model of Bagging scheme and random subspace–based naïve Bayes tree in Zigui County of the Three Gorges Reservoir Area, China - Xudong Hu; Cheng Huang; Hongbo Mei; Han Zhang (Bulletin of Engineering Geology and the Environment, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Overcoming diverse homologous recombinations and single chimeric guide RNA competitive inhibition enhances Cas9‐based cyclical multiple genes coediting in filamentous fungi - Youzhi Miao; Yanwei Xia; Yanqiong Kong; Han Zhu; Huiling Mei; Pan Li; Haichao Feng; Weibing Xun; Zhihui Xu; Nan Zhang; Dongyang Liu; Qirong Shen; et al. (Environmental Microbiology, 2021)
Summary Deciphering the complex cellular behaviours and advancing the biotechnology applications of filamentous fungi increase the requirement for genetically manipulating a large number of target genes. The current strategies cannot cyclically coedit multiple genes simultaneously. In this study, we firstly revealed the existence of diverse homologous recombination (HR) types in marker‐free editing of filamentous fungi, and then, demonstrated that sgRNA efficiency‐mediated competitive inhibition resulted in the low integration of multiple genetic sites during coediting, which are the two major obstacles to limit the efficiency of cyclically coediting of multiple genes. To overcome these obstacles, we developed a biased cutting strategy by Cas9 to greatly enhance the desired HR type and applied a new selection marker labelling strategy for multiple donor DNAs, in which only the donor DNA with the lowest sgRNA efficiency was labelled. Combined with these strategies, we successfully developed a convenient method for cyclically coediting multiple genes in different filamentous fungi. In addition, diverse HRs resulted in a useful and convenient one‐step approach for gene functional study combining both gene disruption and complementation. This research provided both a useful one‐step approach for gene functional study and an efficient strategy for cyclically coediting multiple genes in filamentous fungi.

Puerhibacterium puerhi gen. nov., sp. nov., a novel member of the family Promicromonosporaceae, isolated from Pu-erh tea pile-fermentation - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Lu Han; Wen-Shu Peng; Li Liu; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

Changes in the physiological characteristics of Panax ginseng embryogenic calli and molecular mechanism of ginsenoside biosynthesis under cold stress - Tao Zhang; Yan Gao; Mei Han; Linmin Yang (Planta, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Altered resting-state functional networks in patients with hemodialysis: a graph-theoretical based study - Mei Jin; Liyan Wang; Hao Wang; Xue Han; Zongli Diao; Wang Guo; Zhenghan Yang; Heyu Ding; Zheng Wang; Peng Zhang; Pengfei Zhao; Han Lv; et al. (Brain Imaging and Behavior, 2021)

Early diagnosis of rabies virus infection by RPA-CRISPR techniques in a rat model - Meishen Ren; Hong Mei; Jiaojiao Zhou; Ming Zhou; Heyou Han; Ling Zhao (Archives of Virology, 2021)

Rare taxa maintain the stability of crop mycobiomes and ecosystem functions - Chao Xiong; Ji‐Zheng He; Brajesh K. Singh; Yong‐Guan Zhu; Jun‐Tao Wang; Pei‐Pei Li; Qin‐Bing Zhang; Li‐Li Han; Ju‐Pei Shen; An‐Hui Ge; Chuan‐Fa Wu; Li‐Mei Zhang (Environmental Microbiology, 2021)
Summary Plants harbour highly diverse mycobiomes which sustain essential functions for host health and productivity. However, ecological processes that govern the plant–mycobiome assembly, interactions and their impact on ecosystem functions remain poorly known. Here we characterized the ecological role and community assembly of both abundant and rare fungal taxa along the soil–plant continuums (rhizosphere, phyllosphere and endosphere) in the maize–wheat/barley rotation system under different fertilization practices at two contrasting sites. Our results indicate that mycobiome assembly is shaped predominantly by compartment niche and host species rather than by environmental factors. Moreover, crop‐associated fungal communities are dominated by few abundant taxa mainly belonging to Sordariomycetes and Dothideomycetes, while the majority of diversity within mycobiomes are represented by rare taxa. For plant compartments, the abundant sub‐community is mainly determined by stochastic processes. In contrast, the rare sub‐community is more sensitive to host selection and mainly governed by deterministic processes. Furthermore, our results demonstrate that rare taxa play an important role in fungal co‐occurrence network and ecosystem functioning like crop yield and soil enzyme activities. These results significantly advance our understanding of crop mycobiome assembly and highlight the key role of rare taxa in sustaining the stability of crop mycobiomes and ecosystem functions.

New secondary metabolite with cytotoxicity from spawning soft coral Asterospicularia laurae in Taiwan - Jui-Hsin Su; Chih-I Liu; Mei-Chin Lu; Chi-I Chang; Min-Ying Hsieh; Yu-Chi Lin; Chang-Feng Dai; Ya-Han Zhang; Zheng-Yu Lin; Yun-Sheng Lin (Natural Product Research, 2021)

Clinacanthus nutans Mitigates Neuronal Death and Reduces Ischemic Brain Injury: Role of NF-κB-driven IL-1β Transcription - Mei-Han Kao; Jui-Sheng Wu; Wai-Mui Cheung; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Deron R. Herr; Teng-Nan Lin (NeuroMolecular Medicine, 2021)

The reduction of lipid-sourced energy production caused by ATGL inhibition cannot be compensated by activation of HSL, autophagy, and utilization of other nutrients in fish - Si-Lan Han; Yan Liu; Samwel M. Limbu; Li-Qiao Chen; Mei-Ling Zhang; Zhen-Yu Du (Fish Physiology and Biochemistry, 2021)

Cerebral blood flow alterations in hemodialysis patients with and without restless legs syndrome: an arterial spin labeling study - Hao Wang; Xue Han; Mei Jin; Li-yan Wang; Zong-li Diao; Wang Guo; Peng Zhang; Zheng Wang; Han Lv; He-yu Ding; Zheng-yu Zhang; Peng-fei Zhao; et al. (Brain Imaging and Behavior, 2021)

Diversity and potential biogeochemical impacts of viruses in bulk and rhizosphere soils - Li Bi; Dan‐Ting Yu; Shuai Du; Li‐Mei Zhang; Li‐Yu Zhang; Chuan‐Fa Wu; Chao Xiong; Li‐Li Han; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Viruses can affect microbial dynamics, metabolism and biogeochemical cycles in aquatic ecosystems. However, viral diversity and functions in agricultural soils are poorly known, especially in the rhizosphere. We used virome analysis of eight rhizosphere and bulk soils to study viral diversity and potential biogeochemical impacts in an agro‐ecosystem. The order Caudovirales was the predominant viral type in agricultural soils, with Siphoviridae being the most abundant family. Phylogenetic analysis of the terminase large subunit of Caudovirales identified high viral diversity and three novel groups. Viral community composition differed significantly between bulk and rhizosphere soils. Soil pH was the main environmental driver of the viral community structure. Remarkably, abundant auxiliary carbohydrate‐active enzyme (CAZyme) genes were detected in viromes, including glycoside hydrolases, carbohydrate esterases and carbohydrate‐binding modules. These results demonstrate that virus‐encoded putative auxiliary metabolic genes or metabolic genes that may change bacterial metabolism and indirectly contribute to biogeochemical cycling, especially carbon cycling, in agricultural soil.

Performance evaluation of ensemble learning techniques for landslide susceptibility mapping at the Jinping county, Southwest China - Xudong Hu; Hongbo Mei; Han Zhang; Yuanyuan Li; Mengdi Li (Natural Hazards, 2021)

Elevated atmospheric CO 2 reduces yield‐scaled N 2 O fluxes from subtropical rice systems: Six site‐years field experiments - Zhisheng Yao; Rui Wang; Xunhua Zheng; Baoling Mei; Zaixing Zhou; Baohua Xie; Haibo Dong; Chunyan Liu; Shenghui Han; Zhongjun Xu; Klaus Butterbach‐Bahl; Jianguo Zhu (Global Change Biology, 2021)
Increasing levels of atmospheric CO 2 are expected to enhance crop yields and alter soil greenhouse gas fluxes from rice paddies. While elevated CO 2 ( ) effects on CH 4 emissions from rice paddies have been studied in some detail, little is known how might affect N 2 O fluxes or yield‐scaled emissions. Here, we report on a multi‐site, multi‐year in‐situ FACE (free‐air CO 2 enrichment) study, aiming to determine N 2 O fluxes and crop yields from Chinese subtropical rice systems as affected by . In this study, we tested various N fertilization and residue addition treatments, with rice being grown under either (+200 μmol/mol) or ambient control. Across the six site‐years, rice straw and grain yields under were increased by 9%–40% for treatments fertilized with ≥150 kg N/ha, while seasonal N 2 O emissions were decreased by 23%–73%. Consequently, yield‐scaled N 2 O emissions were significantly lower under . For treatments receiving insufficient fertilization (≤125 kg N/ha), however, no significant effects on N 2 O emissions were observed. The mitigating effect of upon N 2 O emissions is closely associated with plant N uptake and a reduction of soil N availability. Nevertheless, increases in yield‐scaled N 2 O emissions with increasing N surplus suggests that N surplus is a useful indicator for assessing N 2 O emissions from rice paddies. Our findings indicate that with rising atmospheric CO 2 soil N 2 O emissions from rice paddies will decrease, given that the farmers’ N fertilization is usually sufficient for crop growth. The expected decrease in N 2 O emissions was calculated to compensate 24% of the simultaneously observed increase in CH 4 emissions under . This shows that for an agronomic and environmental assessment of effects on rice systems, not only CH 4 emissions, but also N 2 O fluxes and yield‐scaled emissions need to be considered for identifying most climate‐friendly and economically viable options for future rice production.

Calcimicrobes in Cambrian microbialites (Shandong, North China) and comparison with experimentally produced biomineralization precipitates - Yanyang Zhao; Huaxiao Yan; Maurice E. Tucker; Mei Han; Hui Zhao; Guangzhou Mao; Chao Peng; Zuozhen Han (Carbonates and Evaporites, 2020)

Light grazing facilitates carbon accumulation in subsoil in Chinese grasslands: A meta‐analysis - Zhi‐Yun Jiang; Zhong‐Min Hu; Derrick Y. F. Lai; Dao‐Rui Han; Mei Wang; Min Liu; Meng Zhang; Ming‐Yan Guo (Global Change Biology, 2020)
Grazing by livestock greatly affects the soil carbon (C) cycle in grassland ecosystems. However, the effects of grazing at different intensities and durations on the dynamics of soil C in its subsoil layers are not clearly understood. Here, we compiled data from 78 sites (in total 122 published studies) to examine the effects of varying grazing intensities and durations on soil C content at different depths for grasslands in China. Our meta‐analysis revealed that grazing led to an overall decrease in soil C content and productivity of above‐ground vegetation (e.g., above‐ground biomass and litter) but an increase in below‐ground biomass. Specifically, the effects of grazing on soil C content became less negative or even positive with increasing soil depths. An increase of soil C content was consequently found under light grazing (LG), although soil C content still decreased under moderate and heavy grazing. The increase in soil C content under LG could be largely attributed to the increase of soil C content in subsoil layers (>20 cm), despite that soil C content in surface soil layer (0–20 cm) decreased. Moreover, the magnitude of increase in soil C content under LG in subsoil layers increased with grazing duration. A possible reason of the increase in soil C content in the subsoil layers was due to the increases in below‐ground biomass. Our study highlights that LG may modify the allocation of C input and promote its accumulation in subsoil layers, thus offsetting the negative impact of grazing on surface soil C content, a finding that has significant implications for C sequestration in grasslands.

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Creation of fertility-restored materials for Ogura CMS in Brassica oleracea by introducing Rfo gene from Brassica napus via an allotriploid strategy - Hai-long Yu; Zhi-yuan Li; Wen-jing Ren; Feng-qing Han; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Yu-mei Liu; Zhi-yuan Fang; Yang-yong Zhang (Theoretical and Applied Genetics, 2020)
Key message Ogura CMS fertility-restored materials, with 18 chromosomes, normal seed setting, stable fertility and closer genetic background to the parent Chinese kale, were successfully developed in B. oleracea via a triploid strategy for the first time. Abstract Ogura cytoplasmic male sterility (CMS) is the most widely used sterile type in seed production for commercial hybrids of Brassica oleracea vegetables. However, the natural Ogura CMS restorer line has not been found in B. oleracea crops. In this study, the triploid strategy was used with the aim to create euploid B. oleracea progenies with the Rfo gene. The allotriploid AAC hybrid YL2 was used as a male parent to backcross with Ogura CMS Chinese kale. After successive backcrosses, the BC 2 Rfo -positive individual 16CMSF2-11 and its BC 3 progenies, with 18 chromosomes, were developed, which were morphologically identical to the parent Chinese kale. Compared with F 1 and BC 1 plants, it showed stable fertility performance, and regular meiosis behavior and could produce seeds normally under natural pollination. The genomic composition analysis of Rfo -positive progenies by using molecular markers showed that more than 87% of the C-genome components of BC 3 Rfo -progenies recovered to the parent Chinese kale, while most or all of the A n -genome segments were lost in 16CMSF2-11 and its progenies. The results suggested that the genetic background of Rfo -positive individuals was closer to that of the parent Chinese kale along with backcrossing. Hereof, the Ogura CMS fertility-restored materials of Chinese kale were successfully created via triploid strategy for the first time, providing a bridge for utilizing the Ogura CMS B. oleracea germplasm in the future. Moreover, our study indicates that the triploid strategy is effective for transferring genes from B. napus into B. oleracea .

The combinatory effects of natural products and chemotherapy drugs and their mechanisms in breast cancer treatment - Yubo Zhang; Huajun Li; Jing Zhang; Chaoran Zhao; Shuai Lu; Jinping Qiao; Mei Han (Phytochemistry Reviews, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Impaired peroxisomal fat oxidation induces hepatic lipid accumulation and oxidative damage in Nile tilapia - Yan Liu; Si-Lan Han; Yuan Luo; Ling-Yu Li; Li-Qiao Chen; Mei-Ling Zhang; Zhen-Yu Du (Fish Physiology and Biochemistry, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

MiR-27b-3p exerts tumor suppressor effects in esophageal squamous cell carcinoma by targeting Nrf2 - Mei Han; Na Li; Fanzhou Li; Hua Wang; Lanying Ma (Human Cell, 2020)

Long interpregnancy interval and adverse perinatal outcomes: A retrospective cohort study - Jing Lin; Han Liu; Dan-Dan Wu; Hong-Tao Hu; Hui-Hui Wang; Cheng-Liang Zhou; Xin-Mei Liu; Xiao-Jun Chen; Jian-Zhong Sheng; He-Feng Huang (Science China Life Sciences, 2020)

Using demographic model selection to untangle allopatric divergence and diversification mechanisms in the Rheum palmatum complex in the Eastern Asiatic Region - Li Feng; Markus Ruhsam; Yi‐Han Wang; Zhong‐Hu Li; Xu‐Mei Wang (Molecular Ecology, 2020)
Allopatric divergence is often initiated by geological uplift and restriction to sky‐islands, climate oscillations, or river capture. However, it can be difficult to establish which mechanism was the most likely to generate the current phylogeographical structure of a species. Recently, genomic data in conjunction with a model testing framework have been applied to address this issue in animals. To test whether such an approach is also likely to be successful in plants, we used population genomic data of the Rheum palmatum complex from the Eastern Asiatic Region, in conjunction with biogeographical reconstruction and demographic model selection, to identify the potential mechanism(s) which have led to the current level of divergence. Our results indicate that the R. palmatum complex originated in the central Hengduan Mts and possibly in regions further east, and then dispersed westward and eastward resulting in genetically distinct lineages. Populations are likely to have diverged in refugia during climate oscillations followed by subsequent expansion and secondary contact. However, model simulations within the western lineage of the R. palmatum complex cannot reject a restriction to sky‐islands as a possible mechanism of diversification due to the genetically ambiguous position of one population. This highlights that genetically mixed populations might introduce ambiguity regarding the best diversification model in some cases. Although it might be possible to resolve this ambiguity using other data, sometimes this could prove to be difficult in complex biogeographical areas.

Viral metagenomics reveals sapoviruses of different genogroups in stool samples from children with acute gastroenteritis in Jiangsu, China - Wang Li; Surong Dong; Juan Xu; Xiaobin Zhou; Junling Han; Zhaqing Xie; Qin Gong; Hailin Peng; Chenglin Zhou; Mei Lin (Archives of Virology, 2020)
Sapoviruses (SAVs), including several genogroups (GI to GV), are one of the causes of acute gastroenteritis (AGE). In this study, viral metagenomics revealed the presence of sapoviruses of different genogroups in stool from children with AGE. Eight different complete SAV genomes were determined, of which five belonged to GI and the other three belonged to GII, GIV and GV, respectively. Although they were highly similar to published sequences, the GIV and GV were the first complete genome sequences of these SAVs found in China. In a prevalence investigation, 19% of subjects with AGE were positive for SAVs, while none of the control group was positive.

Effects of High Pressure on Myofibrillar Protein and Moisture Distribution of Shrimp ( Solenocera melantho ) Muscle - Mingchun Lv; Han Zhang; Kalin Mei; Wenge Yang; Zhiyan Wang (Journal of Aquatic Food Product Technology, 2020)

Endothelial Notch activation promotes neutrophil transmigration via downregulating endomucin to aggravate hepatic ischemia/reperfusion injury - Peiran Zhang; Kangyi Yue; Xinli Liu; Xianchun Yan; Ziyan Yang; Juanli Duan; Congcong Xia; Xinyuan Xu; Mei Zhang; Liang Liang; Lin Wang; Hua Han (Science China Life Sciences, 2020)

DNA stable isotope probing revealed no incorporation of 13CO2 into comammox Nitrospira but ammonia-oxidizing archaea in a subtropical acid soil - Zi-Yang He; Ju-Pei Shen; Li-Mei Zhang; Hua-Jing Tian; Bing Han; Hong-Jie Di; Ji-Zheng He (Journal of Soils and Sediments, 2020)

Does dietary intake of selenium protect against cancer? A systematic review and meta-analysis of population-based prospective studies - Angelica Kuria; Xin Fang; Mei Li; Hedong Han; Jia He; Jan Olav Aaseth; Yang Cao (Critical Reviews in Food Science and Nutrition, 2020)

Microbial methane production is affected by secondary metabolites in the heartwood of living trees in upland forests - Huan-Long Li; Xi-Mei Zhang; Feng-Dan Deng; Xing-Guo Han; Chun-Wang Xiao; Shi-Jie Han; Zhi-Ping Wang (Trees, 2020)

Plasma biomarkers and plaque strain predict long-term cardiovascular events in patients with acute coronary syndrome - Mingjun Xu; Xiaobo Hu; Lin Wang; Wei Zhang; Lindi Wu; Jifu Li; Yuguo Chen; Pengfei Zhang; Haijun Su; Yaling Han; Cheng Zhang; Mei Zhang; et al. (Science China Life Sciences, 2020)

Inhibition of intestinal lipases alleviates the adverse effects caused by high-fat diet in Nile tilapia - Yu-Xue Zhang; Zhe-Yue Jiang; Si-Lan Han; Ling-Yu Li; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Fish Physiology and Biochemistry, 2020)

Effects of long-term exposure to air pollution on the incidence of type 2 diabetes mellitus: a meta-analysis of cohort studies - Mei Yang; Han Cheng; Chaowei Shen; Jie Liu; Hongkai Zhang; Jiyu Cao; Rui Ding (Environmental Science and Pollution Research, 2020)

Se Regulates the Contractile Ability of Uterine Smooth Musclevia Selenoprotein N, Selenoprotein T, and Selenoprotein Win Mice - Fu-han Wang; Xiao Peng; Yu Chen; Ying Wang; Mei Yang; Meng-yao Guo (Biological Trace Element Research, 2019)

De novo assembly and transcriptome analysis of differentially expressed genes relevant to variegation in hawthorn flowers - Wei Ji; Wei Zhao; Rong-Chen Liu; Xiao-Bo Jiao; Kai Han; Zhong-Yi Yang; Mei-Ying Gao; Rui Ren; Xiu-Juan Fan; Ming-Xia Yang (Plant Biotechnology Reports, 2019)

Associations of ambient PM2.5 and O3 with cardiovascular mortality: a time-series study in Hefei, China - Han Cheng; Furong Zhu; Ruoqian Lei; Chaowei Shen; Jie Liu; Mei Yang; Rui Ding; Jiyu Cao (International Journal of Biometeorology, 2019)

Innovative sludge pretreatment technology for impurity separation using micromesh - Xiaojie Mei; Xiaomeng Han; Lili Zang; Zhichao Wu (Environmental Science and Pollution Research, 2019)

A preliminary study on diet of the Yangtze finless porpoise using next‐generation sequencing techniques - Jiwei Yang; Xiaoling Wan; Xianyuan Zeng; Jinsong Zheng; Yi Han; Fei Fan; Yujiang Hao; Kexiong Wang; Zhigang Mei; Ding Wang (Marine Mammal Science, 2019)

Effects of drought–re-watering–drought on the photosynthesis physiology and secondary metabolite production of Bupleurum chinense DC. - Linlin Yang; Yu Zhao; Qi Zhang; Lin Cheng; Mei Han; Yueying Ren; Limin Yang (Plant Cell Reports, 2019)

Usage patterns and comfort of gardens: a seasonal survey of internal garden microclimate in the aged care homes of Chengdu City - Hua Zong; Yin Liu; Qian Wang; Mei-lin Liu; Han Chen (International Journal of Biometeorology, 2019)

Measurement of urinary arsenic profiles and DNA hypomethylation in a case–control study of urothelial carcinoma - Chi-Jung Chung; Hui-Ling Lee; Chao-Hsiang Chang; Han Chang; Chiu-Shong Liu; Wei-Ting Jung; Huei-Ju Liu; Saou-Hsing Liou; Mu-Chi Chung; Yu-Mei Hsueh (Archives of Toxicology, 2019)

Biodiversity and antifouling activity of fungi associated with two soft corals from the South China Sea - Xiao-Yong Zhang; Hui-Li Hao; Stanley Chun Kwan Lau; Huai-You Wang; Yu Han; Li-Mei Dong; Ri-Ming Huang (Archives of Microbiology, 2019)

Research on the required width of a fault waterproof coal pillar based on underground pressure control theory - Longqing Shi; Ying Wang; Mei Qiu; Lu Han; Yunping Zhao (Arabian Journal of Geosciences, 2019)

Seldom-segment versus multi-segment intramedullary spinal cord gliomas: a comparative clinical study - Jianjun Sun; Zhenyu Wang; Zhendong Li; Haibo Wu; Mei Zheng; Qing Chang; Yunfeng Han; Zhihui Cui; Hung I. Liao; Tao Wang; Xiaodong Chen; Xuan Yang; et al. (Science China Life Sciences, 2019)

Early-Middle Ordovician intermediate-mafic and ultramafic rocks in central Jilin Province, NE China: geochronology, origin, and tectonic implications - Zhigang Song; Chao Han; Hui Liu; Zuozhen Han; Junlei Yan; Wenjian Zhong; Lihua Gao; Qingxiang Du; Mei Han; Jingjing Li (Mineralogy and Petrology, 2019)

Real-time evacuation and failure mechanism of a giant soil landslide on 19 July 2018 in Yanyuan County, Sichuan Province, China - Guisheng Hu; Mei Liu; Ningsheng Chen; Xiaopeng Zhang; Kanglin Wu; Binish Raj Khanal; D. Han (Landslides, 2019)

Adsorption and Desorption of Carbendazim and Thiamethoxam in Five Different Agricultural Soils - Lingxi Han; Qiqing Ge; Jiajia Mei; Yanli Cui; Yongfei Xue; Yunlong Yu; Hua Fang (Bulletin of Environmental Contamination and Toxicology, 2019)

Ambient air pollution and the risk of stillbirth: a population-based prospective birth cohort study in the coastal area of China - Hongyan Zang; Han Cheng; Wenya Song; Mei Yang; Ping Han; Chunxiao Chen; Rui Ding (Environmental Science and Pollution Research, 2019)

Simultaneous prediction of rock matrix modulus and critical porosity - Nuo Li; Hao Chen; Xiu-Mei Zhang; Jian-Qiang Han; Jian Wang; Xiu-Ming Wang (Applied Geophysics, 2019)

LncRNA ZBTB40-IT1 modulated by osteoporosis GWAS risk SNPs suppresses osteogenesis - Bing Mei; Ya Wang; Weiyuan Ye; Han Huang; Qian Zhou; Yuanyuan Chen; Yajing Niu; Manling Zhang; Qingyang Huang (Human Genetics, 2019)

Viral metagenomics analysis and eight novel viral genomes identified from the Dushanzi mud volcanic soil in Xinjiang, China - Dan-Ting Yu; Ji-Zheng He; Li-Mei Zhang; Li-Li Han (Journal of Soils and Sediments, 2019)

Identification of QTL regions for seedling root traits and their effect on nitrogen use efficiency in wheat (Triticum aestivum L.) - Xiaoli Fan; Wei Zhang; Na Zhang; Mei Chen; Shusong Zheng; Chunhua Zhao; Jie Han; Jiajia Liu; Xilan Zhang; Liqiang Song; Jun Ji; Xigang Liu; et al. (Theoretical and Applied Genetics, 2018)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Low root/shoot (R/S) biomass ratio can be an indicator of low cadmium accumulation in the shoot of Chinese flowering cabbage (Brassica campestris L. ssp. chinensis var. utilis Tsen et Lee) cultivars - Zhi-Min Xu; Xiu-Qin Mei; Ling Tan; Qu-Sheng Li; Li-Li Wang; Bao-Yan He; Shi-Hong Guo; Chu Zhou; Han-Jie Ye (Environmental Science and Pollution Research, 2018)

Lycium barbarum polysaccharide attenuates diabetic testicular dysfunction via inhibition of the PI3K/Akt pathway-mediated abnormal autophagy in male mice - Guang-Jiang Shi; Jie Zheng; Xiao-Xu Han; Ya-Ping Jiang; Zhi-Mei Li; Jing Wu; Qing Chang; Yang Niu; Tao Sun; Yu-Xiang Li; Zhen Chen; Jian-Qiang Yu (Cell and Tissue Research, 2018)

Low-Cd tomato cultivars (Solanum lycopersicum L.) screened in non-saline soils also accumulated low Cd, Zn, and Cu in heavy metal-polluted saline soils - Zhi-Min Xu; Xiao-Qi Tan; Xiu-Qin Mei; Qu-Sheng Li; Chu Zhou; Li-Li Wang; Han-Jie Ye; Ping Yang (Environmental Science and Pollution Research, 2018)

Confounding influence of tamoxifen in mouse models of Cre recombinase-induced gene activity or modulation - Seddik Hammad; Amnah Othman; Christoph Meyer; Ahmad Telfah; Joerg Lambert; Bedair Dewidar; Julia Werle; Zeribe Chike Nwosu; Abdo Mahli; Christof Dormann; Yan Gao; Kerry Gould; et al. (Archives of Toxicology, 2018)

Combination of NAD+ and NADPH Offers Greater Neuroprotection in Ischemic Stroke Models by Relieving Metabolic Stress - Qiao Huang; Meiling Sun; Mei Li; Dingmei Zhang; Feng Han; Jun Chao Wu; Kohji Fukunaga; Zhong Chen; Zheng-Hong Qin (Molecular Neurobiology, 2018)

Clinacanthus nutans Mitigates Neuronal Apoptosis and Ischemic Brain Damage Through Augmenting the C/EBPβ-Driven PPAR-γ Transcription - Jui-Sheng Wu; Mei-Han Kao; Hsin-Da Tsai; Wai-Mui Cheung; Jin-Jer Chen; Wei-Yi Ong; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Alteration of SlYABBY2b gene expression impairs tomato ovary locule number and endogenous gibberellin content - Hui Li; Mei-hua Sun; Ming-fang Qi; Jiao Xing; Tao Xu; Han-ting Liu; Tian-lai Li (Journal of Zhejiang University-SCIENCE B, 2018)

A comparison of amorphous calcium carbonate crystallization in aqueous solutions of MgCl2 and MgSO4: implications for paleo-ocean chemistry - Mei Han; Yanyang Zhao; Hui Zhao; Zuozhen Han; Huaxiao Yan; Bin Sun; Ruirui Meng; Dingxiang Zhuang; Dan Li; Binwei Liu (Mineralogy and Petrology, 2018)

Investigation of Trace Element Content in the Seeds, Pulp, and Peel of Mashui Oranges Using Microwave Digestion and ICP-MS Analysis - Lingyun Chen; Mei Shen; Ande Ma; Weili Han (Biological Trace Element Research, 2018)

Zircon U–Pb geochronology and geochemistry of the post-collisional volcanic rocks in eastern Xinjiang Province, NW China: implications for the tectonic evolution of the Junggar terrane - Qingxiang Du; Zuozhen Han; Xiaoli Shen; Chao Han; Mei Han; Zhigang Song; Lihua Gao; Hui Liu; Wenjian Zhong; Junlei Yan (International Geology Review, 2018)

Synthesis and antitumour activity of arctigenin amino acid ester derivatives against H22 hepatocellular carcinoma - Enbo Cai; Shijie Guo; Limin Yang; Mei Han; Jing Xia; Yan Zhao; Xiaorui Gao; Yu Wang (Natural Product Research, 2018)

Human placenta-derived mesenchymal stem cells loaded on linear ordered collagen scaffold improves functional recovery after completely transected spinal cord injury in canine - Sufang Han; Zhifeng Xiao; Xing Li; Huan Zhao; Bin Wang; Zhixue Qiu; Zhi Li; Xin Mei; Bai Xu; Caixia Fan; Bing Chen; Jin Han; et al. (Science China Life Sciences, 2018)

C21 steroid derivatives from the Dai herbal medicine Dai-Bai-Jie, the dried roots of Marsdenia tenacissima, and their screening for anti-HIV activity - Xu Pang; Li-Ping Kang; Xiao-Mei Fang; He-Shui Yu; Li-Feng Han; Yang Zhao; Li-Xia Zhang; Li-Yan Yu; Bai-Ping Ma (Journal of Natural Medicines, 2018)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)

Kinsenoside and polysaccharide production by rhizome culture of Anoectochilus roxburghii in continuous immersion bioreactor systems - Mei-Yu Jin; Lu Han; He Li; Hong-Qiu Wang; Xuan-Chun Piao; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Involvement of IL-17 in Secondary Brain Injury After a Traumatic Brain Injury in Rats - Tan Li; Yong-mei Zhang; Dong Han; Rong Hua; Bing-nan Guo; Shu-qun Hu; Xian-liang Yan; Tie Xu (NeuroMolecular Medicine, 2017)

Effects of glucose and gibberellic acid on glucosinolate content and antioxidant properties of Chinese kale sprouts - Hui-ying Miao; Meng-yu Wang; Jia-qi Chang; Han Tao; Bo Sun; Qiao-mei Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Down-regulation of Noggin and miR-138 coordinately promote osteogenesis of mesenchymal stem cells - Xing-Kun Sun; Jin Zhou; Lei Zhang; Tian Ma; Yu-Han Wang; Yan-Mei Yang; Yan-Ting Tang; Hong Li; Li-Jun Wang (Journal of Molecular Histology, 2017)

Calcium carbonate precipitation by Synechocystis sp. PCC6803 at different Mg/Ca molar ratios under the laboratory condition - Zuozhen Han; Ruirui Meng; Huaxiao Yan; Hui Zhao; Mei Han; Yanyang Zhao; Bin Sun; Yanbiao Sun; Jie Wang; Dingxiang Zhuang; Wenjun Li; Lingxue Lu (Carbonates and Evaporites, 2017)

20(S)-25-methoxyl-dammarane-3β, 12β, 20-triol negatively regulates activation of STAT3 and ERK pathways and exhibits anti-cancer effects in HepG2 cells - Hui-Han Ai; Zi-Long Zhou; Lu-Guo Sun; Mei-Ting Yang; Wei Li; Chun-Lei Yu; Zhen-Bo Song; Yan-Xin Huang; Yin Wu; Lei Liu; Xiao-Guang Yang; Yu-Qing Zhao; et al. (Apoptosis, 2017)

Comparative and population genomic landscape of Phellinus noxius : A hypervariable fungus causing root rot in trees - Chia‐Lin Chung; Tracy J. Lee; Mitsuteru Akiba; Hsin‐Han Lee; Tzu‐Hao Kuo; Dang Liu; Huei‐Mien Ke; Toshiro Yokoi; Marylette B. Roa; Mei‐Yeh J. Lu; Ya‐Yun Chang; Pao‐Jen Ann; et al. (Molecular Ecology, 2017)
The order Hymenochaetales of white rot fungi contain some of the most aggressive wood decayers causing tree deaths around the world. Despite their ecological importance and the impact of diseases they cause, little is known about the evolution and transmission patterns of these pathogens. Here, we sequenced and undertook comparative genomic analyses of Hymenochaetales genomes using brown root rot fungus Phellinus noxius , wood‐decomposing fungus Phellinus lamaensis, laminated root rot fungus Phellinus sulphurascens and trunk pathogen Porodaedalea pini . Many gene families of lignin‐degrading enzymes were identified from these fungi, reflecting their ability as white rot fungi. Comparing against distant fungi highlighted the expansion of 1,3‐beta‐glucan synthases in P. noxius , which may account for its fast‐growing attribute. We identified 13 linkage groups conserved within Agaricomycetes, suggesting the evolution of stable karyotypes. We determined that P. noxius has a bipolar heterothallic mating system, with unusual highly expanded ~60 kb A locus as a result of accumulating gene transposition. We investigated the population genomics of 60 P. noxius isolates across multiple islands of the Asia Pacific region. Whole‐genome sequencing showed this multinucleate species contains abundant poly‐allelic single nucleotide polymorphisms with atypical allele frequencies. Different patterns of intra‐isolate polymorphism reflect mono‐/heterokaryotic states which are both prevalent in nature. We have shown two genetically separated lineages with one spanning across many islands despite the geographical barriers. Both populations possess extraordinary genetic diversity and show contrasting evolutionary scenarios. These results provide a framework to further investigate the genetic basis underlying the fitness and virulence of white rot fungi.

Interannual variability of PDSI from tree-ring widths for the past 278 years in Baotou, China - XinJia Zhang; Yu Liu; Huiming Song; Qiufang Cai; Qiang Li; Boyang Zhao; Han Liu; Ruochen Mei (Trees, 2017)

Attenuation of ethanol abstinence-induced anxiety- and depressive-like behavior by the phosphodiesterase-4 inhibitor rolipram in rodents - Mei-Fang Gong; Rui-Ting Wen; Ying Xu; Jian-Chun Pan; Ning Fei; Yan-Meng Zhou; Jiang-Ping Xu; Jian-Hui Liang; Han-Ting Zhang (Psychopharmacology, 2017)

Protective effects of paeonol on inflammatory response in IL-1β-induced human fibroblast-like synoviocytes and rheumatoid arthritis progression via modulating NF-κB pathway - Ke-feng Zhai; Hong Duan; Lin Luo; Wen-gen Cao; Fang-kai Han; Ling-ling Shan; Xue-mei Fang (Inflammopharmacology, 2017)

Comparative study of the leaf transcriptomes and ionoms of Juglans regia and its wild relative species Juglans cathayensis - Zhongcheng Zhou; Muxian Han; Mei Hou; Xiaojing Deng; Rui Tian; Shuifa Min; Jinbo Zhang (Acta Physiologiae Plantarum, 2017)

Preservation of Anticancer and Immunosuppressive Properties of Rapamycin Achieved Through Controlled Releasing Particles - Yan Liang Fan; Han Wei Hou; Hui Min Tay; Wei Mei Guo; Per-Olof Berggren; Say Chye Joachim Loo (AAPS PharmSciTech, 2017)

Prostanoid EP3 receptor agonist sulprostone enhances pacemaker activity of colonic interstitial cells of Cajal - Man Woo Kim; Han Yi Jiao; Seok Won Kim; Chan Guk Park; Mei Jin Wu; Chansik Hong; Seok Choi; Jae Yeoul Jun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Responses of soil nitrous oxide production and abundances and composition of associated microbial communities to nitrogen and water amendment - Qing Wang; Yu-Rong Liu; Cui-Jing Zhang; Li-Mei Zhang; Li-Li Han; Ju-Pei Shen; Ji-Zheng He (Biology and Fertility of Soils, 2017)

Characterization of the temporal and spatial expression of wheat (Triticum aestivum L.) plant height at the QTL level and their influence on yield-related traits - Na Zhang; Xiaoli Fan; Fa Cui; Chunhua Zhao; Wei Zhang; Xueqiang Zhao; Lijuan Yang; Ruiqing Pan; Mei Chen; Jie Han; Jun Ji; Dongcheng Liu; et al. (Theoretical and Applied Genetics, 2017)

Genistein inhibited ammonia induced astrocyte swelling by inhibiting NF-κB activation-mediated nitric oxide formation - Hongliang Dai; Guizhi Jia; Wei Wang; Chunguang Liang; Siyu Han; Minghui Chu; Xifan Mei (Metabolic Brain Disease, 2017)

Effects of the nitrification inhibitor dicyandiamide (DCD) on N2Oemissions and the abundance of nitrifiers and denitrifiers in two contrasting agricultural soils - Qing Wang; Hang-Wei Hu; Ju-Pei Shen; Shuai Du; Li-Mei Zhang; Ji-Zheng He; Li-Li Han (Journal of Soils and Sediments, 2017)

AKTs/PKBs: molecular characterization, tissue expression and transcriptional responses to insulin and/or wortmannin in yellow catfish Pelteobagrus fulvidraco - Mei-Qin Zhuo; Ya-Xiong Pan; Kun Wu; Yi-Huan Xu; Li-Han Zhang; Zhi Luo (Fish Physiology and Biochemistry, 2017)

Prediction Reliability of Water Inrush Through the Coal Mine Floor - Mei Qiu; Jin Han; Yan Zhou; Longqing Shi (Mine Water and the Environment, 2017)

A Volumetric and Functional Connectivity MRI Study of Brain Arginine-Vasopressin Pathways in Autistic Children - Xiao-Jing Shou; Xin-Jie Xu; Xiang-Zhu Zeng; Ying Liu; Hui-Shu Yuan; Yan Xing; Mei-Xiang Jia; Qing-Yun Wei; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2017)

IRS1 and IRS2: molecular characterization, tissue expression and transcriptional regulation by insulin in yellow catfish Pelteobagrus fulvidraco - Mei-Qin Zhuo; Ya-Xiong Pan; Kun Wu; Yi-Huan Xu; Li-Han Zhang; Zhi Luo (Fish Physiology and Biochemistry, 2017)

Cryopreservation of Jerusalem artichoke cultivars using an improved droplet-vitrification method - Jin-Mei Zhang; Li Han; Xin-Xiong Lu; Gayle M. Volk; Xia Xin; Guang-Kun Yin; Juan-Juan He; Ling Wang; Xiao-Ling Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Unique community structure of viruses in a glacier soil of the Tianshan Mountains, China - Li-Li Han; Dan-Ting Yu; Li-Mei Zhang; Jun-Tao Wang; Ji-Zheng He (Journal of Soils and Sediments, 2017)

Geochemistry and geochronology of Upper Permian–Upper Triassic volcanic rocks in eastern Jilin Province, NE China: implications for the tectonic evolution of the Palaeo-Asian Ocean - Qingxiang Du; Zuozhen Han; Xiaoli Shen; Lihua Gao; Mei Han; Zhigang Song; Jingjing Li; Wenjian Zhong; Junlei Yan; Hui Liu (International Geology Review, 2017)

Temporal dynamics of fungal communities in soybean rhizosphere - Li-Li Han; Jun-Tao Wang; Sheng-Hui Yang; Wen-Feng Chen; Li-Mei Zhang; Ji-Zheng He (Journal of Soils and Sediments, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

Tree-ring-width-based PDSI reconstruction for central Inner Mongolia, China over the past 333 years - Yu Liu; Xinjia Zhang; Huiming Song; Qiufang Cai; Qiang Li; Boyang Zhao; Han Liu; Ruochen Mei (Climate Dynamics, 2017)

Upregulating the Expression of Survivin-HBXIP Complex Contributes to the Protective Role of IMM-H004 in Transient Global Cerebral Ischemia/Reperfusion - Shi-Feng Chu; Zhao Zhang; Wei Zhang; Mei-Jin Zhang; Yan Gao; Ning Han; Wei Zuo; Hui-Yong Huang; Nai-Hong Chen (Molecular Neurobiology, 2017)

Geochemistry of fine-grained clastic rocks in the Mesoproterozoic Kawabulake Group: implications for provenance and the tectonic model of the Eastern Tianshan, Xinjiang, NW China - Deng-Feng Li; Hua-Yong Chen; Li Zhang; Philip Fralick; Pete Hollings; Mei Mi; Wan-Jian Lu; Jin-Sheng Han; Cheng-Ming Wang; Jing Fang (International Journal of Earth Sciences, 2017)

Effects of dicyandiamide and acetylene on N2O emissions and ammonia oxidizers in a fluvo-aquic soil applied with urea - Qing Wang; Li-Mei Zhang; Ju-Pei Shen; Shuai Du; Li-Li Han; Ji-Zheng He (Environmental Science and Pollution Research, 2016)

Nitrogen fertiliser-induced changes in N2O emissions are attributed more to ammonia-oxidising bacteria rather than archaea as revealed using 1-octyne and acetylene inhibitors in two arable soils - Qing Wang; Li-Mei Zhang; Ju-Pei Shen; Shuai Du; Li-Li Han; Ji-Zheng He (Biology and Fertility of Soils, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

A strategy for introducing an endangered plant Mosla hangchowensis to urban area based on nitrogen preference - Mei-Ying Fan; Kai-Xuan Pan; Wen-Juan Han; Yi-Jun Lu; Qi Shen; Meng Wang; Yuan Ren; Ze-Long Qu; Jie Chang; Ying Ge (Acta Physiologiae Plantarum, 2016)

Comparison of R-ketamine and rapastinel antidepressant effects in the social defeat stress model of depression - Bangkun Yang; Ji-chun Zhang; Mei Han; Wei Yao; Chun Yang; Qian Ren; Min Ma; Qian-Xue Chen; Kenji Hashimoto (Psychopharmacology, 2016)

Plasma Oxytocin and Arginine-Vasopressin Levels in Children with Autism Spectrum Disorder in China: Associations with Symptoms - Hong-Feng Zhang; Yu-Chuan Dai; Jing Wu; Mei-Xiang Jia; Ji-Shui Zhang; Xiao-Jing Shou; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2016)

Proteomic Analyses for the Global S-Nitrosylated Proteins in the Brain Tissues of Different Human Prion Diseases - Li-Na Chen; Qi Shi; Bao-Yun Zhang; Xiao-Mei Zhang; Jing Wang; Kang Xiao; Yan Lv; Jing Sun; Xiao-Dong Yang; Cao Chen; Wei Zhou; Jun Han; et al. (Molecular Neurobiology, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Clinacanthus nutans Protects Cortical Neurons Against Hypoxia-Induced Toxicity by Downregulating HDAC1/6 - Hsin-Da Tsai; Jui-Sheng Wu; Mei-Han Kao; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

Discovery of the New Plant Growth-Regulating Compound LYXLF2 Based on Manipulating the Halogenase in Amycolatopsis orientalis - Li Xu; Ting Han; Mei Ge; Li Zhu; XiuPing Qian (Current Microbiology, 2016)

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea - Hai-long Yu; Zhi-yuan Fang; Yu-mei Liu; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Yang-yong Zhang (Theoretical and Applied Genetics, 2016)

[Gly14]-Humanin Protects Against Amyloid β Peptide-Induced Impairment of Spatial Learning and Memory in Rats - Li Yuan; Xiao-Jie Liu; Wei-Na Han; Qing-Shan Li; Zhao-Jun Wang; Mei-Na Wu; Wei Yang; Jin-Shun Qi (Neuroscience Bulletin, 2016)

Potential subchronic food safety of the stacked trait transgenic maize GH5112E-117C in Sprague-Dawley rats - Shiwen Han; Shiying Zou; Xiaoyun He; Kunlun Huang; Xiaohong Mei (Transgenic Research, 2016)

Autoimmunity and dysmetabolism of human acquired immunodeficiency syndrome - Yan-Mei Huang; Xue-Zhi Hong; Jia-Hua Xu; Jiang-Xi Luo; Han-You Mo; Hai-Lu Zhao (Immunologic Research, 2016)

Non-alkaloids extract from Stemona sessilifolia enhances the activity of chemotherapeutic agents through P-glycoprotein-mediated multidrug-resistant cancer cells - Lu Han; Yang-Mei Ma; Li An; Qiao Zhang; Chang-Li Wang; Qing-Chun Zhao (Natural Product Research, 2016)

Thrombomodulin and High-Sensitive C-Reactive Protein Levels in Blood Correlate with the Development of Cerebral Infarction Among Asians - Yan Han; Shuai Wu; Qiang Hu; Jian-Qi Xiao; Dong-Mei Wei; Li-Li Liu; Ze-Zhi Li (Molecular Neurobiology, 2016)

Dexmedetomidine Dose-Dependently Attenuates Ropivacaine-Induced Seizures and Negative Emotions Via Inhibiting Phosphorylation of Amygdala Extracellular Signal-Regulated Kinase in Mice - Ming-Zhu Zhai; Huang-Hui Wu; Jun-Bin Yin; Yuan-Yuan Cui; Xiao-Peng Mei; Han Zhang; Xia Zhu; Xue-Feng Shen; Alan David Kaye; Guo-Zhong Chen (Molecular Neurobiology, 2016)

Calpain-Dependent ErbB4 Cleavage Is Involved in Brain Ischemia-Induced Neuronal Death - Ying-mei Lu; Yin-ping Gao; Rong-rong Tao; Mei-hua Liao; Ji-yun Huang; Gang Wu; Feng Han; Xiao-ming Li (Molecular Neurobiology, 2016)

Molecular identification of ‘Candidatus phytoplasma asteris’ related strain (16SrΙ-B) associated with Broussonetia papyrifera in Nanjing, China - Cong-Jin Mei; Qing-Can Wang; Ju-Can Gui; Yan-Ling Ji; Han-Shou Yu (European Journal of Plant Pathology, 2016)

Effects of 4-methylbenzylidene camphor (4-MBC) on neuronal and muscular development in zebrafish (Danio rerio) embryos - Vincent Wai Tsun Li; Mei Po Mirabelle Tsui; Xueping Chen; Michelle Nga Yu Hui; Ling Jin; Raymond H. W. Lam; Richard Man Kit Yu; Margaret B. Murphy; Jinping Cheng; Paul Kwan Sing Lam; Shuk Han Cheng (Environmental Science and Pollution Research, 2016)

Reproductive responses of male Brandt’s voles (Lasiopodomys brandtii) to 6-methoxybenzoxazolinone (6-MBOA) under short photoperiod - Xin Dai; Lian Yu Jiang; Mei Han; Man Hong Ye; Ai Qin Wang; Wan Hong Wei; Sheng Mei Yang (The Science of Nature, 2016)

Upregulation of Dickkopf1 by oscillatory shear stress accelerates atherogenesis - Mengmeng Li; Xinxin Liu; Yu Zhang; Mingxue Di; Han Wang; Lin Wang; Yifei Chen; Xiaoling Liu; Xiaoqing Cao; Renya Zeng; Yun Zhang; Mei Zhang (Journal of Molecular Medicine, 2016)

QTL detection for wheat kernel size and quality and the responses of these traits to low nitrogen stress - Fa Cui; Xiaoli Fan; Mei Chen; Na Zhang; Chunhua Zhao; Wei Zhang; Jie Han; Jun Ji; Xueqiang Zhao; Lijuan Yang; Zongwu Zhao; Yiping Tong; et al. (Theoretical and Applied Genetics, 2016)

Valproic Acid Influences MTNR1A Intracellular Trafficking and Signaling in a β-Arrestin 2-Dependent Manner - Ling-juan Hong; Quan Jiang; Sen Long; Huan Wang; Ling-di Zhang; Yun Tian; Cheng-kun Wang; Jing-jing Cao; Rong-rong Tao; Ji-yun Huang; Mei-hua Liao; Ying-mei Lu; et al. (Molecular Neurobiology, 2016)

A combination of chitosan and chemical fertilizers improves growth and disease resistance in Begonia × hiemalis Fotsch - Yang-Er Chen; Shu Yuan; Han-Mei Liu; Zhi-Yu Chen; Ying-Hong Zhang; Huai-Yu Zhang (Horticulture, Environment, and Biotechnology, 2016)

Reassessment of an Arabidopsis cell wall invertase inhibitor AtCIF1 reveals its role in seed germination and early seedling growth - Tao Su; Sebastian Wolf; Mei Han; Hongbo Zhao; Hongbin Wei; Steffen Greiner; Thomas Rausch (Plant Molecular Biology, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Dissimilarity of phytoplankton assemblages in two connected tropical reservoirs: effects of water transportation and environmental filtering - Li-Juan Xiao; Ren Hu; Liang Peng; La-Mei Lei; Yu Feng; Bo-Ping Han (Hydrobiologia, 2016)

Comparison of ketamine, 7,8-dihydroxyflavone, and ANA-12 antidepressant effects in the social defeat stress model of depression - Ji-chun Zhang; Wei Yao; Chao Dong; Chun Yang; Qian Ren; Min Ma; Mei Han; Kenji Hashimoto (Psychopharmacology, 2015)

Heavy metal accumulation in soils, plants, and hair samples: an assessment of heavy metal exposure risks from the consumption of vegetables grown on soils previously irrigated with wastewater - Lamin Daddy Massaquoi; Hui Ma; Xue Hui Liu; Peng Yu Han; Shu-Mei Zuo; Zhong-Xian Hua; Dian-Wu Liu (Environmental Science and Pollution Research, 2015)

Cambrian oncoids and other microbial-related grains on the North China Platform - Zuozhen Han; Xiaolei Zhang; Naijie Chi; Mei Han; Jusun Woo; Hyun Suk Lee; Jitao Chen (Carbonates and Evaporites, 2015)

Enteractinococcus lamae sp. nov. and Enteractinococcus viverrae sp. nov., isolated from animal faeces - Xiu Chen; Gui-Ding Li; Qin-Yuan Li; Cai-Juan Hu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang; Li Han; Xue-Shi Huang (Antonie van Leeuwenhoek, 2015)

Detection and identification of ‘Candidatus Phytoplasma ziziphi’ associated with violet orychophragmus yellow dwarf disease in China - Qing-Can Wang; Cong-Jin Mei; Ju-Can Gui; Yan-Ling Ji; Han-Shou Yu (Journal of General Plant Pathology, 2015)

Endogenous level of TIGAR in brain is associated with vulnerability of neurons to ischemic injury - Lijuan Cao; Jieyu Chen; Mei Li; Yuan-Yuan Qin; Meiling Sun; Rui Sheng; Feng Han; Guanghui Wang; Zheng-Hong Qin (Neuroscience Bulletin, 2015)

Up-regulation of SPOCK1 induces epithelial–mesenchymal transition and promotes migration and invasion in esophageal squamous cell carcinoma - Xiaopeng Song; Ping Han; Jingmei Liu; Yunwu Wang; Dongxiao Li; Jiayi He; Jin Gong; Mengke Li; Wei Tu; Wei Yan; Mei Liu; Huanjun Huang; et al. (Journal of Molecular Histology, 2015)

Generation of mutant threonine dehydratase and its effects on isoleucine synthesis in Corynebacterium glutamicum - Yanfeng Guo; Jianzhong Xu; Mei Han; Weiguo Zhang (World Journal of Microbiology and Biotechnology, 2015)

Longitudinal changes of dopamine transporters in heroin users during abstinence - Shasha Xu; Ying Liu; Yu Li; Yangping Deng; Yiyun Huang; Jie Yuan; Rongbin Lv; Yuankai Wang; Guangming Zhang; Zhirui Guo; Mei Han; Xingdang Liu; et al. (Psychopharmacology, 2015)

Genome-wide identification and characterization of cystatin family genes in rice (Oryza sativa L.) - Wei Wang; Peng Zhao; Xue-mei Zhou; Han-xian Xiong; Meng-xiang Sun (Plant Cell Reports, 2015)

Paenibacillus populi sp. nov., a novel bacterium isolated from the rhizosphere of Populus alba - Tong-Yan Han; Xiao-Mei Tong; Yan-Wei Wang; Hui-Min Wang; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

Halosimplex litoreum sp. nov., isolated from a marine solar saltern - Pan-Pan Yuan; Jia-Qi Xu; Wen-Mei Xu; Zhao Wang; Shuai Yin; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Antonie van Leeuwenhoek, 2015)

He-Ne laser preillumination improves the resistance of tall fescue (Festuca arundinacea Schreb.) seedlings to high saline conditions - Li-Mei Gao; Yong-Feng Li; Rong Han (Protoplasma, 2015)

Distribution of Yeast Isolates from Invasive Infections and Their In Vitro Susceptibility to Antifungal Agents: Evidence from 299 Cases in a 3-Year (2010 to 2012) Surveillance Study - Wei Li; Yu-an Hu; Fang-qiu Li; Li-ning Shi; Hai-feng Shao; Mei Huang; Ying Wang; Dan-dan Han; Hong Liao; Chun-fang Ma; Guo-yong Zhang (Mycopathologia, 2015)

GRP75 Involves in Retinal Ganglion Cell Apoptosis After Rat Optic Nerve Crush - Gaoming Zhang; Mei Han; Xiaodong Wang; Aiping Xiao (Journal of Molecular Neuroscience, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

Rhizobium capsici sp. nov., isolated from root tumor of a green bell pepper (Capsicum annuum var. grossum) plant - Shih-Yao Lin; Mei-Hua Hung; Asif Hameed; You-Cheng Liu; Yi-Han Hsu; Cheng-Zhe Wen; A. B. Arun; Hans-Jürgen Busse; Stefanie P. Glaeser; Peter Kämpfer; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

N-3 polyunsaturated fatty acids intake and risk of colorectal cancer: meta-analysis of prospective studies - Guo-Chong Chen; Li-Qiang Qin; Da-Bing Lu; Tie-Mei Han; Yan Zheng; Guo-Zhang Xu; Xiao-Huai Wang (Cancer Causes & Control, 2015)

Spontaneous Running Wheel Improves Cognitive Functions of Mouse Associated with miRNA Expressional Alteration in Hippocampus Following Traumatic Brain Injury - Tian-hao Bao; Wei Miao; Jian-hong Han; Mei Yin; Yong Yan; Wei-wei Wang; Yu-hong Zhu (Journal of Molecular Neuroscience, 2014)

Ethyl methane sulfonate induces disease resistance in Begonia × hiemalis Fotsch. - Yang-Er Chen; Ying-Hong Zhang; Shu Yuan; Han-Mei Liu; Xian-Yin Zeng; Huai-Yu Zhang (Horticulture, Environment, and Biotechnology, 2014)

One-step integration of multiple genes into the oleaginous yeast Yarrowia lipolytica - Shuliang Gao; Linna Han; Li Zhu; Mei Ge; Sheng Yang; Yu Jiang; Daijie Chen (Biotechnology Letters, 2014)

Ambient noise spectral properties in the north area of Xisha - Lianglong Da; Chao Wang; Mei Han; Lin Zhang (Acta Oceanologica Sinica, 2014)

The evolution analysis of flood and drought in Huai River Basin of China based on monthly precipitation characteristics - Deng-Hua Yan; Dong-Mei Han; Gang Wang; Yong Yuan; Yong Hu; Hong-yang Fang (Natural Hazards, 2014)

Antiemetic Role of Thalidomide in a Rat Model of Cisplatin-Induced Emesis - Zheng-xiang Han; Jie Xu; Hong-mei Wang; Jan Ma; Xuan Sun; Xiu-ping Du (Cell Biochemistry and Biophysics, 2014)

Clinical Factors Associated With the Diagnosis and Progression of Diabetic Nephropathy - Shuang Liang; Qian Li; Han-Yu Zhu; Jian-Hui Zhou; Rui Ding; Xiang-Mei Chen; Guang-Yan Cai (Cell Biochemistry and Biophysics, 2014)

Two Chinese pedigrees for adenomatous polyposis coli: new mutations at codon 1309 and predisposition to phenotypic variations - Dai-Xiang Liao; Bing Li; Xue-Mei Du; Jun-Hui Yu; Hong Chang; Zhi-Qiang Wu; Hao-Jie Hao; You-Xin Wang; Wei-Dong Han; Shu-jun Cheng; Cheng-Hua Luo (Familial Cancer, 2014)

Morphology and molecular phylogeny for two new species of Fomitopsis (Basidiomycota) from South China - Mei-Ling Han; Jie Song; Bao-Kai Cui (Mycological Progress, 2014)

Response of bacterial pdo1, nah, and C12O genes to aged soil PAH pollution in a coke factory area - Xue-Mei Han; Yu-Rong Liu; Yuan-Ming Zheng; Xiao-Xia Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)

Degradation of oxalic acid by the mycoparasite C oniothyrium minitans plays an important role in interacting with S clerotinia sclerotiorum - Li‐Mei Zeng; Jing Zhang; Yong‐Chao Han; Long Yang; Ming‐de Wu; Dao‐Hong Jiang; Weidong Chen; Guo‐Qing Li (Environmental Microbiology, 2014)
Summary C oniothyrium minitans ( Cm ) is a mycoparasite of the phytopathogenic fungus S clerotinia sclerotiorum ( Ss ). Ss produces a virulence factor oxalic acid ( OA ) which is toxic to plants and also to Cm , and Cm detoxifies OA by degradation. In this study, two oxalate decarboxylase genes, Cmoxdc1 and Cmoxdc2 , were cloned from Cm strain Chy‐1. OA and low pH induced expression of Cmoxdc1 , but not Cmoxdc2 . Cmoxdc1 was partially responsible for OA degradation, whereas Cmoxdc2 had no effect on OA degradation. Disruption of Cmoxdc1 in Cm reduced its ability to infect Ss in dual cultures where OA accumulated. Compared with Chy ‐1, the Cmoxdc1 ‐disrupted mutants had reduced expression levels of two mycoparasitism‐related genes chitinase ( Cmch1 ) and β‐1,3‐glucanase ( Cmg1 ), and had no detectable activity of extracellular proteases in the presence of OA . On the other hand, the cultural filtrates of the Cmoxdc1 ‐disrupted mutants in OA ‐amended media showed enhanced antifungal activity, possibly because of increased production of antifungal substances under acidic pH condition resulted from reduced Cmoxdc1 ‐ mediated OA degradation. This study provides direct genetic evidence of OA degradation regulating mycoparasitism and antibiosis of Cm against Ss , and sheds light on the sophisticated strategies of Cm in interacting with metabolically active mycelia and dormant sclerotia of Ss .

A new epimer of ocotillol from stems and leaves of American ginseng - Liu Han; Mei-Yu Lin; Qian Zheng; Hai-Yu Liu; Hai-Yan Liu; Gang Dong; Jin-Ping Liu; Ping-Ya Li (Natural Product Research, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Pharmacokinetics study of asperosaponin VI and its metabolites cauloside A, HN saponin F and hederagenin - Er-Wei Liu; Jia-Long Wang; Li-Feng Han; Yan-Xu Chang; Tao Wang; Yan Huo; Lei Wang; Xiu-Mei Gao (Journal of Natural Medicines, 2014)

Study on Changes of Clinical Indicators and Key Proteins from Fluoride Exposure - Hong He; Hongmei Wang; Mei Han; Yuguo Jiao; Congli Ma; Han Zhang; Zhou Zhou (Biological Trace Element Research, 2014)

Potential genetic anticipation in hereditary leiomyomatosis-renal cell cancer (HLRCC) - Mei Hua Wong; Chuen Seng Tan; Soo Chin Lee; Yvonne Yong; Aik Seng Ooi; Joanne Ngeow; Min Han Tan (Familial Cancer, 2014)

Age and provenance of the Ergunahe Group and the Wubinaobao Formation, northeastern Inner Mongolia, NE China: implications for tectonic setting of the Erguna Massif - Yi-Han Zhang; Wen-Liang Xu; Jie Tang; Feng Wang; Mei-Jun Xu; Wei Wang (International Geology Review, 2014)

Differences in Gene Expression and Regulation during Ontogenetic Phase Change in Apple Seedlings - Yan Gao; Feng Qiu Yang; Xin Cao; Chun Min Li; Yi Wang; Yong Bo Zhao; Guang Juan Zeng; Dong Mei Chen; Zhen Hai Han; Xin Zhong Zhang (Plant Molecular Biology Reporter, 2014)

A Simple One-Step PCR Walking Method and Its Application of Bacterial rRNA for Sequencing Identification - Hongfa Zhang; Chunping You; Jing Ren; Dan Xu; Mei Han; Wenyan Liao (Current Microbiology, 2014)

Analysis of promoters of microRNAs from a Glycine max degradome library - Yi-qiang Han; Zheng Hu; Dian-feng Zheng; Ya-mei Gao (Journal of Zhejiang University-SCIENCE B, 2014)

The role of Gracilaria lemaneiformis in eliminating the dissolved inorganic carbon released from calcification and respiration process of Chlamys farreri - Zeng Jie Jiang; Jian Guang Fang; Ting Ting Han; Yu Ze Mao; Jia Qi Li; Mei Rong Du (Journal of Applied Phycology, 2014)

A Simple One-Step PCR Walking Method and Its Application of Bacterial rRNA for Sequencing Identification - Hongfa Zhang; Chunping You; Jing Ren; Dan Xu; Mei Han; Wenyan Liao (Current Microbiology, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

A Comparative Study on the Effects of Excess Iodine and Herbs with Excess Iodine on Thyroid Oxidative Stress in Iodine-Deficient Rats - Tianshu Gao; Rui Shi; Tengche Qi; Huisi Yin; Lan Mei; Xiaoqing Han; Peng Cui (Biological Trace Element Research, 2014)

Dishevelled-1 (Dvl-1) Protein: a Potential Participant of Oxidative Stress Induced by Selenium Deficiency - Han-dong Zhao; Mei-na Sun; Meng-di Li; Feng-lan Li; Hui Li (Biological Trace Element Research, 2014)

Lack of association between the polymorphisms of hypoxia-inducible factor 1A (HIF1A) gene and SLE susceptibility in a Chinese population - Chen-Chen Feng; Qian-Ling Ye; Yan Zhu; Rui-Xue Leng; Gui-Mei Chen; Jie Yang; Han Cen; Xiao-Ke Yang; Rui Li; Wang-Dong Xu; Hai-Feng Pan; Dong-Qing Ye (Immunogenetics, 2014)

Haloplanus salinus sp. nov., an extremely halophilic archaeon from a Chinese marine solar saltern - Xing–Xing Qiu; Mei-Lin Zhao; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2013)

Dopamine transporter availability in heroin-dependent subjects and controls: longitudinal changes during abstinence and the effects of Jitai tablets treatment - Ying Liu; Mei Han; Xingdang Liu; Yanping Deng; Yu Li; Jie Yuan; Rongbin Lv; Yuankai Wang; Guangming Zhang; Jinlong Gao (Psychopharmacology, 2013)

Two new Fomitopsis species from southern China based on morphological and molecular characters - Hai-Jiao Li; Mei-Ling Han; Bao-Kai Cui (Mycological Progress, 2013)

Halorubrum rubrum sp. nov., an extremely halophilic archaeon from a Chinese salt lake - Xing-Xing Qiu; Mei-Lin Zhao; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Antonie van Leeuwenhoek, 2013)

Characterization of Genes Encoding Granule-Bound Starch Synthase in Sacred Lotus Reveals Phylogenetic Affinity of Nelumbo to Proteales - Chao Gu; Lu Wang; Liyao Zhang; Yanling Liu; Mei Yang; Zhaonian Yuan; Shaohua Li; Yuepeng Han (Plant Molecular Biology Reporter, 2013)

Golgi apparatus analyzed by cryo-electron microscopy - Hong-Mei Han; Cedric Bouchet-Marquis; Jan Huebinger; Markus Grabenbauer (Histochemistry and Cell Biology, 2013)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

(−)-Epigallocatechin-3-gallate alleviates spatial memory impairment in APP/PS1 mice by restoring IRS-1 signaling defects in the hippocampus - Ning Jia; Kun Han; Jing-Jing Kong; Xiu-Mei Zhang; Sha Sha; Gui-Ru Ren; Yun-Peng Cao (Molecular and Cellular Biochemistry, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Effects of chronic social defeat stress on behavior and choline acetyltransferase, 78-kDa glucose-regulated protein, and CCAAT/enhancer-binding protein (C/EBP) homologous protein in adult mice - Tong Zhao; Guang-Biao Huang; Sushma Shrestha Muna; Tarique Rajasaheb Bagalkot; Hong-Mei Jin; Han-Jung Chae; Young-Chul Chung (Psychopharmacology, 2013)

LPS induces cardiomyocyte injury through calcium-sensing receptor - Hong-yu Wang; Xue-yan Liu; Gan Han; Zhu-ying Wang; Xiao-xie Li; Zhi-mei Jiang; Chun-ming Jiang (Molecular and Cellular Biochemistry, 2013)

A consensus envelope protein domain III can induce neutralizing antibody responses against serotype 2 of dengue virus in non-human primates - Hsin-Wei Chen; Shih-Jen Liu; Yi-Shiuan Li; Hsueh-Hung Liu; Jy-Ping Tsai; Chen-Yi Chiang; Mei-Yu Chen; Chyi-Sing Hwang; Chin-Cheng Huang; Hui-Mei Hu; Han-Hsuan Chung; Sze-Hsien Wu; et al. (Archives of Virology, 2013)

Dual liver transplantation - Hao Chen; Ying Zhang; Yong-mei Han; Emmanue Huguet; Dong-sheng Huang; Jia-hong Dong (Journal of Zhejiang University-SCIENCE B, 2013)

Association of AFF1 rs340630 and AFF3 rs10865035 polymorphisms with systemic lupus erythematosus in a Chinese population - Han Cen; Rui-Xue Leng; Wei Wang; Mo Zhou; Chen-Chen Feng; Gui-Mei Chen; Rui Li; Hai-Feng Pan; Xiang-Pei Li; Dong-Qing Ye (Immunogenetics, 2012)

Mitochondrial dysfunction and cellular metabolic deficiency in Alzheimer’s disease - Xue-Mei Gu; Han-Chang Huang; Zhao-Feng Jiang (Neuroscience Bulletin, 2012)

Choline inhibits angiotensin II-induced cardiac hypertrophy by intracellular calcium signal and p38 MAPK pathway - Shu Wang; Hong-mei Han; Zhen-wei Pan; Peng-zhou Hang; Li-hua Sun; Ya-nan Jiang; Hao-xin Song; Zhi-min Du; Yan Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Angiopoietin-1 preconditioning enhances survival and functional recovery of mesenchymal stem cell transplantation - Xian-bao Liu; Han Chen; Hui-qiang Chen; Mei-fei Zhu; Xin-yang Hu; Ya-ping Wang; Zhi Jiang; Yin-chuan Xu; Mei-xiang Xiang; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Isolation and characterization of a Chinese strain of human enterovirus 74 from a healthy child in the Tibet Autonomous Region of China - Jitao Wang; Yong Zhang; Mei Hong; Xiaolei Li; Shuangli Zhu; Dongmei Yan; Dongyan Wang; Hongqiu An; Tsewang; Jianrong Han; Wenbo Xu (Archives of Virology, 2012)

Amino Acid Profiles of Bivalve Mollusks from Beibu Gulf, China - De-Wei Chen; Jian Su; Xiao-Ling Liu; Dong-Mei Yan; Ying Lin; Wei-Ming Jiang; Xiao-Han Chen (Journal of Aquatic Food Product Technology, 2012)

Influences of free-air CO2 enrichment (FACE), nitrogen fertilizer and crop residue incorporation on CH4 emissions from irrigated rice fields - Baohua Xie; Zaixing Zhou; Baoling Mei; Xunhua Zheng; Haibo Dong; Rui Wang; Shenghui Han; Feng Cui; Yinghong Wang; Jianguo Zhu (Nutrient Cycling in Agroecosystems, 2012)

Automated Sample Clean-up and Fraction of Organochlorine Pesticides in Sediments Using the SPE–GPC–VAP System - Mei Han; Zhifen Gan; Shuxuan Liang; Lihui An; Xingru Zhao (Bulletin of Environmental Contamination and Toxicology, 2012)

Identification of markers linked to major gene loci involved in determination of fruit shape index of apples (Malus domestica) - Huan Huan Sun; Yong Bo Zhao; Chun Min Li; Dong Mei Chen; Yi Wang; Xin Zhong Zhang; Zhen Hai Han (Euphytica, 2012)

Expansins are involved in cell growth mediated by abscisic acid and indole-3-acetic acid under drought stress in wheat - Mei-rong Zhao; Yang-yang Han; Ya-nan Feng; Feng Li; Wei Wang (Plant Cell Reports, 2012)

Characterization of Prototheca zopfii Associated with Outbreak of Bovine Clinical Mastitis in Herd of Beijing, China - Jian Gao; Han-qi Zhang; Jian-zhong He; Yang-hua He; Shu-mei Li; Rong-guang Hou; Qiao-xing Wu; Yang Gao; Bo Han (Mycopathologia, 2012)

Deletion of RBP-J in adult mice leads to the onset of aortic valve degenerative diseases - Zhi Li; Lei Feng; Chun-Mei Wang; Qi-Jun Zheng; Bi-Jun Zhao; Wei Yi; Jin-Zhou Zhang; Yue-Min Wang; Hai-Tao Guo; Ding-Hua Yi; Hua Han (Molecular Biology Reports, 2012)

Phylogenetic relationships between Leymus (Poaceae, Triticeae) and related diploid Triticeae species based on isozyme and genome-specific random amplified polymorphic DNA (RAPD) markers - Rui-Wu Yang; Min-Han Zhong; Xue-Mei Zou; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou (Plant Biosystems, 2012)

Three-dimensional interpretation of sparse survey line MT data: Synthetic examples - Chang-Hong Lin; Han-Dong Tan; Qing Shu; Tuo Tong; Yu-Mei Zhang (Applied Geophysics, 2012)

Eco-compensation of wetlands in Yellow River Delta of Shandong Province, China - Mei Han; Jinlong Cui; Zhen Hao; Yi Wang; Renqing Wang (Chinese Geographical Science, 2012)

Cordyceps militaris (Hypocreales: Cordycipitaceae): transcriptional analysis and molecular characterization of cox1 and group I intron with putative LAGLIDADG endonuclease - Zhuangli Zheng; Keqing Jiang; Chunhua Huang; Caiying Mei; Richou Han (World Journal of Microbiology and Biotechnology, 2012)

Comparative analyses of leaf anatomy of dicotyledonous species in Tibetan and Inner Mongolian grasslands - JianJing Ma; ChengJun Ji; Mei Han; TingFang Zhang; XueDong Yan; Dong Hu; Hui Zeng; JinSheng He (Science China Life Sciences, 2012)

Isolation and Characterization of the Iron-Regulated MxbHLH01 Gene in Malus xiaojinensis - Hong-Mei Xu; Yi Wang; Feng Chen; Xin-Zhong Zhang; Zhen-Hai Han (Plant Molecular Biology Reporter, 2011)

Selecting the optimum location of the corner using gravity gradient method - Peng-Fei Sun; Yan-Gang Wu; Chun-Cheng Yang; Zhao-Hong Han; Mei-Ning Fan (Applied Geophysics, 2011)

AAPS Workshop Report: Strategies to Address Therapeutic Protein–Drug Interactions during Clinical Development - Sandhya Girish; Steven W Martin; Mark C Peterson; Lei K. Zhang; Hong Zhao; Joseph Balthasar; Raymond Evers; Honghui Zhou; Min Zhu; Lewis Klunk; Chao Han; Eva Gil Berglund; et al. (The AAPS Journal, 2011)

Methyl jasmonate- and salicylic acid-induced d-chiro-inositol production in suspension cultures of buckwheat (Fagopyrum esculentum) - Yao-hui Hu; Ya-tong Yu; Chun-hong Piao; Jun-mei Liu; Han-song Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Effective Gene Delivery to Mesenchymal Stem Cells Based on the Reverse Transfection and Three-Dimensional Cell Culture System - Cai-Xia He; Ni Li; Yu-Lan Hu; Xiu-Mei Zhu; Hai-Jie Li; Min Han; Pei-Hong Miao; Zhong-Jie Hu; Gang Wang; Wen-Quan Liang; Yasuhiko Tabata; Jian-Qing Gao (Pharmaceutical Research, 2011)

Application of EM algorithms for seismic facices classification - Mei Han; Yong Zhao; Gaoming Li; Albert C. Reynolds (Computational Geosciences, 2011)

Species-specific and needle age-related responses of photosynthesis in two Pinus species to long-term exposure to elevated CO2 concentration - Yu-Mei Zhou; Cun-Guo Wang; Shi-Jie Han; Xu-Bing Cheng; Mai-He Li; A-Nan Fan; Xiu-Xiu Wang (Trees, 2011)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

Generation of transgenic watermelon resistant to Zucchini yellow mosaic virus and Papaya ringspot virus type W - Tsong-Ann Yu; Chu-Hui Chiang; Hui-Wen Wu; Chin-Mei Li; Ching-Fu Yang; Jun-Han Chen; Yu-Wen Chen; Shyi-Dong Yeh (Plant Cell Reports, 2011)

Determination of optimal carbon source and pH value for sclerotial formation of Polyporus umbellatus under artificial conditions - Yong-Mei Xing; Juan Chen; Ya-Li Lv; Han-Qiao Liang; Shun-Xing Guo (Mycological Progress, 2011)

Carbon and nitrogen storage in plant and soil as related to nitrogen and water amendment in a temperate steppe of northern China - Fu-Mei Lü; Xiao-Tao Lü; Wei Liu; Xu Han; Guang-Ming Zhang; De-Liang Kong; Xing-Guo Han (Biology and Fertility of Soils, 2011)

Polymorphism of prion protein gene in sheep of Inner Mongolian, China - Cai-Xia Han; Hong-Xiang Liu; Yi-Xin Lu; Ming-Xin Song; De-Ming Zhao; Xiang-Mei Zhou; Li-Feng Yang; Xiao-Yun Li (Virus Genes, 2011)

Abnormalities in periodontal and salivary tissues in conditional presenilin 1 and presenilin 2 double knockout mice - Wenfei Han; Tingting Ji; Lili Wang; Li Yan; Haibo Wang; Zhenlan Luo; Bing Mei; Jiansheng Su (Molecular and Cellular Biochemistry, 2011)

A new cytotoxic iridoid from Callicarpa nudiflora - Wen-Li Mei; Zhuang Han; Hai-Bin Cui; You-Xing Zhao; Yuan-Yuan Deng; Hao-Fu Dai (Natural Product Research, 2010)

Distribution, development and proliferation of interstitial cells of Cajal in murine colon: an immunohistochemical study from neonatal to adult life - Juan Han; Wen-Hao Shen; You-Zhao Jiang; Bin Yu; Yang-Tao He; Nan Li; Feng Mei (Histochemistry and Cell Biology, 2010)

Evaluation of the geology-environmental capacity of buildings based on the ANFIS model of the floor area ratio - Zhen-Dong Cui; Yi-Qun Tang; Xue-Xin Yan; Chun-Ling Yan; Han-Mei Wang; Jian-Xiu Wang (Bulletin of Engineering Geology and the Environment, 2010)

A single-nucleotide polymorphism of the TNFAIP3 gene is associated with systemic lupus erythematosus in Chinese Han population - Li-Qiong Cai; Zai-Xing Wang; Wen-Sheng Lu; Jian-Wen Han; Liang-Dan Sun; Wen-Hui Du; Shu-Mei Zhang; Xian-Bo Zuo; Xue-Jun Zhang; Sen Yang (Molecular Biology Reports, 2010)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Molecular Cloning and Characterization of a Gene Encoding Eukaryotic Initiation Factor iso4E in Tomato (Solanum lycopersicum) - Yu-Yang Zhang; Mei-Fang Qi; Jin Sun; Xiao-Hui Zhang; He-Li Shi; Han-Xia Li; Zhi-Biao Ye (Plant Molecular Biology Reporter, 2009)

Memory deficits and neurochemical changes induced by C-reactive protein in rats: implication in Alzheimer’s disease - Huan-Bing Lin; Xue-Mei Yang; Tie-Jun Li; Yu-Fang Cheng; Han-Ting Zhang; Jiang-Ping Xu (Psychopharmacology, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Anthraquinone derivatives from Micromonospora rhodorangea - Chun-Mei Xue; Li Tian; Wen-Han Lin; Zhi-Wei Deng (Natural Product Research, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

QTL analysis of kernel shape and weight using recombinant inbred lines in wheat - Xian-Yin Sun; Ke Wu; Yan Zhao; Fan-Mei Kong; Guan-Zhu Han; Hong-Ming Jiang; Xing-Jiao Huang; Rui-Jun Li; Hong-Gang Wang; Si-Shen Li (Euphytica, 2009)

An age-dependent proliferation is involved in the postnatal development of interstitial cells of Cajal in the small intestine of mice - Feng Mei; Jiang Zhu; Sheng Guo; De-shan Zhou; Juan Han; Bin Yu; Shi-feng Li; Zhong-yong Jiang; Cheng-jie Xiong (Histochemistry and Cell Biology, 2009)

New BZLF1 sequence variations in EBV-associated undifferentiated nasopharyngeal carcinoma in southern China - Kun-Mei Ji; Chun-Lin Li; Guang Meng; Ai-Dong Han; Xu-Li Wu (Archives of Virology, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Adrenal myelolipoma within myxoid cortical adenoma associated with Conn’s syndrome - Lu Hong-sheng; Gan Mei-fu; Chen Han-song; Huang Shan-qiang (Journal of Zhejiang University-SCIENCE B, 2008)

Fine mapping and candidate gene analysis of hwh1 and hwh2, a set of complementary genes controlling hybrid breakdown in rice - Wenzhu Jiang; Sang-Ho Chu; Rihua Piao; Joong-Hyoun Chin; Yong-Mei Jin; Joohyun Lee; Yongli Qiao; Longzhi Han; Zongze Piao; Hee-Jong Koh (Theoretical and Applied Genetics, 2008)

Evolutionary and functional study of the CDPK gene family in wheat (Triticum aestivum L.) - Ai-Li Li; Yuan-Fang Zhu; Xiao-Mei Tan; Xiang Wang; Bo Wei; Han-Zi Guo; Zeng-Lin Zhang; Xiao-Bo Chen; Guang-Yao Zhao; Xiu-Ying Kong; Ji-Zeng Jia; Long Mao (Plant Molecular Biology, 2008)

The Influence of Surface Trapping and Dark States on the Fluorescence Emission Efficiency and Lifetime of CdSe and CdSe/ZnS Quantum Dots - Hong-Mei Gong; Zhang-Kai Zhou; Hao Song; Zhong-Hua Hao; Jun-Bo Han; Yue-Ying Zhai; Si Xiao; Qu-Quan Wang (Journal of Fluorescence, 2007)

Effect of heartbeat perception on heartbeat evoked potential waves - Hui Yuan; Hong-Mei Yan; Xiao-Gang Xu; Fei Han; Qing Yan (Neuroscience Bulletin, 2007)

No changes in densities of cannabinoid receptors in the superior temporal gyrus in schizophrenia - Chao Deng; Mei Han; Xu-Feng Huang (Neuroscience Bulletin, 2007)

Hydroquinone–Benzonitrile System: Intramolecular Charge-Transfer and Computational Studies - Kuangsen Sung; Pin-Mei Huang; Chi-Han Zhou (Journal of Fluorescence, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

In situ expression of the GmNMH7 gene is photoperiod-dependent in a unique soybean (Glycine max [L.] Merr.) flowering reversion system - Cunxiang Wu; Qibin Ma; Kwan-Mei Yam; Ming-Yan Cheung; Yunyuan Xu; Tianfu Han; Hon-Ming Lam; Kang Chong (Planta, 2006)

The influence of muscle type and dystrophin deficiency on murine expression profiles - Judith N. Haslett; Peter B. Kang; Mei Han; Alvin T. Kho; Despina Sanoudou; Jay M. Volinski; Alan H. Beggs; Isaac S. Kohane; Louis M. Kunkel (Mammalian Genome, 2005)

Phenotypic polymorphism of CYP2A6 activity in a Chinese population - Ping Xu; Song-Lin Huang; Rong-Hua Zhu; Xing-Mei Han; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)

A study of the surface-emerging palaeochannels on the South Coast Plain of Laizhou Bay - Mei Han; Dao-gao Li; Ming-hua Zhao; Ai-xia Jiang (Chinese Geographical Science, 2000)

Hair concentrations of calcium, iron, and zinc in pregnant women and effects of supplementation - Po Lau Leung; Han Ming Huang; Da Ze Sun; MeI Guang Zhu (Biological Trace Element Research, 1999)

Hair and serum calcium, iron, copper, and zinc levels during normal pregnancy at three trimesters - Han Ming Huang; Po Lau Leung; Da Ze Sun; Mei Guang Zhu (Biological Trace Element Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)